Powder and granular material and method for producing powder and granular material
By preparing powder particles with specific pore structures, the problem of insufficient dispersion of polymer particles in the resin is solved, and better impact resistance and surface appearance are achieved.
Patent Information
- Application Number
- CN202080062288.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2020-09-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-09-25
AI Technical Summary
In the process of dispersing polymer particles in a resin, the dispersion is insufficient, making it difficult to achieve ideal impact resistance and surface appearance.
By preparing powder particles with specific pore structures, specifically, the pores of powder particles have an average pore size of 0.03 μm to 1.00 μm, and the total volume of the pores reaches 0.0600 mL/g or more, to improve the polymer Dispersibility of particles in resin.
The superior dispersion of polymer particles in the resin is achieved, and the impact resistance and surface appearance quality of the resin composition are improved.
Smart Images

Figure BDA0003531796510000861 
Figure BDA0003531796510000991
Abstract
Description
Technical Field
[0001] The present invention relates to a powder or granule and a method for producing the powder or granule. Background Art
[0002] In order to improve the impact resistance of thermoplastic resins or thermosetting resins, a method of adding an elastomer, particularly polymer microparticles, to the resin is widely used.
[0003] For example, Patent Document 1 discloses a technique for obtaining a resin composition by mixing a polymer composition obtained by mixing polymer fine particles and a solid epoxy resin and powderizing the mixture, and a liquid epoxy resin.
[0004] Patent document 2 discloses a polymer composition comprising (i) a polymer (P1) and (ii) a polymer obtained by a multi-stage process, wherein the multi-stage process comprises: a stage (a) comprising (a) a polymer (A1) having a glass transition temperature of less than 10°C; a stage (b) comprising (b) a polymer (B1) having a glass transition temperature of at least 60°C; and a stage (c) comprising (c) a polymer (C1) having a glass transition temperature of at least 30°C.
[0005] Patent Document 3 discloses a polymer composition comprising a (meth)acrylic acid polymer (P1) and a multistage polymer, wherein the multistage polymer accounts for at least 20% by weight of the polymer composition.
[0006] (Prior art literature)
[0007] Patent Document 1: International Publication No. WO2016 / 102658
[0008] Patent Document 2: International Publication No. WO2016 / 102682
[0009] Patent Document 3: International Publication No. WO2016 / 102666 Summary of the invention
[0010] (Problems to be solved by the present invention)
[0011] However, from the viewpoint of the dispersibility of polymer microparticles in resin, the above-mentioned conventional techniques are not sufficient and there is room for further improvement.
[0012] One embodiment of the present invention has been made in view of the above problems, and an object of the present invention is to provide a novel powder or granule having excellent dispersibility of polymer fine particles in a matrix resin and a method for producing the powder or granule.
[0013] (Methods of solving the problem)
[0014] The present inventors have repeatedly conducted in-depth studies to solve the above-mentioned problems, and as a result, have independently discovered that if a powder or particle has a specific amount of pores and the pores have a specific average pore diameter, the polymer particles of the powder or particle have excellent dispersibility in the matrix resin, thereby completing the invention involved in one embodiment (first embodiment) of the present invention.
[0015] That is, the powder and granule according to one embodiment of the present invention comprises polymer microparticles (A) and resin (B), wherein the polymer microparticles (A) comprise a rubber-containing graft copolymer, wherein the rubber-containing graft copolymer comprises an elastomer and a graft portion graft-bonded to the elastomer, wherein the elastomer comprises one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber, and the graft portion comprises a polymer having a specific structural unit, wherein the specific structural unit is derived from an aromatic vinyl monomer, a vinyl cyanide monomer and a (meth)acrylate monomer. The invention relates to a method for preparing an aqueous solution of at least one monomer, wherein the resin (B) is a liquid having a viscosity of 100 mPa·s to 1000000 mPa·s at 25°C, or is a semisolid or solid. When the total amount of the polymer particles (A) and the resin (B) is set to 100 weight %, the polymer particles (A) are 50 to 99 weight %, the resin (B) is 1 to 50 weight %, and the powder or granule has pores with an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is 0.0600 mL / g or more.
[0016] In addition, a method for producing a powder or granule according to one embodiment of the present invention comprises: a coagulation step of preparing an agglomerate containing polymer microparticles (A) and a resin (B); and a drying step of subjecting the agglomerate to airflow drying or freeze drying, wherein the polymer microparticles (A) comprise a rubber-containing graft copolymer, the rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastomer comprising at least one rubber selected from the group consisting of a diene rubber, a (meth)acrylate rubber, and an organosiloxane rubber, and the graft portion A polymer having a specific structural unit, wherein the specific structural unit is derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer, wherein the resin (B) is a liquid, semisolid, or solid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., and when the total amount of the polymer particles (A) and the resin (B) is 100 weight %, the polymer particles (A) are 50 to 99 weight % and the resin (B) is 1 to 50 weight %.
[0017] (Effects of the Invention)
[0018] According to one embodiment of the present invention, a powder or granule having excellent dispersibility of polymer microparticles in a matrix resin can be provided. DETAILED DESCRIPTION
[0019] An embodiment of the present invention is described below, but the present invention is not limited thereto. The present invention is not limited to the various configurations described below, and various changes can be made within the scope shown in the present invention. In addition, embodiments or embodiments obtained by appropriately combining the technical means respectively disclosed in different embodiments or embodiments are also included in the technical scope of the present invention. Moreover, new technical features can be formed by combining the technical means respectively disclosed in each embodiment. In addition, all academic literature and patent literature recorded in this specification are cited as references in this specification. In addition, in this specification, unless otherwise specified, "A to B" indicating a numerical range means "above A (including A and larger than A) and below B (including B and smaller than B)".
[0020] [I. First embodiment]
[0021] [I-1. Technical concept of one embodiment of the present invention (first embodiment)]
[0022] It is very difficult to disperse polymer particles having a volume average particle size of less than 1 μm in a resin (e.g., a thermosetting resin such as epoxy resin) at an industrial level. The powder (also referred to as secondary particles) formed by the aggregation of primary particles of polymer particles (i.e., particles having a volume average particle size of less than 1 μm) can have a volume average particle size of more than 1 μm. The mixing of the powder of polymer particles and the thermosetting resin can be easily performed by mechanical mixing. However, in the existing powder of polymer particles, in the mixture of the powder and the thermosetting resin, i.e., the resin composition, the primary particles of the polymer particles will agglomerate with each other in the thermosetting resin without separation. Therefore, the toughness improvement effect and impact resistance improvement effect of the cured product of the resin composition brought by the polymer particles are small, and the surface appearance of the cured product is also very poor.
[0023] One embodiment of the present invention is completed in view of the above-mentioned problems, and its purpose is as described above. In other words, the purpose of one embodiment of the present invention is to provide a powder that can be used to realize a resin composition, wherein the polymer particles are uniformly dispersed in a matrix resin.
[0024] In the process of repeated and intensive research to solve the above-mentioned problems, the present inventors independently found the following surprising insight: if a powder or granule has a specific number of pores and the pores have a specific average pore diameter, the polymer particles of the powder or granule have excellent dispersibility in the matrix resin. The reason for this is not clear, but it can be inferred as follows.
[0025] A powder or granule having a specific amount of pores (e.g., a total volume of pores of 0.0600 mL / g or more) and a specific average pore diameter (e.g., an average pore diameter of 0.03 μm to 1.00 μm) has a larger surface area than a powder or granule not having a specific amount of pores and a specific average pore diameter. Here, "a powder or granule not having a specific amount of pores and a specific average pore diameter" means: (a) a powder or granule having a total volume of all pores of less than a specific amount (e.g., 0.0600 mL / g), or (b) a powder or granule having most of pores exceeding a specific average pore diameter (e.g., an average pore diameter of 1.00 μm). The larger the surface area of the powder, the larger the contact area between (a) the matrix resin and the powder, and / or (b) the easier it is for the powder to contain the matrix resin due to the capillary phenomenon of the pores of the powder. For these reasons, it is speculated that the powder is "easy to be wetted" by the matrix resin. It is therefore speculated that the easier it is for the powder to be wetted by the matrix resin, the easier it is to disperse the polymer particles into the matrix resin by subsequent mechanical pulverization. The inventors have discovered such a novel insight and completed the present invention. However, one embodiment of the present invention is not limited to these novel insights.
[0026] 〔I-2. Powder and granular body〕
[0027] The powder and granule involved in one embodiment of the present invention contains polymer particles (A) and resin (B). The polymer particles (A) contain a rubber-containing graft copolymer, which has an elastomer and a graft portion graft-bonded to the elastomer. The elastomer contains one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber. The graft portion contains a polymer having a specific structural unit, which is derived from one or more monomers selected from aromatic vinyl monomers, vinyl cyanide monomers and (meth)acrylate monomers. The resin (B) is a liquid having a viscosity of 100mPa·s to 1000000mPa·s at 25°C, or is a semisolid or solid. In the powder and granule, when the total amount of the polymer particles (A) and the resin (B) is set to 100% by weight, the polymer particles (A) are 50 to 99% by weight, and the resin (B) is 1 to 50% by weight. The powder or granule has pores with an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is 0.0600 mL / g or more.
[0028] Hereinafter, “the powder or granule according to one embodiment (first embodiment) of the present invention” may be referred to as “the first powder or granule.” The first powder or granule is mixed with a matrix resin (C) described later to form a resin composition.
[0029] The first powder or granule has the above-mentioned configuration, and thus has the advantage that the polymer fine particles (A) are excellently dispersed in the matrix resin. In other words, the first powder or granule has the above-mentioned configuration, and thus has the advantage that the first powder or granule can be mixed with the matrix resin (C) described later to provide a resin composition in which the polymer fine particles (A) are uniformly dispersed in the matrix resin (C).
[0030] In this specification, "powder and granule" includes both powder and granule, and refers to an aggregate of powder, granule, etc. In addition, when special distinction is required, "powder" refers to powder with a volume average particle size of 0.01mm to 0.1mm, and "granule" refers to granule with a volume average particle size of 0.1mm to 10mm. However, powder and granule may also contain coarse particles of 10mm or more. In addition, for the "volume average particle size" of powder particles smaller than 10μm, the dynamic light scattering (DLS) particle size distribution measuring device Nanotrac WaveII-EX150 (manufactured by Micro Track Bell Co., Ltd.) can be used for measurement. For the "volume average particle size" of powder particles larger than 10μm, the laser diffraction particle size distribution measuring device Micro Track MT3000II (manufactured by Micro Track Bell Co., Ltd.) can be used for measurement.
[0031] (I-2-1. Polymer microparticles (A))
[0032] The polymer fine particles (A) include a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer.
[0033] (I-2-1-1. Elastomer)
[0034] The elastomer comprises one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber. The elastomer may also comprise natural rubber other than these rubbers. The elastomer may also be referred to as an elastic part or rubber particles. In this specification, (meth)acrylate refers to acrylate and / or methacrylate.
[0035] Hereinafter, the case where the elastomer contains a diene rubber (case A) will be described. The powder-containing resin composition obtained in case A can be used to provide a cured product or a molded product having excellent toughness and impact resistance. A cured product or a molded product having excellent toughness and / or impact resistance can also be said to have excellent durability.
[0036] The diene rubber is an elastomer containing a structural unit derived from a diene monomer. The diene monomer may also be referred to as a conjugated diene monomer. In case A, the diene rubber may contain, in 100% by weight of its structural units: 50 to 100% by weight of a structural unit derived from a diene monomer, and 0 to 50% by weight of a structural unit derived from a vinyl monomer (excluding the above-mentioned diene monomer) copolymerizable with the diene monomer. In case A, the diene rubber may also contain: a structural unit derived from a (meth) acrylate monomer in a content less than that of the structural unit derived from the diene monomer.
[0037] Examples of the diene monomer include 1,3-butadiene, isoprene (ie, 2-methyl-1,3-butadiene), and 2-chloro-1,3-butadiene. These diene monomers may be used alone or in combination of two or more.
[0038] As vinyl monomers other than diene monomers that can be copolymerized with diene monomers (hereinafter sometimes referred to as vinyl monomers A), for example, there can be mentioned: (a) vinyl aromatic hydrocarbons such as styrene, α-methylstyrene, monochlorostyrene, and dichlorostyrene; (b) vinyl carboxylic acids such as acrylic acid and methacrylic acid; (c) vinyl cyanides such as acrylonitrile and methacrylonitrile; (d) halogenated vinyls such as vinyl chloride, vinyl bromide, and chloroprene; (e) vinyl acetate; (f) olefins such as ethylene, propylene, butylene, and isobutylene; (g) multifunctional monomers such as diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene; and the like. The above-mentioned vinyl monomers A may be used alone or in combination of two or more. Among the above-mentioned vinyl monomers A, styrene is particularly preferred.
[0039] In case A, as the diene rubber, butadiene rubber (also called polybutadiene rubber) composed of structural units derived from 1,3-butadiene, or a copolymer of 1,3-butadiene and styrene, i.e., butadiene-styrene rubber (also called polystyrene-butadiene) is preferred. As the diene rubber, butadiene rubber is preferred. According to this scheme, the desired effect can be exerted by making the elastomer of the polymer particles (A) contain a diene rubber. In addition, butadiene-styrene rubber is more preferred because the transparency of the obtained cured product or molded body can be improved by adjusting its refractive index.
[0040] Hereinafter, the case where the elastomer contains a (meth)acrylate rubber (case B) will be described. In case B, a wide range of polymer designs can be performed for the elastomer by combining a plurality of monomers.
[0041] The (meth)acrylate rubber is an elastomer containing a structural unit derived from a (meth)acrylate monomer. In case B, the (meth)acrylate rubber may contain, in 100% by weight of its structural units, 50 to 100% by weight of a structural unit derived from a (meth)acrylate monomer and 0 to 50% by weight of a structural unit derived from a vinyl monomer (excluding the above-mentioned (meth)acrylate monomer) copolymerizable with the (meth)acrylate monomer. In case B, the (meth)acrylate rubber may also contain a structural unit derived from a diene monomer in a smaller content than the structural unit derived from the (meth)acrylate monomer.
[0042] Examples of the (meth)acrylate monomer include: (a) alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; (b) aromatic ring-containing (meth)acrylates such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate; (c) 2-hydroxyethyl (meth)acrylate, 4-hydroxyethyl (meth)acrylate, and 4-hydroxyethyl (meth)acrylate. (meth)acrylate monomers include hydroxyalkyl (meth)acrylates such as butyl (meth)acrylate and the like; (d) glycidyl (meth)acrylates such as glycidyl (meth)acrylate and glycidyl alkyl (meth)acrylate; (e) alkoxyalkyl (meth)acrylates; (f) allyl (meth)acrylates such as allyl (meth)acrylate and allyl alkyl (meth)acrylate; (g) multifunctional (meth)acrylates such as monoethylene glycol di[(meth)acrylate], triethylene glycol di[(meth)acrylate], and tetraethylene glycol di[(meth)acrylate; and the like. These (meth)acrylate monomers may be used alone or in combination of two or more. Among these (meth)acrylate monomers, ethyl (meth)acrylate, butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred, and butyl (meth)acrylate is further preferred.
[0043] In case B, as the (meth)acrylate rubber, preferably one or more of ethyl (meth)acrylate rubber, butyl (meth)acrylate rubber and 2-ethylhexyl (meth)acrylate rubber are used, and butyl (meth)acrylate rubber is more preferred. Ethyl (meth)acrylate rubber is a rubber composed of structural units derived from ethyl (meth)acrylate, butyl (meth)acrylate rubber is a rubber composed of structural units derived from butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate rubber is a rubber composed of structural units derived from 2-ethylhexyl (meth)acrylate. By this scheme, the glass transition temperature (Tg) of the elastomer is reduced, so that polymer particles (A) and powder particles with lower Tg can be obtained. As a result, (a) the obtained resin composition containing powder particles can be used to provide a cured product or a molded body with excellent toughness, and (b) the viscosity of the resin composition can be further reduced.
[0044] As the vinyl monomer other than the (meth)acrylate monomer copolymerizable with the (meth)acrylate monomer (hereinafter also referred to as the vinyl monomer B), the monomers exemplified above as the vinyl monomer A can be cited. Only one vinyl monomer B can be used, or two or more vinyl monomers B can be used in combination. Among the vinyl monomers B, styrene is particularly preferred.
[0045] The case where the elastomer contains an organosiloxane rubber (case C) is described below. The powder-containing resin composition obtained in case C can be used to provide a cured product or a molded product having sufficient heat resistance and excellent impact resistance at low temperatures.
[0046] Examples of the organosiloxane rubber include: (a) an organosiloxane polymer composed of a silyloxy unit substituted with two alkyl groups or two aryl groups, wherein the silyloxy unit substituted with two alkyl groups or two aryl groups is, for example, dimethylsilyloxy, diethylsilyloxy, methylphenylsilyloxy, diphenylsilyloxy, dimethylsilyloxy-diphenylsilyloxy, etc.; (b) an organosiloxane polymer composed of a silyloxy unit substituted with one alkyl group or one aryl group, wherein the silyloxy unit substituted with one alkyl group or one aryl group is, for example, an organohydrogensilyloxy unit in which a part of the side chain alkyl group is substituted with a hydrogen atom, etc. These organosiloxane polymers may be used alone or in combination of two or more.
[0047] In this specification, a polymer composed of dimethylsiloxy units is referred to as dimethylsiloxy rubber, a polymer composed of methylphenylsiloxy units is referred to as methylphenylsiloxy rubber, and a polymer composed of dimethylsiloxy units and diphenylsiloxy units is referred to as dimethylsiloxy-diphenylsiloxy rubber. In case C, as the organosiloxane rubber, (a) from the viewpoint that the obtained powder-containing resin composition can be used to provide a cured product or a molded product with excellent heat resistance, one or more of dimethylsiloxy rubber, methylphenylsiloxy rubber, and dimethylsiloxy-diphenylsiloxy rubber are preferred; (b) from the viewpoint of easy availability and economical, dimethylsiloxy rubber is more preferred.
[0048] In case C, the polymer fine particles (A) preferably contain 80% by weight or more of the organosiloxane rubber, more preferably 90% by weight or more of the organosiloxane rubber, based on 100% by weight of the elastomer contained in the polymer fine particles (A). According to this embodiment, the obtained powder-containing resin composition can be used to provide a cured product or a molded product having excellent heat resistance.
[0049] In one embodiment of the present invention, the elastomer is preferably one or more selected from butadiene rubber, butadiene-styrene rubber, butadiene-(meth)acrylate rubber, ethyl (meth)acrylate rubber, butyl (meth)acrylate rubber, 2-ethylhexyl (meth)acrylate rubber, dimethylsiloxy rubber, methylphenylsiloxy rubber, and dimethylsiloxy-diphenylsiloxy rubber, and more preferably one or more selected from butadiene rubber, butadiene-styrene rubber, butyl (meth)acrylate rubber, and dimethylsiloxy rubber.
[0050] (Cross-linked structure of elastomer)
[0051] From the viewpoint of being able to maintain the dispersion stability of the polymer particles (A) in the matrix resin (C), it is preferred that a cross-linked structure is introduced into the elastomer. Regarding the method for introducing the cross-linked structure into the elastomer, a generally used technique can be adopted, for example, the following method can be cited, namely: in the manufacture of the elastomer, a cross-linked monomer such as a multifunctional monomer and / or a mercapto-containing compound is mixed with a monomer that can constitute the elastomer, and then polymerized. In this specification, the manufacture of polymers such as elastomers is also referred to as polymerizing polymers.
[0052] In addition, the following methods can be cited as methods for introducing a crosslinked structure into an organosiloxane rubber: (a) when it is necessary to polymerize an organosiloxane rubber, a multifunctional alkoxysilane compound is used together with other materials; (b) a reactive group (e.g., (a) a mercapto group and (b) a reactive vinyl group, etc.) is introduced into an organosiloxane rubber, and then a free radical reaction is carried out by adding (a) an organic peroxide or (b) a polymerizable vinyl monomer to the obtained reaction product; or (c) when it is necessary to polymerize an organosiloxane rubber, a crosslinking monomer such as a multifunctional monomer and / or a mercapto group-containing compound is mixed with other materials and then polymerized.
[0053] The multifunctional monomer can also be said to be a monomer having more than two free radical polymerizable reaction groups in the same molecule. The free radical polymerizable reaction group is preferably a carbon-carbon double bond. Here, the multifunctional monomer does not include butadiene. As the multifunctional monomer, (meth) acrylic acid esters with ethylenic unsaturated double bonds can be cited, such as (meth) acrylic acid allyl alkyl esters and (meth) acrylic acid allyl oxygen alkyl esters. As monomers with 2 (meth) acryloyl groups, di[(meth) acrylic acid] ethylene glycol ester, di[(meth) acrylic acid] butanediol ester, di[(meth) acrylic acid] butanediol ester, di[(meth) acrylic acid] hexanediol ester, di[(meth) acrylic acid] cyclohexanedimethanol ester, and di[(meth) acrylic acid] polyglycol esters can be cited. Examples of the polyglycol di(meth)acrylates include triethylene glycol di(meth)acrylate), tripropylene glycol di(meth)acrylate), tetraethylene glycol di(meth)acrylate, polyethylene glycol (600) di(meth)acrylate, and the like. In addition, examples of monomers having three (meth)acryloyl groups include trimethylolpropane tri(meth)acrylates having an alkoxy segment, tripropyl ether tri(meth)acrylate), pentaerythritol tri(meth)acrylate, and tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate. Examples of trimethylolpropane tri(meth)acrylates having an alkoxy segment include trimethylolpropane tri(meth)acrylate), and trimethylolpropane ethyl ether tri(meth)acrylate. In addition, as a monomer having four (meth)acryloyl groups, tetra[(meth)acrylate] pentaerythritol ester, tetra[(meth)acrylate] di(trimethylolpropane) ester, etc. can be mentioned. In addition, as a monomer having five (meth)acryloyl groups, penta[(meth)acrylate] dipentaerythritol ester, etc. can be mentioned. In addition, as a monomer having six (meth)acryloyl groups, hexa[(meth)acrylate] di(trimethylolpropane) ester, etc. can be mentioned. As a multifunctional monomer, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, divinylbenzene, etc. can also be mentioned.
[0054] As the mercapto-containing compound, alkyl-substituted mercaptan, allyl-substituted mercaptan, aryl-substituted mercaptan, hydroxyl-substituted mercaptan, alkoxy-substituted mercaptan, cyano-substituted mercaptan, amino-substituted mercaptan, silyl-substituted mercaptan, acid-substituted mercaptan, halogen-substituted mercaptan and acyl-substituted mercaptan can be mentioned. As the alkyl-substituted mercaptan, an alkyl-substituted mercaptan having 1 to 20 carbon atoms is preferred, and an alkyl-substituted mercaptan having 1 to 10 carbon atoms is more preferred. As the aryl-substituted mercaptan, a phenyl-substituted mercaptan is preferred. As the alkoxy-substituted mercaptan, an alkoxy-substituted mercaptan having 1 to 20 carbon atoms is preferred, and an alkoxy-substituted mercaptan having 1 to 10 carbon atoms is more preferred. As the acid-substituted mercaptan, an alkyl-substituted mercaptan having a carboxyl group and 1 to 10 carbon atoms, or an aryl-substituted mercaptan having a carboxyl group and 1 to 12 carbon atoms is preferred.
[0055] (Glass transition temperature of elastomer)
[0056] The glass transition temperature of the elastomer is preferably 80°C or less, more preferably 70°C or less, more preferably 60°C or less, more preferably 50°C or less, more preferably 40°C or less, more preferably 30°C or less, more preferably 20°C or less, more preferably 10°C or less, more preferably 0°C or less, more preferably -20°C or less, more preferably -40°C or less, more preferably -45°C or less, more preferably -50°C or less, more preferably -55°C or less, more preferably -60°C or less, more preferably -65°C or less, more preferably -70°C or less, more preferably -75°C or less, more preferably -80°C or less, more preferably -85°C or less, more preferably -90°C or less, more preferably -95°C or less, more preferably -100°C or less, more preferably -105°C or less, more preferably -110°C or less, more preferably -115°C or less, further preferably -120°C or less, particularly preferably -125°C or less. In this specification, "glass transition temperature" may be referred to as "Tg". By the above scheme, polymer microparticles (A) having a relatively low Tg and granules having a relatively low Tg can be obtained. As a result, the obtained powder-containing resin composition can be used to provide a cured product or molded product having excellent toughness. In addition, the viscosity of the obtained powder-containing resin composition can be further reduced by the above scheme. The Tg of the elastomer can be obtained by measuring the viscoelasticity of a flat plate composed of polymer particles (A). Specifically, the Tg can be measured as follows: (1) For a flat plate composed of polymer particles (A), a dynamic viscoelasticity measurement device (such as DVA-200 manufactured by IT Measurement and Control Co., Ltd.) is used to perform a dynamic viscoelasticity measurement under tensile conditions to obtain a tanδ coordinate graph; (2) On the obtained tanδ coordinate graph, the peak temperature of tanδ is determined as the glass transition temperature. Here, if multiple peaks are obtained in the tanδ coordinate graph, the lowest peak temperature is determined as the glass transition temperature of the elastomer.
[0057] On the other hand, the Tg of the elastomer is preferably greater than 0°C, more preferably above 20°C, further preferably above 50°C, particularly preferably above 80°C, and most preferably above 120°C. This allows a cured product to be obtained that can suppress a decrease in the elastic modulus (rigidity) of the resulting cured product or molded product, i.e., has a sufficient elastic modulus (rigidity).
[0058] The Tg of the elastomer can be determined according to the components of the structural units contained in the elastomer, etc. In other words, the Tg of the obtained elastomer can be adjusted by changing the monomer components used when producing (polymerizing) the elastomer.
[0059] Here, in the case of assuming that a homopolymer is polymerized from only one monomer, the group of monomers that realize a homopolymer having a Tg greater than 0°C is referred to as monomer group a. In addition, in the case of assuming that a homopolymer is polymerized from only one monomer, the group of monomers that realize a homopolymer having a Tg lower than 0°C is referred to as monomer group b. An elastomer containing 50 to 100% by weight (more preferably 65 to 99% by weight) of a structural unit derived from at least one monomer in monomer group a and 0 to 50% by weight (more preferably 1 to 35% by weight) of a structural unit derived from at least one monomer in monomer group b is referred to as elastomer X. The Tg of the elastomer X is greater than 0°C. In addition, when the elastomer contains the elastomer X, the obtained powder-containing resin composition can be used to provide a cured product or a molded product having sufficient rigidity.
[0060] Even when the Tg of the elastomer is higher than 0° C., it is still preferred that a cross-linked structure be introduced into the elastomer. Examples of the method for introducing a cross-linked structure include the methods described above.
[0061] Examples of monomers that can belong to the monomer group a include, but are not limited to: unsubstituted vinyl aromatic compounds such as styrene and 2-vinylnaphthalene; substituted vinyl aromatic compounds such as α-methylstyrene; cycloalkylated vinyl aromatic compounds such as 3-methylstyrene, 4-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,5-dimethylstyrene, 2,4,6-trimethylstyrene; cycloalkoxylated vinyl aromatic compounds such as 4-methoxystyrene and 4-ethoxystyrene; ring halogenated vinyl aromatic compounds such as 2-chlorostyrene and 3-chlorostyrene; cyclic ester substituted vinyl aromatic compounds such as 4-acetoxystyrene Vinyl aromatic compounds; ring-hydroxylated vinyl aromatic compounds such as 4-hydroxystyrene; vinyl esters such as vinyl benzoate and vinyl cyclohexanoate; vinyl halides such as vinyl chloride; aromatic monomers such as acenaphthene and indene; alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, and isopropyl methacrylate; aromatic methacrylates such as phenyl methacrylate; methacrylates such as isobornyl methacrylate and trimethylsilyl methacrylate; methacrylic monomers including methacrylic acid derivatives such as methacrylonitrile; certain acrylic esters such as isobornyl acrylate and tert-butyl acrylate; acrylic monomers including acrylic acid derivatives such as acrylonitrile; and the like. In addition, as monomers that can belong to the monomer group a, there can be mentioned: monomers that can achieve a homopolymer having a Tg of 120° C. or higher when polymerized into a homopolymer, such as acrylamide, isopropyl acrylamide, N-vinyl pyrrolidone, isobornyl methacrylate, dicyclopentyl methacrylate, 2-methyl-2-adamantyl methacrylate, 1-adamantyl acrylate, and 1-adamantyl methacrylate, etc. These monomers a may be used alone or in combination of two or more.
[0062] As the monomer b, ethyl acrylate, butyl acrylate (another name: butyl acrylate), 2-ethylhexyl acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, etc. can be cited. Only one of these monomers b can be used, or two or more can be used in combination. Among these monomers b, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate are particularly preferred.
[0063] (Volume average particle size of elastomer)
[0064] The volume average particle size of the elastomer is preferably 0.03 μm to 50.00 μm, more preferably 0.05 μm to 10.00 μm, more preferably 0.08 μm to 2.00 μm, more preferably 0.10 μm to 1.00 μm, further preferably 0.10 μm to 0.80 μm, and particularly preferably 0.10 μm to 0.50 μm. If the volume average particle size of the elastomer (a) is 0.03 μm or more, an elastomer having a desired volume average particle size can be stably obtained, and if (b) is 50.00 μm or less, the heat resistance and impact resistance of the obtained cured product or molded product are good. The volume average particle size of the elastomer can be measured by using an aqueous latex containing the elastomer as a material and using a dynamic light scattering particle size distribution measuring device or the like. The method for measuring the volume average particle size of the elastomer is described in detail in the following examples.
[0065] (Ratio of elastic body)
[0066] The ratio of the elastomer in the polymer particles (A) is preferably 40 to 97% by weight, more preferably 60 to 95% by weight, and further preferably 70 to 93% by weight, based on 100% by weight of the polymer particles (A). When the ratio of the elastomer is 40% by weight or more, the obtained powder-containing resin composition can be used to provide a cured product or molded body having excellent toughness and impact resistance. When the ratio of the elastomer is 97% by weight or less, the polymer particles (A) are not easy to agglomerate (difficult to agglomerate), and therefore the obtained powder-containing resin composition will not be high in viscosity. As a result, the resin composition is easy to handle.
[0067] (Gel content of elastomer)
[0068] The elastomer may swell in a suitable solvent, but is preferably insoluble therein. The elastomer is preferably insoluble in the matrix resin (C) used.
[0069] The gel content of the elastomer is preferably 60% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and particularly preferably 95% by weight or more. When the gel content of the elastomer is within these ranges, the obtained powder-containing resin composition can be used to provide a cured product or a molded product having excellent toughness.
[0070] In this specification, the method for calculating the gel content is as follows. First, an aqueous latex containing polymer particles (A) is obtained, and then a powder of the polymer particles (A) is obtained from the aqueous latex. Here, the method for obtaining the powder of the polymer particles (A) from the aqueous latex is not particularly limited, but for example, the following method can be cited: (i) agglomerating the polymer particles (A) in the aqueous latex, (ii) dehydrating the obtained agglomerates, and (iii) further drying the agglomerates to obtain the powder of the polymer particles (A). Next, 2.0 g of the powder of the polymer particles (A) is dissolved in 50 mL of methyl ethyl ketone (MEK), and then the obtained MEK dissolved product is separated into a component soluble with respect to MEK (MEK soluble component) and a component insoluble with respect to MEK (MEK insoluble component). Specifically, the obtained MEK solution was centrifuged at 30,000 rpm for 1 hour using a centrifuge (CP60E manufactured by Hitachi Koki Co., Ltd.), thereby separating the solution into a MEK soluble component and a MEK insoluble component. Here, the centrifugation operation was performed 3 times in total. The weights of the obtained MEK soluble component and the MEK insoluble component were measured, and the gel content was calculated according to the following formula.
[0071] Gel content (%) = (weight of methyl ethyl ketone insoluble components) / {(weight of methyl ethyl ketone insoluble components) + (weight of methyl ethyl ketone soluble components)} × 100
[0072] (Deformation example of elastic body)
[0073] In one embodiment of the present invention, the "elastomer" of the polymer microparticles (A) may be composed of only a single elastomer having the same structural unit component. In this case, the "elastomer" of the polymer microparticles (A) is one selected from diene rubber, (meth)acrylate rubber, and organosilicone rubber.
[0074] In one embodiment of the present invention, the "elastomer" of the polymer particles (A) may also be composed of a plurality of elastomers having different structural unit components. In this case, the "elastomer" of the polymer particles (A) may be two or more selected from diene rubber, (meth)acrylate rubber, and organosiloxane rubber. In addition, the "elastomer" of the polymer particles (A) may also be one selected from diene rubber, (meth)acrylate rubber, and organosiloxane rubber. In other words, the "elastomer" of the polymer particles (A) may be a plurality of diene rubbers, (meth)acrylate rubbers, or organosiloxane rubbers having different structural unit components.
[0075] The case where the "elastomer" of the polymer particles (A) in one embodiment of the present invention is composed of a plurality of elastomers having different structural unit components is described. In this case, the plurality of elastomers are respectively set as elastomer 1, elastomer 2, ..., and elastomer n. Here, n is an integer greater than 2. The "elastomer" of the polymer particles (A) may also include a composite composed of elastomer 1, elastomer 2, ..., and elastomer n that are polymerized separately. The "elastomer" of the polymer particles (A) may also include an entire elastomer obtained by sequentially polymerizing elastomer 1, elastomer 2, ..., and elastomer n. Such an operation of sequentially polymerizing a plurality of elastomers (polymers) is called multi-stage polymerization. An entire elastomer obtained by polymerizing a plurality of elastomers in multiple stages is also called a multi-stage polymerized elastomer. The method for producing a multi-stage polymerized elastomer will be described in detail later.
[0076] A multi-stage polymerized elastomer consisting of elastomer 1, elastomer 2, ..., and elastomer n is described. In the multi-stage polymerized elastomer, elastomer n can cover at least a portion of elastomer n-1 or can cover the entire elastomer n-1. In the multi-stage polymerized elastomer, a portion of elastomer n may also be embedded inside elastomer n-1.
[0077] In a multi-stage polymeric elastomer, each of the multiple elastomers may also be formed into a layer structure. For example, in the case where the multi-stage polymeric elastomer is composed of elastomer 1, elastomer 2 and elastomer 3, elastomer 1 is formed as the innermost layer, and an elastomer 2 layer is formed on the outside of elastomer 1, and further, an elastomer 3 layer is formed on the outside of the elastomer 2 layer as the outermost layer of the elastomer. This form is also an aspect of the present invention. Such a multi-stage polymeric elastomer in which multiple elastomers are each formed into a layer structure is also called a multilayer elastomer. That is, in one embodiment of the present invention, the "elastomer" of the polymer microparticle (A) may include (a) a composite of multiple elastomers, (b) a multi-stage polymeric elastomer and / or (c) a multilayer elastomer.
[0078] (I-2-1-2. Branching)
[0079] In this specification, the polymer grafted to the elastomer is referred to as a graft portion. The graft portion includes a polymer having a specific structural unit, and the specific structural unit is derived from one or more monomers selected from aromatic vinyl monomers, vinyl cyanide monomers, and (meth)acrylate monomers. The graft portion can play various roles due to the above-mentioned scheme. The so-called "various roles" include, for example: (a) improving the compatibility between the matrix resin (C) and the polymer particles (A); (b) improving the dispersibility of the polymer particles (A) in the matrix resin (C); and (c) enabling the polymer particles (A) to be dispersed in the form of primary particles in the obtained powder-containing resin composition or in the cured product or molded body; etc.
[0080] Specific examples of the aromatic vinyl monomer include styrene, α-methylstyrene, p-methylstyrene, and divinylbenzene.
[0081] Specific examples of the vinyl cyanide monomer include acrylonitrile and methacrylonitrile.
[0082] Specific examples of the (meth)acrylic acid ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hydroxyethyl (meth)acrylate, and hydroxybutyl (meth)acrylate.
[0083] One or more monomers selected from the group consisting of the aromatic vinyl monomers, vinyl cyanide monomers and (meth)acrylate monomers may be used alone or in combination of two or more.
[0084] Regarding the structural units of the graft portion, the total content of the structural units derived from the aromatic vinyl monomer, the structural units derived from the vinyl cyanide monomer, and the structural units derived from the (meth)acrylate monomer is preferably 10 to 95% by weight, more preferably 30 to 92% by weight, further preferably 50 to 90% by weight, particularly preferably 60 to 87% by weight, and most preferably 70 to 85% by weight, based on 100% by weight of all the structural units of the graft portion.
[0085] The grafted portion preferably includes a structural unit derived from a monomer having a reactive group. The monomer having a reactive group is preferably a monomer having one or more reactive groups selected from epoxy, oxetane, hydroxyl, amino, imide, carboxylic acid, anhydride, cyclic ester, cyclic amide, benzoxazine and cyanate groups, more preferably a monomer having one or more reactive groups selected from epoxy, hydroxyl and carboxylic acid groups, and most preferably a monomer having an epoxy group. Through this scheme, the grafted portion of the polymer particles (A) can be chemically bonded to the matrix resin (C) in the obtained powder-containing resin composition. As a result, in the obtained powder-containing resin composition or in the cured product or molded body, the aggregation of the polymer particles (A) does not occur and the good dispersion state of the polymer particles (A) can be maintained.
[0086] Specific examples of the monomer having an epoxy group include glycidyl group-containing vinyl monomers such as glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, and allyl glycidyl ether.
[0087] Specific examples of monomers having a hydroxyl group include: (a) hydroxyl straight-chain alkyl (meth)acrylates (especially hydroxyl straight-chain C1-6 alkyl (meth)acrylates) such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; (b) hydroxy-modified caprolactone (meth)acrylate; (c) branched hydroxyalkyl (meth)acrylates such as methyl α-(hydroxymethyl)acrylate and ethyl α-(hydroxymethyl)acrylate; (d) hydroxyl-containing (meth)acrylates such as mono[(meth)acrylate] esters of polyester diols (especially saturated polyester diols) obtained from dicarboxylic acids (phthalic acid, etc.) and diols (propylene glycol, etc.); and the like.
[0088] Specific examples of the monomer having a carboxylic acid group include monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, and dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid, etc. As the monomer having a carboxylic acid group, the above monocarboxylic acids can be preferably used.
[0089] The above-mentioned monomers having a reactive group may be used alone or in combination of two or more.
[0090] Regarding the grafted portion, the content of the structural unit derived from the monomer having a reactive group is preferably 0.5 to 90% by weight, more preferably 1 to 50% by weight, further preferably 2 to 35% by weight, and particularly preferably 3 to 20% by weight in 100% by weight of the grafted portion. If the grafted portion contains 0.5% by weight or more of the structural unit derived from the monomer having a reactive group in 100% by weight of the grafted portion, the obtained powder-containing resin composition can be used to provide a cured product or molded body with sufficient impact resistance. If the grafted portion contains 90% by weight or less of the structural unit derived from the monomer having a reactive group in 100% by weight of the grafted portion, the obtained powder-containing resin composition can be used to provide a cured product or molded body with sufficient impact resistance and the resin composition has the advantage of good storage stability.
[0091] The structural unit derived from the monomer having a reactive group is preferably contained in the graft portion, and more preferably contained only in the graft portion.
[0092] The grafted portion may also contain a structural unit derived from a polyfunctional monomer. When the grafted portion contains a structural unit derived from a polyfunctional monomer, there are the following advantages, etc.: (a) the swelling of the polymer microparticles (A) in the obtained powder-containing resin composition can be prevented; (b) the viscosity of the obtained powder-containing resin composition is reduced, thereby having a tendency to improve the handleability of the resin composition; and (c) the dispersibility of the polymer microparticles (A) in the matrix resin (C) is improved.
[0093] When the graft portion does not contain a structural unit derived from a polyfunctional monomer, the obtained powder-containing resin composition can be used to provide a cured product having more excellent toughness and impact resistance than when the graft portion contains a structural unit derived from a polyfunctional monomer.
[0094] Regarding the multifunctional monomers that can be used in the polymerization of the grafting portion, the same monomers as the aforementioned multifunctional monomers can be cited. Among these multifunctional monomers, regarding the multifunctional monomers that can be preferably used for the polymerization of the grafting portion, allyl methacrylate, di[(meth)acrylate] butanediol, di[(meth)acrylate] ethylene glycol, di[(meth)acrylate] butanediol, di[(meth)acrylate] hexanediol, di[(meth)acrylate] cyclohexanedimethanol, and di[(meth)acrylate] polyglycol esters can be cited. These multifunctional monomers can be used only one, or two or more can be used in combination.
[0095] The graft portion preferably contains 1 to 20% by weight, more preferably 5 to 15% by weight, of the structural unit derived from the polyfunctional monomer based on 100% by weight of the graft portion.
[0096] In the graft portion, the above-mentioned monomers may be used alone or in combination of two or more during polymerization.
[0097] The graft portion may include structural units derived from other monomers in addition to the structural units derived from the above-mentioned monomers.
[0098] (Glass transition temperature of grafted part)
[0099] The glass transition temperature of the graft portion is preferably 190°C or lower, more preferably 160°C or lower, more preferably 140°C or lower, more preferably 120°C or lower, more preferably 80°C or lower, more preferably 70°C or lower, more preferably 60°C or lower, more preferably 50°C or lower, more preferably 40°C or lower, more preferably 30°C or lower, more preferably 20°C or lower, more preferably 10°C or lower, more preferably 0°C or lower, more preferably -20°C or lower, more preferably -40°C or lower, more preferably -45°C or lower, more preferably -50°C or lower, more preferably -55°C or lower, more preferably -60°C or lower, more preferably -65°C or lower, more preferably -70°C or lower, more preferably -75°C or lower, more preferably -80°C or lower, more preferably -85°C or lower, more preferably -90°C or lower, more preferably -95°C or lower, more preferably -100°C or lower, more preferably -105°C or lower, more preferably -110°C or lower, more preferably -115°C or lower, further preferably -120°C or lower, particularly preferably -125°C or lower.
[0100] The glass transition temperature of the graft portion is preferably 0° C. or higher, more preferably 30° C. or higher, more preferably 50° C. or higher, more preferably 70° C. or higher, further preferably 90° C. or higher, and particularly preferably 110° C. or lower.
[0101] The Tg of the graft portion can be determined by the composition of the structural unit contained in the graft portion, etc. In other words, the Tg of the resulting graft portion can be adjusted by changing the monomer composition used when producing (polymerizing) the graft portion.
[0102] The Tg of the grafted portion can be obtained by measuring the viscoelasticity of a flat plate composed of polymer particles (A). Specifically, the Tg can be measured as follows: (1) A dynamic viscoelasticity measurement device (e.g., DVA-200 manufactured by IT Instrumentation and Control Co., Ltd.) is used to measure the dynamic viscoelasticity of a flat plate composed of polymer particles (A) under tension to obtain a tanδ coordinate graph; (2) On the obtained tanδ coordinate graph, the peak temperature of tanδ is determined as the glass transition temperature. Here, if multiple peaks are obtained in the tanδ coordinate graph, the highest peak temperature is determined as the glass transition temperature of the grafted portion.
[0103] (Grafting rate of grafted part)
[0104] In one embodiment of the present invention, the polymer microparticles (A) may also include the following polymers: a polymer having the same structure as the grafted portion but not graft-bonded to the elastomer. In this specification, a polymer having the same structure as the grafted portion but not graft-bonded to the elastomer is also referred to as a non-grafted polymer. The non-grafted polymer is also regarded as a part of the polymer microparticles (A) involved in one embodiment of the present invention. The non-grafted polymer can also be said to be a polymer that is not graft-bonded to the elastomer among the polymers obtained by polymerization of the grafted portion.
[0105] In this specification, the ratio of the polymer grafted to the elastomer, i.e., the graft portion, in the polymer obtained by polymerization of the graft portion is called the graft ratio. The graft ratio can also be expressed as "(graft portion weight) / {(graft portion weight)+(non-grafted polymer weight)}×100".
[0106] The grafting rate of the grafted portion is preferably 70% or more, more preferably 80% or more, and still more preferably 90% or more. A grafting rate of 70% or more has the advantage that the viscosity of the obtained powder-containing resin composition will not be too high.
[0107] In this specification, the method for calculating the grafting rate is as follows. First, an aqueous latex containing polymer particles (A) is obtained, and then a powder of the polymer particles (A) is obtained from the aqueous latex. Here, regarding the method for obtaining the powder of the polymer particles (A) from the aqueous latex, the following method can be specifically cited: (i) coagulating the polymer particles (A) in the aqueous latex, (ii) dehydrating the obtained coagulation, and (iii) further drying the coagulation to obtain the powder of the polymer particles (A). Next, 2 g of the powder of the polymer particles (A) is dissolved in 50 mL of methyl ethyl ketone (MEK), and then the obtained MEK dissolved product is separated into a component soluble with respect to MEK (MEK soluble component) and a component insoluble with respect to MEK (MEK insoluble component). Specifically, a centrifuge (CP60E manufactured by Hitachi Koki Co., Ltd.) was used to centrifuge the obtained MEK dissolved substance for 1 hour at a rotation speed of 30,000 rpm, thereby separating the dissolved substance into a MEK soluble component and a MEK insoluble component. Here, the centrifugal operation was implemented 3 times in total. Then, 20 ml of the concentrated MEK soluble component was mixed with 200 ml of methanol, and an aqueous solution of calcium chloride in which 0.01 g of calcium chloride was dissolved in water was added to the obtained mixture, and the obtained mixture was stirred for 1 hour. Afterwards, the obtained mixture was separated into a component soluble with respect to methanol and a component insoluble with respect to methanol, and the weight of the component insoluble with respect to methanol was determined as the amount of free polymer (FP).
[0108] The grafting rate was calculated according to the following formula.
[0109] Grafting rate (%) = 100 - [(FP amount) / {(FP amount) + (weight of MEK insoluble component)}] / (weight of grafted polymer) × 10000
[0110] Here, the weight of the polymer other than the grafted portion refers to the input amount of the monomers constituting the polymer other than the grafted portion. The polymer other than the grafted portion is, for example, an elastomer. In addition, if the polymer particles (A) include the surface cross-linked polymer described later, the polymer other than the grafted portion includes both the elastomer and the surface cross-linked polymer. The weight of the grafted portion polymer refers to the input amount of the monomers constituting the grafted portion polymer. In addition, in the calculation of the grafting rate, the method of coagulating the polymer particles (A) is not particularly limited, and a method using a solvent, a method using a coagulant, a method of spraying an aqueous latex, etc. can be adopted.
[0111] (Variation of the grafting portion)
[0112] In one embodiment of the present invention, the grafting part may be composed of a single grafting part having structural units of the same composition. In one embodiment of the present invention, the grafting part may be composed of a plurality of grafting parts having structural units of different compositions.
[0113] The case where the grafting part is composed of multiple grafting parts in one embodiment of the present invention is described. In this case, the multiple grafting parts are respectively set as grafting part 1, grafting part 2, ..., grafting part n (n is an integer greater than 2). The grafting part may also include a complex composed of grafting part 1, grafting part 2, ..., grafting part n polymerized separately. The grafting part may also include a whole polymer obtained by polymerizing grafting part 1, grafting part 2, ..., grafting part n in multiple stages. The polymer obtained by polymerizing multiple grafting parts in multiple stages is also called a multi-stage polymerized grafting part. The method for manufacturing a multi-stage polymerized grafting part will be described in detail later.
[0114] When the grafting part is composed of a plurality of grafting parts, not all of the plurality of grafting parts may be graft-bonded to the elastomer. That is, at least a part of at least one kind of grafting part may be graft-bonded to the elastomer, and other kinds (other plurality of kinds) of grafting parts may be graft-bonded to the grafting part graft-bonded to the elastomer. In addition, when the grafting part is composed of a plurality of grafting parts, it may have a plurality of polymers (a plurality of non-grafted polymers) having the same structure as the plurality of grafting parts but not graft-bonded to the elastomer.
[0115] A multi-stage polymer graft portion consisting of a graft portion 1, a graft portion 2, ..., a graft portion n is described. In the multi-stage polymer graft portion, the graft portion n can cover at least a portion of the graft portion n-1 or can cover the entire graft portion n-1. In the multi-stage polymer graft portion, a portion of the graft portion n may be embedded inside the graft portion n-1.
[0116] In a multi-stage polymer grafting section, each of the multiple grafting sections can also be formed into a layer structure. For example, in the case where the multi-stage polymer grafting section is composed of a grafting section 1, a grafting section 2 and a grafting section 3, the grafting section 1 is formed as the innermost layer of the grafting section, and the grafting section 2 layer is formed on the outside of the grafting section 1, and the grafting section 3 layer is formed on the outside of the grafting section 2 as the outermost layer. This form is also an aspect of the present invention. Such a multi-stage polymer grafting section in which each of the multiple grafting sections is formed into a layer structure is also called a multi-layer grafting section. That is, in one embodiment of the present invention, the grafting section may include (a) a mixture of multiple grafting sections, (b) a multi-stage polymer grafting section and / or (c) a multi-layer grafting section.
[0117] When the elastomer and the grafting part are polymerized sequentially in the production of the polymer microparticles (A), at least a portion of the grafting part can cover at least a portion of the elastomer in the obtained polymer microparticles (A). The so-called sequential polymerization of the elastomer and the grafting part can also be said to be multi-stage polymerization of the elastomer and the grafting part. The polymer microparticles (A) obtained by multi-stage polymerization of the elastomer and the grafting part are also called multi-stage polymers.
[0118] When the polymer microparticles (A) are multistage polymers, the grafts may cover at least a portion of the elastomer or the entire elastomer. When the polymer microparticles (A) are multistage polymers, a portion of the grafts may be embedded inside the elastomer.
[0119] In the case where the polymer particles (A) are multi-stage polymers, the elastomer and the grafted portion may also be formed into a layer structure. For example, the elastomer is formed as the innermost layer (also called the core layer) and the outer side of the elastomer is formed with a grafted portion layer as the outermost layer (also called the shell layer). This form is also an aspect of the present invention. This structure in which the elastomer is the core layer and the grafted portion is the shell layer is also called a core-shell structure. The polymer particles (A) formed into a layer structure (core-shell structure) by the elastomer and the grafted portion are also called multilayer polymers or core-shell polymers. That is, in one embodiment of the present invention, the polymer particles (A) may be multi-stage polymers and / or multilayer polymers or core-shell polymers. However, as long as the grafted portion is graft-bonded to the elastomer, the polymer particles (A) are not limited to the aforementioned scheme.
[0120] At least a part of the graft part preferably covers at least a part of the elastomer. In other words, at least a part of the graft part preferably exists on the outermost side of the polymer microparticle (A).
[0121] (I-2-1-3. Surface cross-linked polymer)
[0122] The rubber-containing graft copolymer preferably has a surface crosslinked polymer in addition to an elastomer and a graft portion graft-bonded to the elastomer. In other words, the polymer microparticle (A) preferably has a surface crosslinked polymer in addition to an elastomer and a graft portion graft-bonded to the elastomer. Hereinafter, an embodiment of the present invention is described by taking the case where the polymer microparticle (A) (e.g., the rubber-containing graft copolymer) further has a surface crosslinked polymer as an example. This case has the following advantages: (a) the anti-blocking property can be improved in the manufacture of the polymer microparticle (A), and (b) the dispersibility of the polymer microparticle (A) in the matrix resin (C) is better from the perspective of the obtained powder-containing resin composition. The reasons for these advantages are not particularly limited, but are presumed to be as follows: the surface crosslinked polymer covers at least a portion of the elastomer, thereby reducing the exposure of the elastomer portion of the polymer microparticle (A), resulting in that the elastomers are not easily adhered to each other, so the dispersibility of the polymer microparticle (A) is improved.
[0123] When the polymer particles (A) further have a surface crosslinked polymer, the following effects can be exerted: (a) reducing the viscosity of the obtained powder-containing resin composition, (b) increasing the crosslinking density of the elastomer, and (c) improving the grafting efficiency of the grafted portion. The crosslinking density of the elastomer refers to the number of crosslinked structures in the entire elastomer.
[0124] The surface cross-linked polymer is composed of 30 to 100% by weight of a structural unit derived from a polyfunctional monomer and 0 to 70% by weight of a structural unit derived from other vinyl monomers, wherein the total of these structural units is 100% by weight.
[0125] Regarding the multifunctional monomers that can be used in the polymerization of the surface cross-linked polymer, the same monomers as the aforementioned multifunctional monomers can be cited. Among these multifunctional monomers, regarding the multifunctional monomers that can be preferably used for the polymerization of the surface cross-linked polymer, allyl methacrylate, di[(meth)acrylate]ethylene glycol, di[(meth)acrylate]butylene glycol ester (for example, di[(meth)acrylate]1,3-butylene glycol ester, etc.), di[(meth)acrylate]butylene glycol ester, di[(meth)acrylate]hexanediol ester, di[(meth)acrylate]cyclohexanedimethanol ester, and di[(meth)acrylate]polyethylene glycol esters can be cited. These multifunctional monomers can be used only one, or two or more can be used in combination.
[0126] The polymer particles (A) may also include: a surface crosslinked polymer obtained by polymerization independently of the polymerization of the rubber-containing graft copolymer, or a surface crosslinked polymer obtained by polymerization together with the rubber-containing graft copolymer. The polymer particles (A) may also be a multi-stage polymer obtained by sequentially polymerizing the elastomer, the surface crosslinked polymer, and the grafted portion in multiple stages. Whichever of these schemes is adopted, the surface crosslinked polymer can cover at least a portion of the elastomer.
[0127] The surface cross-linked polymer can be considered as a part of the elastomer. In other words, the surface cross-linked polymer can also be considered as a part of the rubber-containing graft copolymer, and therefore can also be called the surface cross-linked polymer portion. In the case where the polymer particles (A) contain a surface cross-linked polymer, the grafted portion can also be (a) graft-bonded to an elastomer other than the surface cross-linked polymer, (b) graft-bonded to the surface cross-linked polymer, or (c) graft-bonded to both the elastomer other than the surface cross-linked polymer and the surface cross-linked polymer. If the polymer particles (A) contain a surface cross-linked polymer, the volume average particle size of the elastomer mentioned above refers to the volume average particle size of the elastomer containing the surface cross-linked polymer.
[0128] The following describes a case where the polymer microparticle (A) is a multi-stage polymer obtained by sequentially polymerizing an elastomer, a surface cross-linked polymer, and a grafted portion in multiple stages (case D). In case D, the surface cross-linked polymer can cover a portion of the elastomer or can cover the entire elastomer. In case D, a portion of the surface cross-linked polymer may also be embedded inside the elastomer. In case D, the grafted portion can cover a portion of the surface cross-linked polymer or can cover the entire surface cross-linked polymer. In case D, a portion of the grafted portion may also be embedded inside the surface cross-linked polymer. In case D, the elastomer, the surface cross-linked polymer, and the grafted portion may also have a layer structure. For example, a form in which the elastomer is the innermost layer (core layer) and there is a surface cross-linked polymer layer as an intermediate layer on the outside of the elastomer and there is a grafted portion layer as the outermost layer (shell layer) on the outside of the surface cross-linked polymer is also an aspect of the present invention.
[0129] (I-2-1-4. Physical properties of polymer microparticles (A))
[0130] The physical properties of the polymer fine particles (A) are described below.
[0131] (Volume Average Particle Size (Mv) of Polymer Microparticles (A))
[0132] From the viewpoint of obtaining a highly stable resin composition having a desired viscosity, the volume average particle size (Mv) of the polymer microparticles (A) is preferably 0.03 μm to 50.00 μm, more preferably 0.05 μm to 10.00 μm, more preferably 0.08 μm to 2.00 μm, further preferably 0.10 μm to 1.00 μm, further preferably 0.10 μm to 0.80 μm, and particularly preferably 0.10 μm to 0.50 μm. When the volume average particle size (Mv) of the polymer microparticles (A) is within these ranges, there is also an advantage that the dispersibility of the polymer microparticles (A) in the matrix resin (C) is good. Here, in this specification, unless otherwise specified, "the volume average particle size (Mv) of the polymer microparticles (A)" refers to the volume average particle size of the primary particles of the polymer microparticles (A). The volume average particle size of the polymer microparticles (A) can be measured as follows: an aqueous latex containing the polymer microparticles (A) is used as a material and measured using a dynamic light scattering particle size distribution measuring device. The volume average particle size of the polymer microparticles (A) will be described in detail in the following examples. The volume average particle size of the polymer microparticles (b) can also be measured as follows: a cured product or a molded body of the resin composition is cut, the cut surface is photographed using an electron microscope, etc., and the obtained photographed data (photographed image) is used for measurement.
[0133] In the matrix resin (C), the distribution of the volume average particle size of the polymer particles (A) relative to the number preferably has a half-value width of not less than 0.5 times and not more than 1 times the volume average particle size, thereby obtaining a resin composition with low viscosity and easy handling.
[0134] (I-2-1-5. Method for producing polymer microparticles (A))
[0135] The polymer fine particles (A) can be produced by polymerizing an elastomer and then graft-polymerizing a polymer constituting a graft portion onto the elastomer in the presence of the elastomer.
[0136] Polymer particles (A) can be manufactured by known methods, such as emulsion polymerization, suspension polymerization, microsuspension polymerization and the like. Specifically, the polymerization of the elastomer in the polymer particles (A), the polymerization of the grafted portion (graft polymerization), and the polymerization of the surface cross-linked polymer can be implemented by known methods, such as emulsion polymerization, suspension polymerization, microsuspension polymerization and the like. Among these methods, it is particularly preferred to use emulsion polymerization as the manufacturing method of polymer particles (A). By emulsion polymerization, the following advantages can be exerted: (a) the component design of polymer particles (A) is easier, (b) the industrial production of polymer particles (A) is easier, and (c) the aqueous latex of polymer particles (A) that can be well applied to the manufacture of the present resin composition described later can be easily obtained. Below, the manufacturing method of the elastomer, grafted portion and surface cross-linked polymer as an optional item that can be contained in the polymer particles (A) is described.
[0137] (Method for producing elastomer)
[0138] It is assumed that the elastomer contains one or more rubbers selected from diene rubber and (meth)acrylate rubber. In this case, the elastomer can be produced by methods such as emulsion polymerization, suspension polymerization, microsuspension polymerization, etc. As its production method, for example, the method described in International Publication No. WO2005 / 028546 can be used.
[0139] The elastomer is assumed to include an organosiloxane rubber. In this case, the elastomer can be produced by methods such as emulsion polymerization, suspension polymerization, and microsuspension polymerization. As a production method thereof, for example, the method described in International Publication No. WO2006 / 070664 can be used.
[0140] The case where the "elastomer" of the polymer microparticles (A) is composed of a plurality of elastomers (e.g., elastomer 1, elastomer 2, ..., elastomer n) will be described. In this case, elastomer 1, elastomer 2, ..., elastomer n may be polymerized separately by the above-mentioned method, and then mixed and composited to produce a composite composed of a plurality of elastomers. Alternatively, elastomer 1, elastomer 2, ..., elastomer n may be polymerized in multiple stages in sequence to produce a whole elastomer composed of a plurality of elastomers.
[0141] The multi-stage polymerization of the elastomer is specifically described. For example, the multi-stage polymerization elastomer can be obtained by sequentially performing the following steps (1) to (4): (1) polymerizing elastomer 1 to obtain elastomer 1; (2) then, polymerizing elastomer 2 in the presence of elastomer 1 to obtain elastomer 1+2 of the second stage; (3) then, polymerizing elastomer 3 in the presence of elastomer 1+2 to obtain elastomer 1+2+3 of the third stage; (4) the same process is repeated thereafter, and finally, in the presence of elastomer 1+2+… + ( n-1) to obtain a multi-stage polymerized elastomer 1+2+...+n.
[0142] (Method for producing grafted portion)
[0143] For example, the monomers for forming the grafting portion can be polymerized by known free radical polymerization to form the grafting portion. If a polymer particle precursor containing (a) an elastomer or (b) an elastomer and a surface cross-linked polymer is obtained in the form of an aqueous latex, the polymerization of the grafting portion is preferably carried out by emulsion polymerization. The grafting portion can be manufactured according to the method described in International Publication WO2005 / 028546, for example.
[0144] The method for producing a grafted portion when the grafted portion is composed of a plurality of grafted portions (e.g., grafted portion 1, grafted portion 2, ..., grafted portion n) is described. In this case, the grafted portion 1, grafted portion 2, ..., grafted portion n may be polymerized separately according to the above method, and then mixed and composited to produce a grafted portion (composite) composed of a plurality of grafted portions. Alternatively, the grafted portion 1, grafted portion 2, ..., grafted portion n may be polymerized in multiple stages in sequence to produce a whole grafted portion composed of a plurality of grafted portions.
[0145] The multi-stage polymerization of the grafting part is specifically described. For example, the multi-stage polymerization grafting part can be obtained by sequentially performing the following steps (1) to (4): (1) performing polymerization of grafting part 1 to obtain grafting part 1; (2) then, performing polymerization of grafting part 2 in the presence of grafting part 1 to obtain grafting part 1+2 of the second stage; (3) then, performing polymerization of grafting part 3 in the presence of grafting part 1+2 to obtain grafting part 1+2+3 of the third stage; (4) the same process is repeated thereafter, and finally grafting part 1+2+...+ (n-1) The grafting part n is polymerized in the presence of to obtain a multi-stage polymerized grafting part 1+2+...+n.
[0146] If the grafting part is composed of multiple grafting parts, the grafting parts having multiple grafting parts can be polymerized and then grafted onto the elastomer to produce polymer microparticles (A). Alternatively, multiple polymers constituting the grafting part can be grafted onto the elastomer in multiple stages in sequence in the presence of the elastomer to produce polymer microparticles (A).
[0147] (Method for producing surface cross-linked polymer)
[0148] The surface cross-linked polymer can be formed by polymerizing monomers for forming the surface cross-linked polymer by a known free radical polymerization method. If the elastomer is obtained in the form of an aqueous latex, the surface cross-linked polymer is preferably polymerized by an emulsion polymerization method.
[0149] When emulsion polymerization is used as a method for producing the polymer fine particles (A), a known emulsifier (dispersant) can be used for the production of the polymer fine particles (A).
[0150] As emulsifiers, for example, anionic emulsifiers, nonionic emulsifiers, polyvinyl alcohol, alkyl-substituted cellulose, polyvinyl pyrrolidone, polyacrylic acid derivatives, etc. can be mentioned. As anionic emulsifiers, sulfur-based emulsifiers, phosphorus-based emulsifiers, sarcosine-based emulsifiers, carboxylic acid-based emulsifiers, etc. can be mentioned. As sulfur-based emulsifiers, sodium dodecylbenzene sulfonate (SDBS for short) can be mentioned. As phosphorus-based emulsifiers, sodium polyoxyethylene lauryl ether phosphate can be mentioned.
[0151] If the emulsion polymerization method is used as the method for producing the polymer microparticles (A), a thermal decomposition type initiator can be used in the production of the polymer microparticles (A). Examples of the thermal decomposition type initiator include: (a) 2,2'-azobisisobutyronitrile; (b) peroxides such as organic peroxides and inorganic peroxides; and various known initiators. Examples of the organic peroxide include tert-butyl isopropyl peroxycarbonate, p-menthane hydroperoxide, cumene hydroperoxide, dicumene peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, tert-hexyl peroxide, and the like. Examples of the inorganic peroxide include hydrogen peroxide, potassium persulfate, ammonium persulfate, and the like.
[0152] A redox initiator can also be used in the production of polymer microparticles (A). The redox initiator is an initiator containing the following components: (a) a peroxide such as an organic peroxide or an inorganic peroxide; and (b) a transition metal salt such as iron (II) sulfate, sodium formaldehyde sulfoxylate, glucose, and other reducing agents. If necessary, a chelating agent such as disodium ethylenediaminetetraacetate, or a phosphorus-containing compound such as sodium pyrophosphate, etc. can also be used in combination.
[0153] If a redox initiator is used, polymerization can be carried out at a relatively low temperature at which the peroxide does not undergo substantial thermal decomposition, thereby enabling the polymerization temperature to be set over a wide range. Therefore, it is preferred to use a redox initiator. Among the redox initiators, a redox initiator obtained by using organic peroxides such as cumene hydroperoxide, dicumene peroxide, p-menthane hydroperoxide, and tert-butyl hydroperoxide as peroxide is more preferred. The amount of the initiator used, and the amount of the reducing agent, transition metal salt, and chelating agent used when a redox initiator is used, can be used within a known range.
[0154] If a multifunctional monomer is used for polymerization of an elastomer, a grafted portion or a surface crosslinked polymer in order to introduce a crosslinked structure into the elastomer, a grafted portion or a surface crosslinked polymer, a known chain transfer agent can be used in a known amount range. By using a chain transfer agent, the molecular weight and / or the degree of crosslinking of the obtained elastomer, grafted portion or surface crosslinked polymer can be easily adjusted.
[0155] In the production of polymer microparticles (A), not only the above-mentioned components but also a surfactant can be used. The type and amount of the surfactant used can be adopted within a known range.
[0156] In the production of the polymer microparticles (A), conditions within known numerical ranges can be appropriately used as the polymerization temperature, pressure, deoxygenation and other conditions during polymerization.
[0157] (I-2-2. Resin (B))
[0158] By not only providing the first powder or particle with a specific number of pores having a specific average pore diameter but also providing the first powder or particle with a resin (B), a surprising advantage of excellent dispersibility of the polymer particles (A) in the matrix resin (C) can be achieved.
[0159] The resin (B) may be, for example, a thermosetting resin, a thermoplastic resin, or any combination of a thermosetting resin and a thermoplastic resin.
[0160] (I-2-2-1. Thermosetting resin)
[0161] The thermosetting resin in the resin (B) is not particularly limited, but preferably includes at least one of the following: a resin containing a polymer formed by polymerizing an ethylenically unsaturated monomer, an epoxy resin, a phenolic resin, a polyol resin, and an amino-formaldehyde resin. The thermosetting resin in the resin (B) may also include a resin containing a polymer formed by polymerizing an aromatic polyester raw material. As the resin (B), only one thermosetting resin may be used, or two or more thermosetting resins may be used in combination.
[0162] (Ethylenically unsaturated monomer)
[0163] The ethylenically unsaturated monomer is not particularly limited as long as it has at least one ethylenically unsaturated bond in its molecule.
[0164] Examples of the ethylenically unsaturated monomer include acrylic acid, α-alkyl acrylic acid, α-alkyl acrylic acid ester, β-alkyl acrylic acid, β-alkyl acrylic acid ester, methacrylic acid, acrylic acid ester, methacrylic acid ester, vinyl acetate, vinyl ester, unsaturated ester, polyunsaturated carboxylic acid, polyunsaturated ester, maleic acid, maleic acid ester, maleic anhydride, and acetoxystyrene, etc. These may be used alone or in combination of two or more.
[0165] (Epoxy resin)
[0166] The epoxy resin is not particularly limited as long as it has at least one epoxy group in its molecule.
[0167] Specific examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD type epoxy resins, bisphenol S type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, novolac type epoxy resins, glycidyl ether type epoxy resins of bisphenol A propylene oxide adducts, hydrogenated bisphenol A (or F) type epoxy resins, fluorinated epoxy resins, rubber-modified epoxy resins containing polybutadiene or NBR, flame-retardant epoxy resins such as glycidyl ether of tetrabromobisphenol A, p-oxybenzoic acid glycidyl ether ester type epoxy resins, meta-aminophenol type epoxy resins, diaminodiphenylmethane type epoxy resins, urethane-modified epoxy resins having urethane bonds, various alicyclic epoxy resins, glycidyl ethers of polyols, hydantoin type epoxy resins, epoxides of unsaturated polymers such as petroleum resins, and amino group-containing glycidyl ether resins. As the polyol, N, N-diglycidyl aniline, N, N-diglycidyl-o-toluidine, triglycidyl isocyanurate, polyalkylene glycol diglycidyl ether, and glycerol can be cited. As the epoxy resin, an epoxy compound obtained by addition reaction of the epoxy resin with bisphenol A (or F) or polyacids can also be cited. The epoxy resin is not limited to these, and generally used epoxy resins can be used. These epoxy resins can be used alone or in combination of two or more.
[0168] Among the above-mentioned epoxy resins, epoxy resins having at least two epoxy groups in one molecule are preferred because they have high reactivity when the resin composition is cured and a three-dimensional network is easily formed in the obtained cured product. In addition, regarding epoxy resins having at least two epoxy groups in one molecule, epoxy resins having bisphenol epoxy resin as a main component are preferably used from the viewpoint of superior economic efficiency and easy availability.
[0169] (Phenolic resin)
[0170] Phenolic resin is a compound obtained by reacting phenols with aldehydes, and is not particularly limited. As phenols, there are no particular limitations, but for example, phenol, o-cresol, m-cresol, p-cresol, xylenol, p-tert-butylphenol, p-octylphenol, p-phenylphenol, bisphenol A, bisphenol F, resorcinol, etc. can be mentioned. As particularly preferred phenols, phenol and cresol can be mentioned.
[0171] The aldehydes are not particularly limited, but examples thereof include formaldehyde, acetaldehyde, butyraldehyde, acrolein, and mixtures thereof. As the aldehydes, substances that are sources of these aldehydes or solutions of these aldehydes may be used. As the aldehydes, formaldehyde is preferred from the viewpoint of ease of handling when reacting phenols with aldehydes.
[0172] The molar ratio (F / P) of phenols (P) and aldehydes (F) when reacting phenols with aldehydes (hereinafter, also referred to as the reaction molar ratio) is not particularly limited. If an acid catalyst is used in the reaction, the reaction molar ratio (F / P) is preferably 0.4 to 1.0, and more preferably 0.5 to 0.8. If an alkali catalyst is used in the reaction, the reaction molar ratio (F / P) is preferably 0.4 to 4.0, and more preferably 0.8 to 2.5. When the reaction molar ratio is above the lower limit, the yield will not be too low, and the molecular weight of the obtained phenolic resin will not be too small. On the other hand, when the reaction molar ratio is below the upper limit, the molecular weight of the phenolic resin will not be too large and the softening point will not be too high, so sufficient fluidity can be obtained when heated. In addition, when the reaction molar ratio is below the upper limit, the molecular weight is easier to control, and gelation or partial gelation will not occur due to the reaction conditions.
[0173] (Polyol resin)
[0174] The polyol resin is a compound having two or more active hydrogen atoms at the terminal, and is a polyol having two or more functionalities and a molecular weight of about 50 to 20000. Examples of the polyol resin include aliphatic alcohols, aromatic alcohols, polyether polyols, polyester polyols, polyolefin polyols, and acrylic polyols.
[0175] The aliphatic alcohol may be any of a diol or a trivalent or higher alcohol (a triol, a tetravalent alcohol, etc.). Examples of the diol include: (a) ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, etc. (particularly alkylene glycols having a carbon number of about 1 to 6); and (b) dehydrated condensates of two or more molecules (e.g., about 2 to 6 molecules) of the alkylene glycol compounds (e.g., diethylene glycol, dipropylene glycol, tripropylene glycol, etc.); etc. Examples of the triol include glycerol, trimethylolpropane, trimethylolethane, 1,2,6-hexanetriol, etc. (particularly trihydric alcohols having a carbon number of about 3 to 10). Examples of the tetrahydric alcohol include pentaerythritol, diglycerol, etc. In addition, sugars such as monosaccharides, oligosaccharides, and polysaccharides can be mentioned.
[0176] Examples of the aromatic alcohol include bisphenols such as bisphenol A and bisphenol F; biphenyls such as dihydroxybiphenyl; polyphenols such as hydroquinone and phenol formaldehyde condensate; and naphthalene diol.
[0177] Examples of polyether polyols include: (a) random copolymers or block copolymers obtained by ring-opening polymerization of ethylene oxide, propylene oxide, butylene oxide, styrene oxide, etc. in the presence of one or more initiators containing active hydrogen; and (b) mixtures of these copolymers. Initiators containing active hydrogen used for the ring-opening polymerization of polyether polyols include glycols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, and bisphenol A; triols such as trimethylolethane, trimethylolpropane, and glycerol; sugars such as monosaccharides, oligosaccharides, and polysaccharides; sorbitol; amines such as ammonia, ethylenediamine, urea, monomethyldiethanolamine, and monoethyldiethanolamine; and the like.
[0178] As polyester polyols, for example, there can be mentioned: polymers obtained by polycondensing a polyacid and / or an anhydride of a polyacid with a polyol in the presence of an esterification catalyst at a temperature range of 150 to 270°C. As the polyacid, there can be mentioned maleic acid, fumaric acid, adipic acid, sebacic acid, phthalic acid, dodecanedioic acid, isophthalic acid, azelaic acid, etc. As the polyols, there can be mentioned ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, neopentyl glycol, 3-methyl-1,5-pentanediol, etc. Moreover, as polyester polyols, there can be mentioned: (a) ring-opening polymers such as ε-caprolactone and valerolactone; and (b) active hydrogen compounds having two or more active hydrogens such as polycarbonate diol and castor oil.
[0179] Examples of the polyolefin polyol include polybutadiene polyol, polyisoprene polyol, and hydrogenated products thereof.
[0180] Examples of acrylic polyols include copolymers of hydroxyl-containing monomers (a) such as hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, and vinylphenol, and general-purpose monomers (b) such as n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate; and mixtures of these copolymers.
[0181] Among these polyol resins, polyether polyols are preferred because the obtained powder-containing resin composition has low viscosity and excellent processability, and the resin composition can be used to provide a cured product with an excellent balance between hardness and toughness. In addition, polyester polyols are preferred because the obtained powder-containing resin composition can be used to provide a cured product with excellent adhesion.
[0182] (Amino-formaldehyde resin)
[0183] The amino-formaldehyde resin is not particularly limited as long as it is a compound obtained by reacting an amino compound with an aldehyde under a basic catalyst. Examples of the amino compound include melamine; 6-substituted guanamines such as guanamine, acetylguanamine, and benzoguanamine; amine-substituted triazine compounds such as CTUguanamine (i.e., 3,9-bis[2-(3,5-diamino-2,4,6-triazaphenyl)ethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane) and CMTUguanamine (i.e., 3,9-bis[(3,5-diamino-2,4,6-triazaphenyl)methyl]-2,4,8,10-tetraoxaspiro[5,5]undecane); and ureas such as urea, thiourea, and ethyleneurea. In addition, as the amino compound, the following may be used: (a) substituted melamine compounds in which the hydrogen on the amino group of melamine is substituted by an alkyl group, an alkenyl group, and / or a phenyl group (described in the specification of U.S. Patent No. 5998573 (the same family Japanese publication is Japanese Unexamined Patent Publication No. 9-143238)); and (b) substituted melamine compounds in which the hydrogen on the amino group of melamine is substituted by a hydroxyalkyl group, a hydroxyalkyloxyalkyl group, and / or an aminoalkyl group (described in the specification of U.S. Patent No. 5322915 (the same family Japanese publication is Japanese Unexamined Patent Publication No. 5-202157)); etc. As the amino compound, from the viewpoint that industrial production has been achieved and it is inexpensive, polyfunctional amino compounds such as melamine, guanamine, acetylguanamine and benzoguanamine are preferred among the above-mentioned compounds, and melamine is particularly preferred. The amino compound may be used alone or in combination of two or more. In addition to these amino compounds, (a) phenols such as phenol, cresol, alkylphenol, resorcinol, hydroquinone, pyrogallol, etc.; (b) aniline; etc. may be additionally used.
[0184] Examples of the aldehydes include formaldehyde, p-formaldehyde, acetaldehyde, benzaldehyde, and furfural. As the aldehydes, formaldehyde and p-formaldehyde are preferred because they are inexpensive and have good reactivity with the amino compounds mentioned above. In the production of the amino-formaldehyde resin, it is preferred to use an aldehyde having 1.1 to 6.0 moles, particularly 1.2 to 4.0 moles of effective aldehyde groups per mole of the amino compound.
[0185] (Aromatic polyester raw materials)
[0186] Examples of the aromatic polyester raw material include radical polymerizable monomers such as aromatic vinyl compounds, (meth)acrylic acid derivatives, vinyl cyanide compounds, and maleimide compounds; dimethyl terephthalate, and alkylene glycols; etc. In the present specification, (meth)acrylic acid refers to acrylic acid and / or methacrylic acid.
[0187] (I-2-2-2. Thermoplastic resin)
[0188] Examples of the thermoplastic resin in the resin (B) include acrylic polymers, vinyl copolymers, polycarbonates, polyamides, polyesters, polyphenylene ethers, polyurethanes, and polyvinyl acetates, etc. These may be used alone or in combination of two or more.
[0189] Acrylic polymers are polymers having a structural unit composed of an acrylic ester monomer as a main component. The carbon number of the ester part of the acrylic ester monomer is preferably 1 to 20. In addition, examples of acrylic polymers include: (a) homopolymers of acrylic ester monomers; (b) copolymers composed of acrylic ester monomers and monomers such as unsaturated fatty acids, acrylamide monomers, maleimide monomers, vinyl acetate, or vinyl copolymers (hereinafter also referred to as acrylic copolymers); etc.
[0190] Examples of the acrylic acid ester monomer include methyl acrylate (MA), ethyl acrylate (EA), 2-ethylhexyl acrylate (2EHA), acrylic acid (AA), methacrylic acid (MAA), 2-hydroxyethyl acrylate (2HEA), 2-hydroxyethyl methacrylate (2HEMA), butyl acrylate (BA), methyl methacrylate (MMA), ethyl methacrylate (EMA), n-butyl methacrylate (nBMA), isobutyl methacrylate (iBMA), propyl acrylate, isopropyl acrylate, isobutyl acrylate, tert-butyl acrylate, neopentyl acrylate, isodecyl acrylate, lauryl acrylate, tridecyl acrylate, stearyl acrylate, cyclohexyl acrylate, isobornyl acrylate, trispirodecyl acrylate, hydroxyethyl acrylate, hydroxybutyl acrylate, hydroxypropyl acrylate, hydroxyethyl acrylate, 2-methoxyethyl acrylate, dimethylaminoethyl acrylate, chloroethyl acrylate, trifluoroethyl acrylate, and tetrahydrofurfuryl acrylate. These monomers may be used alone or in combination of two or more.
[0191] In the acrylic copolymer, the ratio between (a) the structural unit derived from an acrylate monomer (structural unit (a)) and (b) the structural unit derived from a monomer such as an unsaturated fatty acid, an acrylamide monomer, a maleimide monomer, vinyl acetate, or a vinyl copolymer (structural unit (b)) is preferably 50 to 100% by weight of the structural unit (a) and 0 to 50% by weight of the structural unit (b).
[0192] The acrylic polymer preferably contains 50% by weight or more, more preferably 60% by weight or more, further preferably 70% by weight or more, particularly preferably 80% by weight or more, and most preferably 90% by weight or more of the structural unit derived from butyl acrylate (BA).
[0193] The vinyl copolymer is obtained by copolymerizing a vinyl monomer mixture containing one or more monomers selected from aromatic vinyl monomers, cyanide vinyl monomers and unsaturated carboxylic acid alkyl ester monomers. The vinyl monomer mixture may further contain other monomers (hereinafter, also referred to as monomer C) that can copolymerize with the aforementioned monomers.
[0194] As the aromatic vinyl monomer, for example, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, vinyltoluene, etc. can be cited. Only one of these vinyl monomers can be used, or two or more can be used in combination. From the viewpoint of being easy to increase the refractive index, aromatic vinyl monomers are preferred among these, and styrene is more preferred.
[0195] The unsaturated carboxylic acid alkyl ester monomer is not particularly limited. For example, an ester composed of an alcohol having 1 to 6 carbon atoms and acrylic acid or methacrylic acid is preferred. The ester composed of an alcohol having 1 to 6 carbon atoms and acrylic acid or methacrylic acid may further have a substituent such as a hydroxyl group or a halogen group.
[0196] Examples of the ester composed of an alcohol having 1 to 6 carbon atoms and acrylic acid or methacrylic acid include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, chloromethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, and 2,3,4,5-tetrahydroxypentyl (meth)acrylate. These may be used alone or in combination of two or more.
[0197] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, ethacrylonitrile, etc. These may be used alone or in combination of two or more.
[0198] Monomer C is not particularly limited as long as it is a vinyl monomer other than the aromatic vinyl monomer, unsaturated carboxylic acid alkyl ester monomer, and cyanide vinyl monomer and does not impair the effect of the present invention. As monomer C, specifically unsaturated fatty acids, acrylamide monomers, maleimide monomers, vinyl acetate, acrylate monomers, etc. can be cited. Only one of them can be used, or two or more of them can be used in combination.
[0199] The unsaturated fatty acid may be selected from, for example, itaconic acid, maleic acid, fumaric acid, crotonic acid, acrylic acid, methacrylic acid, and the like.
[0200] The acrylamide monomer may be selected from, for example, acrylamide, methacrylamide, N-methylacrylamide, and the like.
[0201] Examples of the maleimide monomer include N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-hexylmaleimide, N-octylmaleimide, N-dodecylmaleimide, N-cyclohexylmaleimide, and N-phenylmaleimide.
[0202] The method for producing the vinyl copolymer is not particularly limited, and examples thereof include emulsion polymerization, suspension polymerization, bulk polymerization, and solution polymerization.
[0203] In addition, a polymerization initiator may be used as needed in the method for producing the vinyl copolymer. The polymerization initiator may be, for example, one or more appropriately selected from peroxides, azo compounds, potassium persulfate, etc. The amount of the polymerization initiator added is not particularly limited.
[0204] Examples of peroxides include benzoyl peroxide, cumene hydroperoxide, dicumyl peroxide, diisopropylbenzene hydroperoxide, tert-butyl hydroperoxide, tert-butyl peracetate, tert-butyl perbenzoate, tert-butyl isopropyl carbonate, di-tert-butyl peroxide, tert-butyl peroxyoctanoate, 1,1-bis(tert-butylbisoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylbisoxy)cyclohexane, and tert-butyl 2-ethylperoxyhexanoate. Among them, cumene hydroperoxide, 1,1-bis(tert-butylbisoxy)3,3,5-trimethylcyclohexane, and 1,1-bis(tert-butylbisoxy)cyclohexane are particularly preferred.
[0205] Examples of azo compounds include azobisisobutyronitrile, azobis(2,4-dimethylvaleronitrile), 2-phenylazo-2,4-dimethyl-4-methoxyvaleronitrile, 2-cyano-2-propylazocarbonamide, 1,1'-azobiscyclohexane-1-carbonitrile, azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-dimethylazobisisobutyrate, 1-(tert-butylazo)-2-cyanobutane, and 2-(tert-butylazo)-2-cyano-4-methoxy-4-methylpentane. Among them, 1,1'-azobiscyclohexane-1-carbonitrile is particularly preferred.
[0206] Specific examples of the vinyl copolymer include polyvinyl chloride, chlorinated polyvinyl chloride, polystyrene, styrene-acrylonitrile copolymer, styrene-acrylonitrile-N-phenylmaleimide copolymer, α-methylstyrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene copolymer, etc. These may be used alone or in combination of two or more.
[0207] Examples of the polyester include polyethylene terephthalate and polybutylene terephthalate.
[0208] The resin (B) may be the same resin (resin having the same components) as the matrix resin (C) to be mixed with the matrix resin (C) described later, or may be a different resin from the matrix resin (C). In the resin composition, it is preferred that the matrix resin (C) and the resin (B) do not phase separate. The resin (B) is preferably a resin that is compatible with the matrix resin (C).
[0209] When the resin (B) is the same resin as the matrix resin (C) to be mixed, the resin (B) has the advantage that it does not affect the various physical properties of the obtained powder-containing resin composition, cured product or molded product.
[0210] As an example, it is assumed that resin (B) is the same type of resin as matrix resin (C). In this case, the matrix resin (C) and resin (B) cannot be distinguished in the obtained resin composition containing powder particles. Therefore, in the obtained resin composition containing powder particles, in addition to polymer particles (A), the rest appears to have only resin (B) or only matrix resin (C). In addition, it is assumed that resin (B) is a different type of resin from matrix resin (C). In this case, the matrix resin (C) and resin (B) can be distinguished in the obtained resin composition containing powder particles. In this case, in the final obtained resin composition containing powder particles, in addition to polymer particles (A), resin (B) can also be contained as a resin other than matrix resin (C).
[0211] (I-2-2-3. Others)
[0212] In this specification, fats and fatty acid esters may also be included in the resin (B). As for fats and oils that can be preferably used as the resin (B), epoxidized fats and oils such as epoxidized soybean oil and epoxidized linseed oil may be mentioned. As epoxidized soybean oil, commercially available products may also be used, for example, ADKCIZER O-130P manufactured by ADEKA Co., Ltd. may be mentioned. As for fatty acid esters that can be preferably used as the resin (B), epoxidized fatty acid esters such as epoxidized fatty acid butyl ester, epoxidized fatty acid 2-ethylhexyl ester, epoxidized fatty acid octyl ester and epoxidized fatty acid alkyl ester may be mentioned.
[0213] Epoxidized fats and oils and epoxidized fatty acid esters are sometimes also referred to as epoxy plasticizers. That is, in the present specification, epoxy plasticizers may also be included in resin (B). Regarding epoxy plasticizers other than epoxidized fats and oils and epoxidized fatty acid esters, epoxy hexahydrophthalic acid di(epoxy octadecyl) and epoxy hexahydrophthalic acid di(2-ethylhexyl) etc. can be cited.
[0214] Each of the aforementioned thermosetting resins, thermoplastic resins, mixtures of thermosetting resins and thermoplastic resins, oils and fats, and fatty acid esters can be mixed with an antioxidant for use. In this specification, when an antioxidant is mixed with the above-mentioned substances, the antioxidant is regarded as a part of the resin (B). When only an antioxidant is used, the antioxidant is not regarded as the resin (B). The case where only an antioxidant is used to replace the resin (B) is described. Since the antioxidant is a component that does not contribute to crosslinking, after the obtained powder and granules are mixed with the matrix resin (C), the physical properties of the final product (i.e., the final product. For example, if the matrix resin (C) is a thermosetting resin, it refers to a cured product) tend to deteriorate. For example, there are cases where the Tg of the final product is reduced or the impact resistance is deteriorated.
[0215] The antioxidant is not particularly limited. Examples of the antioxidant include: (a) primary antioxidants such as phenolic antioxidants, amine antioxidants, lactone antioxidants, and hydroxylamine antioxidants; and (b) secondary antioxidants such as sulfur antioxidants and phosphorus antioxidants.
[0216] As the phenolic antioxidant, hindered phenolic antioxidants can be mentioned. As the hindered phenolic antioxidants, compounds having a hindered phenol structure or a semi-hindered phenol structure in the molecule can be mentioned. As the phenolic antioxidant, commercially available products can also be used, for example, Irganox 245 manufactured by BASF JAPAN Co., Ltd. can be mentioned.
[0217] The amine antioxidant is not particularly limited, and conventionally known substances can be widely used. Specific examples of the amine antioxidant include amine-ketone compounds, such as 2,2,4-trimethyl-1,2-dihydroquinoline polymers, 6-ethoxy-1,2-dihydro-2,2,4-trimethylquinoline, and a reaction product obtained by reacting diphenylamine with acetone.
[0218] The amine antioxidants also include aromatic amine compounds. Examples of the aromatic amine compounds include naphthylamine antioxidants, diphenylamine antioxidants, and p-phenylenediamine antioxidants.
[0219] There are no particular limitations on the lactone antioxidant, the hydroxylamine antioxidant, and the sulfur antioxidant, and conventionally known antioxidants can be widely used.
[0220] There is no particular limitation on the phosphorus antioxidant, and conventionally known substances can be widely used. Phosphoric acid and phosphoric acid esters containing active hydrogen may have adverse effects on the storage stability of the obtained resin composition containing powder and granules, and the heat resistance of the cured product or molded body provided by the resin composition. Therefore, as the phosphorus antioxidant, alkyl phosphites, aryl phosphites, alkyl aryl phosphites, etc. are preferably compounds that do not contain phosphoric acid and phosphoric acid esters in the molecule.
[0221] As the antioxidant, other conventionally known substances may also be used. As the antioxidant, for example, various substances described in the "Antioxidant Handbook" (first edition issued on October 25, 1975) issued by Dachengsha, the "Polymer Additive Handbook" (written by Haruna Tetsu, first edition issued on November 7, 2010) issued by CMC Publishing, etc. may be used.
[0222] Resin (B) is preferably selected from one or more of the following: thermosetting resin, a mixture of a thermosetting resin and an antioxidant, a thermoplastic resin, a mixture of a thermoplastic resin and an antioxidant, oils, a mixture of oils and antioxidants, fatty acid esters, a mixture of fatty acid esters and antioxidants, epoxy curing agents, and a mixture of epoxy curing agents and antioxidants. More preferably, it is selected from one or more of the following: epoxy resins, acrylic polymers, a mixture of epoxy resins and antioxidants, a mixture of acrylic polymers and antioxidants, and a mixture of epoxy plasticizers and antioxidants. It is further preferably selected from one or more of the following: a mixture of epoxy resins and antioxidants, a mixture of acrylic polymers and antioxidants, and a mixture of epoxy plasticizers and antioxidants. A mixture of epoxy plasticizers and antioxidants is particularly preferred. This scheme has the following advantages: (a) the obtained powder-containing resin composition can be used to provide a cured product or a molded product with excellent heat resistance, and (b) the dispersibility of the polymer particles (A) in the matrix resin (C) can be improved.
[0223] (I-2-2-4. Physical properties of resin (B))
[0224] The resin (B) is not particularly limited in other properties as long as it is a liquid, semi-solid or solid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25°C. In addition, "the resin (B) has a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25°C" means "the resin (B) has a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25°C".
[0225] If the resin (B) is a liquid, the viscosity of the resin (B) at 25° C. is preferably 750,000 mPa·s or less, more preferably 700,000 mPa·s or less, more preferably 500,000 mPa·s or less, more preferably 350,000 mPa·s or less, more preferably 300,000 mPa·s or less, more preferably 250,000 mPa·s or less, more preferably 100,000 mPa·s or less, more preferably 75,000 mPa·s or less, more preferably 50,000 mPa·s or less, more preferably 30,000 mPa·s or less, more preferably 25,000 mPa·s or less, further preferably 20,000 mPa·s or less, and particularly preferably 15,000 mPa·s or less. This embodiment provides the advantage of excellent fluidity of the powder or granule.
[0226] In addition, the viscosity of the resin (B) at 25°C is more preferably 200 mPa·s or more, more preferably 300 mPa·s or more, more preferably 400 mPa·s or more, more preferably 500 mPa·s or more, further preferably 750 mPa·s or more, further preferably 1000 mPa·s or more, and particularly preferably 1500 mPa·s or more. According to this embodiment, the resin (B) does not penetrate into the polymer microparticles (A), but penetrates between the particles of a plurality of polymer microparticles (A) and stays near the surface of the polymer microparticles (A). As a result, the resin (B) can prevent the polymer microparticles (A) from fusing with each other.
[0227] The viscosity of resin (B) at 25°C is more preferably 100 mPa·s to 750,000 mPa·s, more preferably 100 mPa·s to 700,000 mPa·s, more preferably 100 mPa·s to 350,000 mPa·s, more preferably 100 mPa·s to 300,000 mPa·s, more preferably 100 mPa·s to 50,000 mPa·s, further preferably 100 mPa·s to 30,000 mPa·s, and particularly preferably 100 mPa·s to 15,000 mPa·s.
[0228] If the resin (B) is semi-solid at 25°C, it can be said that the resin (B) is semi-liquid at 25°C, or it can be said that the resin (B) has a viscosity greater than 1,000,000 mPa·s at 25°C. If the resin (B) is semi-solid or solid at 25°C, the obtained powder-containing resin composition has the advantage of being less viscous and easier to handle.
[0229] Furthermore, the viscosity of the resin (B) at 25°C is preferably equal to or less than the value obtained by adding the viscosity of the matrix resin (C) at 25°C to 50,000 mPa·s. If the viscosity of the resin (B) at 25°C is equal to or greater than the viscosity of the matrix resin (C) at 25°C, then from the viewpoint of facilitating uniform mixing of the resin (B) and the matrix resin (C), the viscosity of the resin (B) at 25°C is more preferably equal to or less than the value obtained by adding the viscosity of the matrix resin (C) at 25°C to 20,000 mPa·s, more preferably to 10,000 mPa·s, further preferably to 5,000 mPa·s, and most preferably to 0 mPa·s.
[0230] The viscosity of the resin (B) can be measured using a viscometer. The method for measuring the viscosity of the resin (B) will be described in detail with reference to the following examples.
[0231] The resin (B) preferably has an endothermic peak at 25°C or lower in the thermogram of differential scanning calorimetry (DSC), and more preferably has an endothermic peak at 0°C or lower in the thermogram of differential scanning calorimetry (DSC).
[0232] Regarding the content of the resin (B) in the first powder, when the total amount of the polymer particles (A) and the resin (B) is 100% by weight, the polymer particles (A) are 50 to 99% by weight and the resin (B) is 1 to 50% by weight. The content of the resin (B) can be appropriately set within the above numerical range and the range of conditions that can provide a powder, according to the type of resin (B) and the physical properties of the resin (B) (solid, semi-solid, liquid, or viscosity, etc.). If the resin (B) is liquid at 25°C and the content of the resin (B) in the powder is large, sometimes the powder cannot be obtained. In addition, if the resin (B) is liquid at 25°C and the content of the resin (B) in the powder is large, there is a risk that the fluidity (smoothness) of the powder will deteriorate.
[0233] From the point of view of excellent anti-blocking property, the content of the resin (B) in the first granular body is described. When the total amount of the polymer microparticles (A) and the resin (B) is 100 weight %, it is more preferable that the polymer microparticles (A) are 55 to 99 weight % and the resin (B) is 1 to 45 weight %, more preferably the polymer microparticles (A) are 60 to 99 weight % and the resin (B) is 1 to 40 weight %, more preferably the polymer microparticles (A) are 65 to 99 weight % and the resin (B) is 1 to 35 weight %, more preferably the polymer microparticles (A) are 70 to 99 weight % and the resin (B) is 1 to 30 weight %, and ... The polymer particles (A) preferably account for 75 to 99% by weight and the resin (B) accounts for 1 to 25% by weight, more preferably the polymer particles (A) account for 80 to 99% by weight and the resin (B) accounts for 1 to 20% by weight, further preferably the polymer particles (A) account for 85 to 99% by weight and the resin (B) accounts for 1 to 15% by weight, further preferably the polymer particles (A) account for 90 to 99% by weight and the resin (B) accounts for 1 to 10% by weight, and particularly preferably the polymer particles (A) account for 95 to 99% by weight and the resin (B) account for 1 to 5% by weight.
[0234] The content of the resin (B) in the first granular body is described from the point of view that the polymer microparticles (A) have good dispersibility in the matrix resin (C). When the total amount of the polymer microparticles (A) and the resin (B) is 100 wt%, preferably the polymer microparticles (A) are 50 to 97 wt% and the resin (B) is 3 to 50 wt%, more preferably the polymer microparticles (A) are 50 to 95 wt% and the resin (B) is 5 to 50 wt%, more preferably the polymer microparticles (A) are 50 to 92 wt% and the resin (B) is 8 to 50 wt%, more preferably the polymer microparticles (A) are 50 to 90 wt% and the resin (B) is 10 to 50 wt%, and ...%. The polymer particles (A) are 50 to 87% by weight and the resin (B) is 13 to 50% by weight, more preferably the polymer particles (A) are 50 to 85% by weight and the resin (B) is 15 to 50% by weight, further preferably the polymer particles (A) are 50 to 82% by weight and the resin (B) is 18 to 50% by weight, further preferably the polymer particles (A) are 50 to 80% by weight and the resin (B) is 20 to 50% by weight, and particularly preferably the polymer particles (A) are 60 to 80% by weight and the resin (B) is 20 to 40% by weight.
[0235] (I-2-3. Anti-adhesive agent)
[0236] The first powder or granule preferably further contains an anti-blocking agent. According to this embodiment, the obtained powder or granule has the advantages of (a) excellent anti-blocking property and (b) excellent dispersibility of the polymer fine particles (A) in the matrix resin (C).
[0237] As long as the anti-adhesion agent plays the effect of one embodiment of the present invention, there is no particular restriction. As an anti-adhesion agent, it can be cited: an anti-adhesion agent composed of inorganic particles such as silicon dioxide, titanium oxide, aluminum oxide, zirconium oxide, aluminum silicate, diatomaceous earth, zeolite, kaolin, talc, calcium carbonate, calcium phosphate, barium sulfate, magnesium hydrosilicate; an anti-adhesion agent composed of organic particles; grease-based anti-adhesion agents such as polyethylene wax, higher fatty acid amide, metal soap, and silicone oil. Among these, an anti-adhesion agent composed of particles is preferred, and an anti-adhesion agent composed of organic particles is more preferred. As an anti-adhesion agent composed of organic particles, it is particularly preferred: an anti-adhesion agent composed of polymer organic particles containing structural units derived from one or more monomers in aromatic vinyl monomers, vinyl cyanide monomers, and (meth) acrylate monomers.
[0238] The anti-blocking agent composed of microparticles is generally a product or colloidal product formed by dispersing microparticles in a liquid. The volume average particle size (Mv) of the microparticles in the anti-blocking agent is usually less than 10 μm, preferably 0.05 μm to 10.00 μm. The content of the anti-blocking agent is preferably 0.01 wt% to 5.00 wt%, more preferably 0.50 wt% to 3.00 wt%, relative to the total weight (100 wt%) of the powder.
[0239] (I-2-4. Other optional ingredients)
[0240] The first powder or granule may contain other optional components other than the above-mentioned components as necessary. Examples of other optional components include various components described in the item (4-5. Other optional components) described later.
[0241] The anti-blocking agent and other optional components may be appropriately added during any process in the first method for producing the powder or granule. For example, the anti-blocking agent and other optional components may be added to the aqueous suspension (aqueous latex) of the polymer microparticles (A) before or after coagulation, or the polymer microparticles (A) and the resin (B) before or after coagulation. The anti-blocking agent and other optional components may also be added to the polymer microparticles (A), the resin (B), or the powder or granule containing the polymer microparticles (A) and the resin (B).
[0242] (I-2-5. Physical properties of powder and granule)
[0243] (Domain of resin (B) in TEM image)
[0244] From the viewpoint of preventing the polymer microparticles (A) in the powder and granule from fusing with each other, the resin (B) having a major diameter of 1.5 times or more the volume average particle diameter of the primary particles of the polymer microparticles (A) is preferably present in a small amount in the powder and granule. Specifically, when the powder and granule are subjected to transmission electron microscopy (TEM) analysis and a TEM image is obtained, the number of domains of the resin (B) having a major diameter of 1.5 times or more the average particle diameter of the polymer microparticles (A) is preferably 5 or less, more preferably 3 or less, further preferably 1 or less, and most preferably 0 or less, as viewed in the TEM image.
[0245] For the transmission electron microscope analysis, a known method can be used. For example, the following method can be cited: freeze the powder and then slice the frozen material using an ultrathin slicer to prepare a thin slice sample with a thickness of about 100 nm; then, stain the thin slice with osmium (OsO4) and then provide it to a transmission electron microscope (TEM). The major axis of the resin (B) refers to the maximum length obtained from the TEM image (the length of the longest straight line connecting any two points on the periphery). In addition, the average particle size of the primary particles of the polymer microparticles (A) can be calculated, for example, as follows: randomly select 30 polymer microparticles (A) from the SEM image, calculate the diameter of each conversion circle equal to the projection area of each of the 30 polymer microparticles (A) (circle area conversion diameter), and find the average value of these diameters.
[0246] (Volume average particle size of powder)
[0247] The volume average particle size (Mv) of the powder is preferably 30 μm to 500 μm, more preferably 30 μm to 300 μm, further preferably 50 μm to 300 μm, and particularly preferably 100 μm to 300 μm. According to this scheme, the dispersibility of the polymer particles (A) of the powder in the matrix resin (C) is excellent. In addition, according to this scheme, the following resin composition can be provided: the polymer particles (A) of the powder are uniformly dispersed in the matrix resin (C), have the desired viscosity and are highly stable. In this specification, the volume average particle size of the powder is a value measured using a laser diffraction particle size distribution measuring device (MICROTRAC MT3000II) manufactured by Micro Track Bell Co., Ltd.
[0248] The distribution of the volume average particle size relative to the number of particles preferably has a half-value width of 0.5 to 1 times the volume average particle size. This has the advantage that the obtained powder is less likely to contain fine powder that may cause dust explosions and coarse particles with poor dispersibility.
[0249] In the total amount of the powder (100 wt%), the particles having a volume average particle size of 1000 μm or more are preferably 6.00 wt% or less, more preferably 5.00 wt% or less, more preferably 4.50 wt% or less, more preferably 4.00 wt% or less, more preferably 3.50 wt% or less, more preferably 3.00 wt% or less, more preferably 2.50 wt% or less, more preferably 2.00 wt% or less, more preferably 1.50 wt% or less, more preferably 1.00 wt% or less, further preferably 0.50 wt% or less, and particularly preferably less than the detection limit (e.g. 0.00%). According to this embodiment, the powder has the advantage that the polymer fine particles (A) have very excellent dispersibility in the matrix resin (C). The “particles having a volume average particle size of 1000 μm or more” refers to powders having a particle size of 1000 μm or more, obtained by measuring the volume average particle size (Mv) of the polymer particles (A) using a laser diffraction particle size distribution analyzer MICROTRAC MT3000II (manufactured by MICROTRAC BEL Co., Ltd.).
[0250] In the total amount of the powder (100 wt%), the particles having a volume average particle size of 600 μm or more are preferably 6.00 wt% or less, more preferably 5.50 wt% or less, preferably 5.00 wt% or less, more preferably 4.50 wt% or less, more preferably 4.00 wt% or less, more preferably 3.50 wt% or less, more preferably 3.00 wt% or less, more preferably 2.50 wt% or less, more preferably 1.90 wt% or less, more preferably 2.00 wt% or less, more preferably 1.50 wt% or less, more preferably 1.00 wt% or less, further preferably 0.50 wt% or less, and particularly preferably less than the detection limit (e.g. 0.00%). According to this embodiment, the powder has the advantage that the polymer fine particles (A) are extremely well dispersed in the matrix resin (C). The “particles having a volume average particle size of 600 μm or more” refers to powders having a particle size of 600 μm or more obtained by measuring the volume average particle size (Mv) of the powder using a laser diffraction particle size distribution analyzer MICROTRAC MT3000II (manufactured by MICROTRAC BEL Co., Ltd.).
[0251] There is no particular limitation on the method for controlling the proportion of particles with a volume average particle size of 1000 μm or more or 600 μm or more in the total amount of powder or granules to be within the above-mentioned preferred numerical range, but the following methods can be cited: (1) in the method for manufacturing powder or granules, implementing gas phase coagulation in the later-described condensation step; or (2) using a mesh with a specified pore size to sieve the obtained powder or granules.
[0252] (Pore of powder)
[0253] The powder or granule has pores with an average pore diameter of 0.03 μm to 1.00 μm and the total volume of the pores is 0.0600 mL / g or more. In this specification, the average pore diameter of the powder or granule and the total volume of pores with a specific average pore diameter are values measured by an automatic mercury porosimetry pore distribution measurement device.
[0254] In the powder or granule, the total volume of pores having an average pore diameter of 0.03 μm to 1.00 μm is more preferably 0.0650 mL / g or more, more preferably 0.0700 mL / g or more, more preferably 0.0720 mL / g or more, more preferably 0.0750 mL / g or more, more preferably 0.0800 mL / g or more, more preferably 0.0850 mL / g or more, more preferably 0.0900 mL / g or more, more preferably 0.0950 mL / g or more, more preferably 0.1000 mL / g or more, further preferably 0.1050 mL / g or more, and particularly preferably 0.1100 mL / g or more. According to this embodiment, the powder or granule has the advantage that the polymer fine particles (A) are very well dispersed in the matrix resin (C).
[0255] The powder or granule may have pores with an average pore diameter of 0.03 μm to 4.50 μm. The total volume of pores with an average pore diameter of 0.03 μm to 4.50 μm in the powder or granule is more preferably 0.0900 mL / g or more, more preferably 0.0950 mL / g or more, more preferably 0.1000 mL / g or more, more preferably 0.1050 mL / g or more, more preferably 0.1100 mL / g or more, more preferably 0.1150 mL / g or more, more preferably 0.1200 mL / g or more, more preferably 0.1250 mL / g or more, further preferably 0.1300 mL / g or more, and particularly preferably 0.1350 mL / g or more. According to this embodiment, the powder or granule has the advantage that the dispersibility of the polymer microparticles (A) in the matrix resin (C) is very excellent.
[0256] (Anti-blocking)
[0257] The first powder and particle has excellent anti-adhesion properties. In this specification, the anti-adhesion properties of the powder and particle can be evaluated by the force required to disintegrate the clots of the powder and particle. Regarding the first powder and particle, the force required to disintegrate the clots of the powder and particle is preferably 30,000 Pa or less. Here, the clot is: a clot obtained by applying a load of 6.3 kg to the powder and particle by placing a weight of 6.3 kg on 30 g of the powder and particle contained in a cylindrical container with a diameter of 50 mm and letting it stand at 60°C for 2 hours. In addition, the force (the force required to disintegrate the clots of the powder and particle) is a value measured by a rheometer.
[0258] [I-3. Method for producing powder or granule]
[0259] The method for producing a powder or granule according to one embodiment of the present invention comprises: a coagulation step of preparing a coagulation body containing polymer microparticles (A) and a resin (B), and a drying step of subjecting the coagulation body to air flow drying or freeze drying. The polymer microparticles (A) comprise a rubber-containing graft copolymer, the rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer. The elastomer comprises one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber. The graft portion comprises a polymer having a specific structural unit, the specific structural unit being derived from one or more monomers selected from aromatic vinyl monomers, vinyl cyanide monomers and (meth)acrylate monomers. The resin (B) is a liquid having a viscosity of 100 mPa·s to 1000000 mPa·s at 25°C, or is a semisolid or solid. When the total amount of the polymer microparticles (A) and the resin (B) is 100% by weight, the polymer microparticles (A) are 50 to 99% by weight, and the resin (B) is 1 to 50% by weight. The “method for producing a powder or granule according to one embodiment of the present invention” may also be referred to as a “first production method”.
[0260] The first production method has the above-mentioned configuration, and therefore has the advantage of being able to provide a powder or granule having excellent dispersibility of the polymer fine particles (A) in the matrix resin. In other words, the first production method has the above-mentioned configuration, and therefore has the advantage of being able to provide a powder or granule that can be mixed with the matrix resin (C) to obtain a resin composition in which the polymer fine particles (A) are uniformly dispersed in the matrix resin (C).
[0261] Hereinafter, each step of the first production method will be described in detail, but matters other than those described below (for example, various components and their addition amounts, etc.) are not particularly limited, and the description in the above-mentioned section [I-2. Powders and granules] can be appropriately cited.
[0262] (I-3-1. Aggregation step)
[0263] The aggregation step is not particularly limited as long as aggregates containing polymer fine particles (A) and resin (B) are finally obtained. In other words, the finally obtained aggregates contain polymer fine particles (A) and resin (B).
[0264] The coagulation step may include, for example, the following steps in sequence: a preparation step (a1) of preparing an aqueous latex containing polymer particles (A) and a resin (B); and a coagulation step (a2) of coagulating the polymer particles (A) and the resin (B) in the obtained aqueous latex.
[0265] The preparation step (a1) is not particularly limited as long as an aqueous latex containing polymer particles (A) and resin (B) can be obtained. The method for obtaining the aqueous latex containing polymer particles (A) and resin (B) includes, for example, (i) a method of adding resin (B) to a reaction solution during the polymerization step of polymer particles (A), (ii) a method of adding resin (B) to an aqueous latex of polymer particles (A), and (iii) a method of polymerizing resin (B) using an aqueous latex of polymer particles (A).
[0266] The method of adding the resin (B) to the reaction solution in the polymerization step of the polymer particles (A) or the aqueous latex of the polymer particles (A) is not particularly limited. For example, there can be mentioned: (i) a method of directly adding the resin (B) to the reaction solution or the aqueous latex; (ii) a method of adding the aqueous latex containing the resin (B) to the reaction solution or the aqueous latex after separately preparing the aqueous latex containing the resin (B); and (iii) a method of adding the solution containing the resin (B) to the reaction solution or the aqueous latex after separately preparing the solution containing the resin (B). As the method of adding the resin (B), it is preferred to add the aqueous latex containing the resin (B) to the reaction solution or the aqueous latex after separately preparing the aqueous latex containing the resin (B).
[0267] When a coagulant is used in the aggregation step (a2), the resin (B) may be added to the aqueous latex of the polymer fine particles (A) before or after the coagulant is added. The resin (B) may also be added to the polymer fine particles (A) together with the coagulant.
[0268] As for the method for obtaining the aqueous latex containing the polymer fine particles (A) and the resin (B), a method of adding the resin (B) in the form of an aqueous latex to the aqueous latex of the polymer fine particles (A) is preferred.
[0269] The coagulation step (a2) is not particularly limited as long as a coagulation containing polymer particles (A) and resin (B) can be obtained. The method for coagulating the polymer particles (A) and the resin (B) in the aqueous latex is not particularly limited. As examples of the method, known methods such as a method using a coagulant, a method using a solvent, and a method of spraying the aqueous latex can be cited. Here, the mixture containing the coagulation containing polymer particles (A) and the resin (B) and the aqueous solvent obtained by coagulating the polymer particles (A) and the resin (B) in the aqueous latex is also called a slurry.
[0270] The aggregation of the polymer microparticles (A) and the resin (B) in the aqueous latex is preferably carried out in the presence of an anti-blocking agent, thereby achieving good anti-blocking properties and excellent dispersibility of the polymer microparticles (A) in the matrix resin (C).
[0271] As the aggregation step (a2), a method using a coagulant is preferably adopted. In other words, a coagulant is preferably used in the aggregation step in the first production method.
[0272] The coagulant is not particularly limited as long as it has the property of aggregating (also referred to as coagulation and solidification) the polymer microparticles (A) and the resin (B) in the aqueous latex by contact with the aqueous latex containing the polymer microparticles (A) and the resin (B). Examples of the coagulant include aqueous solutions of inorganic salts, aqueous solutions of inorganic acids, aqueous solutions of organic salts, aqueous solutions of organic acids, and polymer coagulants.
[0273] Examples of the inorganic salt include chloride salts, bromide salts, iodide salts, sulfates, nitrates, ammonium salts, phosphates, etc. Specific examples of the inorganic salt include sodium chloride, potassium chloride, lithium chloride, sodium bromide, potassium bromide, lithium bromide, potassium iodide, sodium iodide, potassium sulfate, sodium sulfate, ammonium sulfate, ammonium chloride, sodium nitrate, potassium nitrate, calcium chloride, ferrous sulfate, magnesium sulfate, zinc sulfate, copper sulfate, barium chloride, ferrous chloride, ferric chloride, magnesium chloride, iron sulfate, aluminum sulfate, potassium alum, iron alum, etc.
[0274] Examples of the inorganic acid include hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and the like.
[0275] Examples of the organic salt include acetates, citrates, formates, gluconates, lactates, oxalates, tartrates, etc. of alkali metals or alkaline earth metals. Specific examples of the organic acid salt include sodium acetate, calcium acetate, sodium formate, calcium formate, etc.
[0276] Examples of the organic acid include acetic acid and formic acid.
[0277] As for the polymer coagulant, it is not particularly limited as long as it is a polymer compound having a hydrophilic group and a hydrophobic group, and can be any one of anionic, cationic, and nonionic polymer coagulants. From the viewpoint of being able to further improve the effect of one embodiment of the present invention, as the polymer coagulant, a cationic polymer coagulant is preferred. A cationic polymer coagulant is a polymer coagulant having a cationic group in the molecule, that is, a polymer coagulant that exhibits cationicity when dissolved in water. As cationic polymer coagulants, for example, polyamines, polydicyandiamides, cationized starch, cationic poly (methyl) acrylamide, water-soluble aniline resins, polythioureas, polyethyleneimine, quaternary ammonium salts, polyvinyl pyridines, chitosan, etc. can be cited.
[0278] As the coagulant, only one of the above compounds may be used, or two or more of them may be used in combination. As the coagulant, sodium chloride, potassium chloride, sodium sulfate, ammonium chloride, calcium chloride, magnesium chloride, magnesium sulfate, barium chloride, hydrochloric acid, sulfuric acid, and other monovalent or divalent inorganic salts or aqueous solutions of inorganic acids may be preferably used among the above compounds. The method of adding the coagulant is not particularly limited, and the coagulant may be added all at once, in batches, or continuously.
[0279] By bringing an aqueous latex containing polymer particles (A) and a resin (B) into contact with a coagulant or a coagulant solution (e.g., an aqueous solution), the polymer particles (A) and the resin (B) can be coagulated. The method for bringing an aqueous latex containing polymer particles (A) and a resin (B) into contact with a coagulant or a coagulant solution is not particularly limited. Examples of such methods include: (i) bringing an aqueous latex containing polymer particles (A) and a resin (B) into contact with a coagulant or a coagulant solution (hereinafter referred to as coagulation method 1); and (ii) spraying an aqueous latex containing polymer particles (A) and a resin (B) to obtain droplets containing polymer particles (A) and a resin (B), and bringing the droplets into contact with a coagulant or a coagulant solution (hereinafter referred to as coagulation method 2), etc.
[0280] Coagulation method 1 is a method in which the aqueous latex containing polymer particles (A) and resin (B) is used in a liquid phase, in other words, it is a method in which the aqueous latex containing polymer particles (A) and resin (B) is not sprayed. In this specification, coagulation method 1 is also referred to as "liquid phase coagulation".
[0281] The coagulation method 1 is described in detail. As the coagulation method 1, the following methods can be specifically mentioned: (1-i) adding a coagulant to an aqueous latex containing polymer particles (A) and a resin (B); (1-ii) mixing the aqueous latex containing polymer particles (A) and a resin (B) with a coagulant solution; (1-iii) spraying a coagulant or a coagulant solution onto the aqueous latex containing polymer particles (A) and a resin (B). This method (1-iii) can also be referred to as a method of spraying a coagulant or a coagulant solution in the presence of polymer particles (A) and a resin (B). In the coagulation method 1, an aqueous latex containing polymer particles (A), a resin (B) and a coagulant can be obtained.
[0282] The coagulation method 1 may further include a step of heating the obtained aqueous latex (the aqueous latex containing the polymer particles (A), the resin (B) and the coagulant). If there is a step of heating the aqueous latex containing the polymer particles (A), the resin (B) and the coagulant, the following advantages can be achieved: the water content of the obtained coagulation can be reduced, and / or the fine powder in the obtained powder can be reduced. In the heating step, the temperature (heating temperature) of the aqueous latex obtained by heating the aqueous latex containing the polymer particles (A), the resin (B) and the coagulant is not particularly limited.
[0283] Coagulation method 2 is a method of spraying an aqueous latex containing polymer particles (A) and a resin (B), in other words, a method of using the aqueous latex containing polymer particles (A) and a resin (B) in the form of droplets. In this specification, coagulation method 2 is also referred to as "vapor phase coagulation".
[0284] The coagulation method 2 is described in detail. As the coagulation method 2, the following methods can be specifically mentioned: (2-i) spraying an aqueous latex containing polymer particles (A) and a resin (B) into a coagulant or a coagulant solution; (2-ii) spraying an aqueous latex containing polymer particles (A) and a resin (B), and spraying a coagulant or a coagulant solution. The method (2-i) can also be referred to as a method including a polymer particle spraying step, wherein the polymer particle spraying step is spraying an aqueous latex containing polymer particles (A) and a resin (B) in the presence of a coagulant.
[0285] The method (2-ii) is specifically described. The method (2-ii) may include the following forms: (2-ii-a) contacting the droplets containing polymer particles (A) and / or resin (B) obtained by spraying with the droplets containing a coagulant obtained by spraying; (2-ii-b) spraying an aqueous latex containing polymer particles (A) and resin (B) into the area (space) where the droplets containing the sprayed coagulant exist; and (2-ii-c) spraying a coagulant solution into the area (space) where the droplets containing polymer particles (A) and / or resin (B) obtained by spraying exist. Here, the existence (space) of the droplets containing the coagulant can also be understood as: in the presence of the coagulant. In addition, the existence area (space) of the droplets containing polymer particles (A) and / or resin (B) can also be understood as: in the presence of the polymer particles (A) and resin (B). Therefore, the method (2-ii) can also be referred to as a method comprising a polymer particle spraying step and a coagulant spraying step, wherein the polymer particle spraying step is to spray an aqueous latex containing polymer particles (A) and a resin (B) in the presence of a coagulant, and the coagulant spraying step is to spray a coagulant or a solution containing a coagulant in the presence of polymer particles (A) and a resin (B).
[0286] The coagulation step in the first manufacturing method is preferably carried out by coagulation method 2, that is, by "gas phase coagulation". In other words, the coagulation step in the first manufacturing method preferably further includes a polymer particle spraying step of spraying an aqueous latex containing polymer particles (A) and a resin (B) in the presence of a coagulant. The advantage of this scheme is that it can obtain: particles with a volume average particle size of 1000 μm or more or particles with a volume average particle size of 600 μm or more account for a low proportion of the total amount of powder and particles. The coagulation step in the first manufacturing method is more preferably not only a polymer particle spraying step, but also a coagulant spraying step of spraying a coagulant or a solution containing a coagulant in the presence of polymer particles (A) and a resin (B). The advantage of this scheme is that it can obtain: particles with a volume average particle size of 1000 μm or more or particles with a volume average particle size of 600 μm or more account for a low proportion of the total amount of powder and particles.
[0287] Through the preparation step (a1) and the aggregation step (a2), a slurry having aggregates containing polymer microparticles (A) and resin (B) can be obtained. The aggregation step may further include a recovery step (a3) of recovering the aggregates obtained from the slurry, that is, recovering the aggregates containing polymer microparticles (A) and resin (B).
[0288] The recovery step (a3) is not particularly limited as long as the aqueous solvent in the slurry can be separated from the aggregates, and a known method can be used. Examples of the recovery step (a3) include a method of filtering the slurry and a method of centrifugally dehydrating the slurry.
[0289] As other styles of the coagulation process, for example, there can be cited a scheme which includes the following steps in sequence: a coagulation step (b1) of using an aqueous latex containing only polymer particles (A) and coagulating the polymer particles (A) in the aqueous latex; a recovery step (b2) of recovering the coagulates of the obtained polymer particles (A); and a mixing step (b3) of mixing the recovered coagulates of the polymer particles (A) with a resin (B).
[0290] The coagulation step (b1) includes a preferred embodiment and may be the same as the coagulation step (a2) except that an aqueous latex containing only polymer fine particles (A) is used instead of an aqueous latex containing polymer fine particles (A) and resin (B).
[0291] The recovery step (b2) includes a preferred embodiment and may be the same as the recovery step (a3) except that the agglomerates contain only the polymer fine particles (A) instead of the polymer fine particles (A) and the resin (B).
[0292] In the mixing step (b3), the method for mixing the recovered aggregates of polymer microparticles (A) and the resin (B) is not particularly limited, and examples of the method include mechanical mixing methods using a planetary mixer, a planetary mixer, a disperser, and the like.
[0293] (I-3-2. Water content of aggregates)
[0294] The agglomerates containing polymer microparticles (A) and resin (B) obtained in the agglomeration step may contain water. The water content of the agglomerates is preferably 10% to 70%, more preferably 20% to 60%, more preferably 30% to 60%, further preferably 30% to 50%, and particularly preferably 30% to 40%, relative to the total weight of the agglomerates (100% by weight). The water content of the agglomerates can be measured by drying the obtained agglomerates in an oven at 120°C for 1 hour, and then comparing the weights before and after drying.
[0295] (I-3-3. Drying step)
[0296] The drying step is a step of drying the aggregates containing the polymer microparticles (A) and the resin (B) obtained in the agglomeration step. In the first production method, the drying step is to air flow dry or freeze dry the aggregates.
[0297] In this specification, airflow drying means drying the aggregates while making them fly in a certain space. The airflow drying method is not particularly limited, and a conventionally known method can be used. As an example of airflow drying, the following method can be cited: the aggregates are contained in a container, and then a gas at a predetermined temperature is sent into the container, thereby drying the aggregates while making them fly in the container.
[0298] The ambient temperature during the drying step is not particularly limited. From the viewpoint of obtaining a powdery granule having a more excellent dispersibility of the polymer microparticles (A) in the matrix resin (C), the drying step is preferably carried out at a temperature of 100°C or less, more preferably at a temperature of 90°C or less, more preferably at a temperature of 80°C or less, more preferably at a temperature of 70°C or less, more preferably at a temperature of 60°C or less, more preferably at a temperature of 50°C or less, more preferably at a temperature of 40°C or less, more preferably at a temperature of 30°C or less, more preferably at a temperature of 20°C or less, further preferably at a temperature of 10°C or less, and particularly preferably at a temperature of 0°C or less.
[0299] Regarding air flow drying, the ambient temperature during the drying process can be adjusted by changing the internal temperature of the container containing the aggregates and / or the temperature of the gas sent into the container.
[0300] Regarding the air flow drying, the gas fed into the container is not particularly limited, and examples of the gas include air, nitrogen, a mixture of nitrogen and air, a mixture of nitrogen and oxygen, and a rare gas.
[0301] The freeze-drying method is not particularly limited, and a conventionally known method can be used. If freeze-drying is used as the drying step, the drying step can be easily performed at a temperature of 0°C or lower.
[0302] The time of the drying process is not particularly limited and can be appropriately set depending on the degree of drying of the agglomerate. The drying time can be, for example, 1 minute to 3 hours, but is preferably 1 minute to 1 hour, more preferably 1 minute to 30 minutes, further preferably 1 minute to 20 minutes, and particularly preferably 1 minute to 10 minutes. The length of time for implementing the drying process can be, for example, the time required for the temperature of the agglomerate (powder and granular body) to reach 40°C.
[0303] In this specification, a method of drying the aggregate containing polymer fine particles (A) and resin (B) by leaving it to stand in a container such as an oven as in the prior art is also referred to as "standing drying".
[0304] (I-3-4. Washing step)
[0305] The first manufacturing method preferably further includes a step of washing the agglomerates obtained in the agglomeration step between the agglomeration step and the drying step. By washing the agglomerates, a powder with a small content of inclusions etc. can be obtained. In the washing step, it is more preferred to wash the agglomerates with water, and it is further preferred to wash with ion exchange water or pure water.
[0306] The washing process is not particularly limited to a specific method as long as it is a process for washing the agglomerates. As a specific method of the washing process, for example, a method of mixing the agglomerates with water and stirring them with a stirrer, a method of kneading the agglomerates with water using a kneader, a method of mixing the agglomerates with water using a planetary mixer, a method of spraying water onto the agglomerates, a method of washing the filter cake using a pressure filter, etc. As a kneading machine, various equipment such as a batch kneading machine, a continuous kneading machine, an extrusion kneading machine, and an extruder can be used.
[0307] The washing time is not particularly limited, and for example, 1 second to 60 minutes can be cited. The washing time is preferably 1 second to 45 minutes, more preferably 1 second to 30 minutes, more preferably 1 minute to 30 minutes, further preferably 3 minutes to 30 minutes, particularly preferably 5 minutes to 30 minutes, and particularly preferably 10 minutes to 30 minutes.
[0308] The number of washing is not particularly limited, and for example, 1 to 10 times (cycles) can be cited. The number of washing is preferably 1 to 6 times (cycles), more preferably 1 to 5 times (cycles), further preferably 1 to 4 times (cycles), and most preferably 1 to 3 times (cycles).
[0309] The amount of washing water is not particularly limited, and for example, it can be 0.1 to 1000 parts by weight relative to 1 part by weight of the agglomerate. The amount of washing water is preferably 1 to 1000 parts by weight, more preferably 1 to 500 parts by weight, more preferably 1 to 200 parts by weight, more preferably 10 to 200 parts by weight, further preferably 15 to 200 parts by weight, and particularly preferably 20 to 200 parts by weight. The amount of washing water is also preferably 1 to 10 parts by weight, preferably 2 to 10 parts by weight, and preferably 2 to 5 parts by weight relative to 1 part by weight of the agglomerate. In addition, if the agglomerate is kneaded with water for washing using a kneader, less washing water can be used, so it is more preferred.
[0310] The temperature of the washing water is also not limited. For example, normal temperature washing water or heated warm washing water can be appropriately used. Since warm washing water has a high washing effect, it is preferred to use heated washing water. The temperature of the washing water can be, for example, 10°C to 100°C, preferably 15°C to 100°C, more preferably 20°C to 100°C, more preferably 40°C to 100°C, more preferably 40°C to 90°C, further preferably 40°C to 85°C, further preferably 40°C to 80°C, and particularly preferably 40°C to 70°C.
[0311] There is no limitation on the method for removing the washing wastewater in the washing process, and examples thereof include drying of the washing water, vacuum filtration, oil-water separation, filter pressing, centrifugation, belt pressing, screw pressing, membrane separation, and squeeze dehydration.
[0312] The object to be washed is not particularly limited to various impurities contained in the aggregate, and includes, for example, not only impurities derived from emulsifiers (such as phosphorus emulsifiers and sulfonic acid emulsifiers), but also impurities derived from coagulants when coagulants are used.
[0313] (I-3-5. Temperature)
[0314] It is preferred that the agglomerates and powders containing polymer particles (A) and resin (B) are operated (treated) in a temperature environment lower than the glass transition temperature of the grafted portion of the polymer particles (A) throughout the entire process of the production method. In other words, the shorter the exposure time of the agglomerates and powders containing polymer particles (A) and resin (B) to a temperature environment higher than the glass transition temperature of the grafted portion of the polymer particles (A) throughout the entire process of the production method, the more preferably. By this scheme, a powder having a better dispersibility of the polymer particles (A) in the matrix resin (C) can be obtained. As a result, the obtained powder can be used to provide a resin composition in which the polymer particles (A) are more uniformly dispersed in the matrix resin (C).
[0315] In the first manufacturing method, the exposure time (period) of the agglomerates and granules containing polymer particles (A) and resin (B) to a temperature environment above the glass transition temperature of the grafted portion of the polymer particles (A) can be shortened by adjusting the following temperatures. These temperatures include: the temperature of the aqueous latex containing polymer particles (A); the temperature of the aqueous latex containing polymer particles (A) and resin (B) (the aqueous latex before the coagulant is added); the temperature of the aqueous solution of the coagulant; the temperature of the aqueous latex containing polymer particles (A), resin (B) and coagulant; the heating temperature in the heating step; the drying temperature in the drying step; the temperature of the washing water in the washing step, etc.
[0316] The temperature lower than the glass transition temperature of the grafted part of the polymer microparticles (A) is different depending on the components of the grafted part, and is therefore appropriately set according to the components of the grafted part. In the entire process of the production method, the agglomerate and the powder containing the polymer microparticles (A) and the resin (B) are preferably operated in an environment below 90°C, more preferably below 80°C, and further preferably below 70°C. That is, the various temperatures mentioned above are preferably below 90°C, more preferably below 80°C, more preferably below 70°C, more preferably below 60°C, more preferably below 50°C, and further preferably below 40°C.
[0317] [I-4. Resin composition]
[0318] A resin composition containing the above-mentioned powder or granule (first powder or granule) and a matrix resin (C) is also one embodiment of the present invention. Hereinafter, the "resin composition according to one embodiment of the present invention" may also be referred to as the "present resin composition".
[0319] (I-4-1. Matrix resin (C))
[0320] The matrix resin (C) may be, for example, a thermosetting resin, a thermoplastic resin, or any combination of a thermosetting resin and a thermoplastic resin.
[0321] The thermosetting resin and the thermoplastic resin concerning the matrix resin (C) each include preferred embodiments, and may be the same embodiments as the thermosetting resin and the thermoplastic resin described in the above section (I-2-2. Resin (B)).
[0322] In the past, it was very difficult to disperse polymer particles (A) in a thermosetting resin in the form of primary particles. However, the powder and granules according to one embodiment of the present invention have the advantage of being able to provide a resin composition in which polymer particles (A) are more uniformly dispersed in the matrix resin (C), even when a thermosetting resin is used as the matrix resin (C). The matrix resin (C) may be a thermosetting resin. The first powder and granules may be powder and granules for a thermosetting resin.
[0323] (I-4-2. Physical properties of matrix resin (C))
[0324] The properties of the matrix resin (C) are not particularly limited. The matrix resin (C) preferably has a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25°C. The viscosity of the matrix resin (C) at 25°C is more preferably 50,000 mPa·s or less, further preferably 30,000 mPa·s or less, and particularly preferably 15,000 mPa·s or less. Through this scheme, the matrix resin (C) has the advantage of excellent fluidity. The matrix resin (C) having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25°C can also be said to be a liquid.
[0325] The greater the fluidity of the matrix resin (C), in other words, the smaller the viscosity, the more difficult it is to disperse the polymer microparticles (A) in the matrix resin (C) in the form of primary particles. In the past, it was very difficult to disperse the polymer microparticles (A) in the form of primary particles in a matrix resin (C) having a viscosity of 1000000 mPa·s or less at 25°C. However, the resin composition according to one embodiment of the present invention has the advantage that the polymer microparticles (A) having the above-mentioned scheme can be well dispersed in a matrix resin (C) having a viscosity of 1000000 mPa·s or less at 25°C.
[0326] In addition, the viscosity of the matrix resin (C) at 25°C is more preferably 100 mPa·s or more, further preferably 500 mPa·s or more, further preferably 1000 mPa·s or more, and particularly preferably 1500 mPa·s or more, so that the matrix resin (C) can enter the polymer particles (A) to prevent the polymer particles (A) from fusing with each other.
[0327] The viscosity of the matrix resin (C) at 25°C is more preferably 100 mPa·s to 750,000 mPa·s, more preferably 100 mPa·s to 700,000 mPa·s, more preferably 100 mPa·s to 350,000 mPa·s, more preferably 100 mPa·s to 300,000 mPa·s, more preferably 100 mPa·s to 50,000 mPa·s, further preferably 100 mPa·s to 30,000 mPa·s, and particularly preferably 100 mPa·s to 15,000 mPa·s.
[0328] The matrix resin (C) may have a viscosity greater than 1,000,000 mPa·s. The matrix resin (C) may be semi-solid (semi-liquid) or solid. If the matrix resin (C) has a viscosity greater than 1,000,000 mPa·s, the obtained powder-containing resin composition has the advantage of less adhesion and easier handling.
[0329] The matrix resin (C) preferably has an endothermic peak at 25° C. or lower, and more preferably has an endothermic peak at 0° C. or lower in the thermogram of differential scanning calorimetry (DSC). According to this embodiment, the matrix resin (C) has an advantage of excellent fluidity.
[0330] (I-4-3. Mixing ratio of powder and granule and matrix resin (C) etc.)
[0331] Regarding the mixing ratio of the first powder and granule and the matrix resin (C), when the total amount of the powder and the matrix resin (C) is 100% by weight, it is generally preferred that the powder and granule be 0.5 to 50% by weight and the matrix resin (C) be 50 to 99.5% by weight, more preferably the powder and granule be 1 to 50% by weight and the matrix resin (C) be 50 to 99% by weight, more preferably the powder and granule be 1 to 45% by weight and the matrix resin (C) be 55 to 99% by weight, more preferably the powder and granule be 1 to 40% by weight and the matrix resin (C) be 60 to 99% by weight, and more preferably the powder and granule be 1 to 35% by weight. The amount of the powder and granules is preferably 1-30% by weight and the matrix resin (C) is 70-99% by weight, more preferably the amount of the powder and granules is 1-25% by weight and the matrix resin (C) is 75-99% by weight, more preferably the amount of the powder and granules is 1.5-25% by weight and the matrix resin (C) is 75-98.5% by weight, further preferably the amount of the powder and granules is 1.5-20% by weight and the matrix resin (C) is 80-98.5% by weight, and particularly preferably the amount of the powder and granules is 2.5-20% by weight and the matrix resin (C) is 80-97.5% by weight.
[0332] If it is desired to control the content ratio of the polymer particles (A) and the matrix resin (C) in the obtained resin composition to a desired value, the blending ratio of the first powder and the matrix resin (C) can be appropriately set based on (a) the content and water content of components other than the polymer particles (A) contained in the powder and the particle, and (b) the method of mixing the powder and the matrix resin (C).
[0333] Regarding the content ratio of the polymer microparticles (A) and the matrix resin (C) in the resin composition, when the total amount of the polymer microparticles (A) and the matrix resin (C) is 100% by weight, it is generally preferred that the polymer microparticles (A) be 0.5 to 50% by weight and the matrix resin (C) be 50 to 99.5% by weight, more preferably the polymer microparticles (A) be 1 to 50% by weight and the matrix resin (C) be 50 to 99% by weight, more preferably the polymer microparticles (A) be 1 to 45% by weight and the matrix resin (C) be 55 to 99% by weight, more preferably the polymer microparticles (A) be 1 to 40% by weight and the matrix resin (C) be 60 to 99% by weight, and more preferably the polymer microparticles (A) be 1 to 40% by weight and the matrix resin (C) be 60 to 99% by weight. The polymer particles (A) are 1 to 35% by weight and the matrix resin (C) is 65 to 99% by weight, more preferably 1 to 30% by weight and the matrix resin (C) is 70 to 99% by weight, more preferably 1 to 25% by weight and the matrix resin (C) is 75 to 99% by weight, more preferably 1.5 to 25% by weight and the matrix resin (C) is 75 to 98.5% by weight, still more preferably 1.5 to 20% by weight and the matrix resin (C) is 80 to 98.5% by weight, and particularly preferably 2.5 to 20% by weight and the matrix resin (C) is 80 to 97.5% by weight.
[0334] The matrix resin (C) is not particularly limited as long as it is a thermosetting resin and is in a fluid state when mixed with the powder or particulate matter. The matrix resin (C) may be solid at room temperature, but is preferably liquid from the viewpoint of processability.
[0335] The temperature at which the powder and the matrix resin (C) are mixed is generally set to a temperature at which the matrix resin (C) can flow. With regard to this temperature, if the resin (B) in the powder can flow at the same temperature at which the matrix resin (C) can flow, the mixed resin (B) and the matrix resin (C) can be easily mixed uniformly.
[0336] If the present resin composition contains a thermosetting resin as a matrix resin (C), a cured product can be obtained by curing the resin composition. If the present resin composition contains a thermoplastic resin as a matrix resin (C), a molded body can be obtained by molding the resin composition. The cured product formed by curing the present resin composition and the molded body formed by molding the present resin composition are also each an embodiment of the present invention.
[0337] The present resin composition may further contain a known thermosetting resin other than the matrix resin (C), and may further contain a known thermoplastic resin.
[0338] (I-4-4. Organic solvent)
[0339] The present resin composition preferably contains substantially no organic solvent. When the above-mentioned powder or granule contains substantially no organic solvent, a resin composition containing substantially no organic solvent can be obtained. "Substantially containing no organic solvent" means that the amount of organic solvent in the resin composition is 100 ppm or less.
[0340] The amount of organic solvent contained in this resin composition (also referred to as solvent content) is preferably less than 100ppm, more preferably less than 50ppm, further preferably less than 25ppm, and particularly preferably less than 10ppm. The amount of organic solvent contained in this resin composition may also be referred to as the amount of volatile components (but excluding water) contained in this resin composition. The amount of organic solvent (volatile component) contained in this resin composition may be obtained, for example, by the following method: heating a specified amount of resin composition with a hot air dryer, etc., measuring the weight of the resin composition before and after heating to obtain the reduced weight, and using the reduced weight as the amount of organic solvent. In addition, the amount of organic solvent (volatile component) contained in this resin composition may also be obtained by gas chromatography. In addition, in the manufacture of the powder and granular body contained in this resin composition and the resin composition, if no organic solvent is used, the amount of organic solvent contained in the resin composition obtained may be regarded as 0ppm.
[0341] The organic solvents substantially not contained in the present resin composition include: (a) esters such as methyl acetate, ethyl acetate, propyl acetate and butyl acetate; (b) ketones such as acetone, methyl ethyl ketone, diethyl ketone and methyl isobutyl ketone; (c) alcohols such as ethanol, (iso)propanol and butanol; (d) ethers such as tetrahydrofuran, tetrahydropyran, dioxane and diethyl ether; (e) aromatic hydrocarbons such as benzene, toluene and xylene; and (f) halogenated hydrocarbons such as dichloromethane and chloroform.
[0342] (I-4-5. Other optional ingredients)
[0343] As required, the present resin composition may also contain other arbitrary components other than the aforementioned components. As other arbitrary components, curing agents, colorants such as pigments and dyes, extender pigments, pigment dispersants, ultraviolet absorbers, the aforementioned antioxidants, heat stabilizers (anti-gelling agents), plasticizers, leveling agents, defoamers, silane coupling agents, antistatic agents, flame retardants, lubricants, viscosity reducers, viscosity modifiers, thixotropy imparting agents, shrinkage reducing agents, inorganic fillers, organic fillers, thermoplastic resins, desiccants, dispersants, thermal conductivity improvers, water binders, overflow preventers, anti-color cross-linking agents, anti-settling agents, film consumption adjusters, surface adjusters, monobasic organic acids, camphor, castor oil, etc. can be cited.
[0344] (I-4-6. Method for producing resin composition)
[0345] The method for producing a resin composition according to one embodiment of the present invention includes the step of mixing the powder and granules described in the item [I-2. Powder and granules] with a matrix resin (C). The method for producing a resin composition according to one embodiment of the present invention may also include the step of mixing the powder and granules obtained by the method for producing a powder and granules described in the item [I-3. Method for producing a powder and granules] with a matrix resin (C). According to these schemes, a resin composition in which polymer microparticles (A) are uniformly dispersed in a matrix resin (C) can be obtained.
[0346] Regarding the method for producing the resin composition, the various components and specific steps therein are not particularly limited, and the above description can be appropriately cited.
[0347] The specific method for mixing the powder and the matrix resin (C) is not particularly limited, and examples thereof include a method using a planetary mixer, a planetary mixer, a disperser, etc. The method for mixing the powder and the matrix resin (C) is preferably a method of mixing at 2000 rpm for 40 minutes using a planetary mixer.
[0348] Furthermore, the method for producing the resin composition may include a step of washing the obtained resin composition. By washing the resin composition, a resin composition with fewer inclusions can be produced. With regard to this washing step, the "powder and granular body" in the item (3-3. washing step) may be replaced with "resin composition" to cite the record of this item.
[0349] Moreover, the method for producing the resin composition according to one embodiment of the present invention may also include other steps. In addition to the aforementioned steps, the resin composition obtained may also be heated to perform devolatilization and drying. The steps may also be performed using various methods and are not particularly limited. For example, heating and vacuum devolatilization may be used to perform devolatilization and drying.
[0350] [I-5. Cured product]
[0351] Regarding the present resin composition described in the item "〔I-4. Resin composition〕", a cured product obtained by curing the present resin composition when the matrix resin (C) is a thermosetting resin is also an embodiment of the present invention. Hereinafter, "the cured product involved in one embodiment of the present invention" is also referred to as "the present cured product".
[0352] The cured product has the above configurations and has (a) a beautiful surface, (b) high rigidity and high elastic modulus, and (c) excellent toughness and adhesiveness.
[0353] 〔I-6. Other uses〕
[0354] The powder (first powder) or resin composition involved in one embodiment of the present invention can be used for a variety of purposes, and the purpose is not particularly limited. The first powder or resin composition can be preferably used for the following purposes, for example: metal-clad laminates, adhesives, coatings, diaphragms, adhesives for reinforcing fibers, resin concrete, composite materials, 3D printing molding materials, sealants, electronic substrates, ink adhesives, wood chip adhesives, rubber chip adhesives, foam chip adhesives, casting adhesives, base plate consolidation materials for floor materials and ceramics, polyurethane foams, etc. As polyurethane foams, car seats, car interior parts, sound absorbing materials, shock absorbing materials, shock absorbers (impact absorbing materials), heat insulating materials, building floor material padding materials, etc. can be cited.
[0355] Among the above uses, the first powder or resin composition is more preferably used for adhesives, coating materials, films, binders for reinforcing fibers, composite materials, molding materials for 3D printing, sealants, and electronic substrates.
[0356] (I-6-1. Metal-clad laminate)
[0357] The metal-clad laminated plate according to one embodiment of the present invention may be any plate made of the present resin composition described in [I-4. Resin composition] when the matrix resin (C) is a thermosetting resin. Hereinafter, the metal-clad laminated plate according to one embodiment of the present invention may be referred to as the present metal-clad laminated plate.
[0358] The metal-clad laminate has the advantages of excellent toughness and impact resistance due to the above-mentioned solution.
[0359] The use of the metal-clad laminate is not particularly limited, and examples thereof include printed circuits, printed wiring, printed wiring boards, printed wiring boards, printed wiring boards, and the like.
[0360] (I-6-2. Adhesive)
[0361] The adhesive according to one embodiment of the present invention includes the first powder or granular material or the resin composition. The adhesive according to one embodiment of the present invention has excellent adhesiveness due to the above configuration.
[0362] The adhesive according to one embodiment of the present invention is also simply referred to as the present adhesive.
[0363] The adhesive can be used in various applications, such as automotive interior materials, general woodworking, furniture, interior decoration, wall materials, and food packaging.
[0364] This adhesive exhibits good adhesion to the following adherends: cold-rolled steel, aluminum, polyester (FRP) reinforced with glass fiber, panels of cured products of thermosetting resins such as epoxy resin reinforced with carbon fiber, panels of thermoplastic resin sheets reinforced with carbon fiber, seat molding materials (SMC), acrylonitrile-butadiene-styrene copolymers (ABS), polyvinyl chloride (PVC), polycarbonate, polypropylene, TPO, wood and glass, etc.
[0365] The adhesive has excellent bonding performance and flexibility not only at low temperature (about -20°C) to room temperature, but also at high temperature (about 80°C). Therefore, the adhesive can be better used as an adhesive for structures.
[0366] The adhesive for structures using this adhesive can be used as an adhesive for structural parts in the fields of automobiles, locomotives (such as high-speed railways, rail vehicles, etc.), civil engineering, construction, building materials, woodworking, electrical, electronic, aircraft, and aerospace industries. In particular, the following uses can be cited in automobile-related applications: bonding of interior materials such as ceilings, doors, and seats; automotive lighting fixtures such as lighting lamps; bonding of exterior materials such as frame plastic sealing materials, etc.
[0367] The present adhesive can be produced using the first powder or granular material or the resin composition. The method for producing the present adhesive is not particularly limited, and a known method can be used.
[0368] (I-6-3. Coating material)
[0369] The coating material according to one embodiment of the present invention includes the first powder or granular material or the resin composition. The coating material according to one embodiment of the present invention can be used to provide a coating film having excellent load resistance and wear resistance due to the above configuration.
[0370] The coating material according to one embodiment of the present invention is also simply referred to as the present coating material.
[0371] The coating material may be, for example, in the following form: it contains an organic solvent and the first powder and particles, and the polymer particles (A) are dispersed in the organic solvent in the form of primary particles. The coating material may also be, for example, in the following form: it contains an organic solvent and the present resin composition, and the polymer particles (A) are dispersed in the organic solvent in the form of primary particles. In the past, it was very difficult to disperse the polymer particles (A) in the form of primary particles in an organic solvent. However, the first powder and particles have the advantage of being able to be used to provide a coating material in which the polymer particles (A) are more uniformly dispersed in an organic solvent. The first powder and particles may be powder and particles for coating materials.
[0372] When the coating material is applied to, for example, a floor or corridor, a generally used construction method can be applied. For example, a primer can be applied to the substrate after the surface is cleaned, and then the coating material can be evenly applied using a trowel, roller, rake, spray gun, etc. according to the construction conditions. After the coating material is applied, curing is completed to obtain a paving film with good performance. The coating film obtained by curing the coating material can become a coating film with excellent load resistance and wear resistance.
[0373] The viscosity of the resin composition used in the coating can be adjusted according to the construction method of the coating. For example, if a trowel or a rake is used in the construction of the coating, the viscosity of the resin composition used in the coating can generally be adjusted to approximately 500 to 9000 cps / 25°C. If a roller or a spray is used in the construction of the coating, the viscosity of the resin composition used in the coating can generally be adjusted to approximately 100 to 3000 cps / 25°C.
[0374] The substrate to which the coating is applied (in other words, the material of the floor or corridor) is not particularly limited. Specific examples of the substrate include: (a) inorganic substrates such as concrete walls, concrete slabs, concrete blocks, CMU (Concrete Masonry Unit), mortar boards, ALC (Autoclaved Light-weight Concrete) boards, gypsum boards (Dens Glass Gold manufactured by Georgia Pacific, etc.), and stone slabs; (b) organic substrates such as wooden substrates (wood, plywood, OSB (Oriented Strand Board), etc.), asphalt, modified asphalt waterproof sheets, ethylene-propylene-diene rubber (EPDM) waterproof sheets, TPO waterproof sheets, plastics, FRP, polyurethane foam insulation materials; and (c) metal substrates such as metal panels; etc.
[0375] The situation when this coating material is applied to a metal substrate or a porous substrate is described. In the laminate obtained by curing the coating material after the coating, the substrate can obtain excellent corrosion resistance. In addition, the coating film obtained by curing the coating material after the coating can give excellent crack resistance and load resistance to the substrate. Therefore, this mode of applying this coating material to a metal substrate or a porous substrate is an especially preferred scheme.
[0376] The coating material may be applied by any known coating method, such as a trowel, a rake, a brush, a roller, an air spray, or an airless spray.
[0377] The application of the coating material is not particularly limited, and can be used, for example, for automobiles, electrical equipment, office machines, building materials, wood, floor coating, paving, strong corrosion protection, concrete corrosion protection, rooftop / roof waterproofing, rooftop / roof corrosion resistance, underground waterproofing film waterproofing materials, automobile repair, tank coating, surface coating, middle layer coating, inner layer coating, primer, electroplating coating, high weather resistance coating, non-yellowing coating, etc. If it is used as a coating material for floor coating and paving coating, it can be used in factories, laboratories, warehouses, and clean rooms.
[0378] The present coating material can be produced using the first powder or granular material or the resin composition. The method for producing the present coating material is not particularly limited, and a known method can be used.
[0379] (I-6-4. Diaphragm)
[0380] The film sheet according to one embodiment of the present invention includes the first powder or granular material or the resin composition. The film according to one embodiment of the present invention has excellent load resistance and wear resistance due to the above configuration.
[0381] The film according to one embodiment of the present invention is also simply referred to as this film sheet.
[0382] The present diaphragm is, for example, a product obtained by volatilizing an organic solvent from a doping liquid containing an organic solvent and the first powder and particle. The present diaphragm may also be, for example, a product obtained by volatilizing an organic solvent from a doping liquid containing an organic solvent and the present resin composition. With respect to these doping liquids, polymer particles (A) are dispersed in the organic solvent in the form of primary particles. In the past, it was very difficult to disperse polymer particles (A) in the form of primary particles in an organic solvent. However, the first powder and particle has the advantage of being able to provide a doping liquid in which the polymer particles (A) are more evenly dispersed in an organic solvent, and therefore has the advantage of being able to provide a film in which the polymer particles (A) are more evenly dispersed. The first powder and particle may be a powder and particle for a diaphragm.
[0383] The use of the film is not particularly limited, and the film can be used for optical films such as polarizing plate protective films, decorative films, conductive films, electromagnetic wave absorbing sheets, antireflection films, and the like.
[0384] The present film can be produced using the first powder or granular material or the resin composition. The method for producing the present film is not particularly limited, and a known method can be used.
[0385] (I-6-5. Composite materials)
[0386] The composite material according to one embodiment of the present invention includes the first powder or granular material or the resin composition as a binder for reinforcing fibers. The composite material according to one embodiment of the present invention has the advantages of excellent toughness and impact resistance due to the above configuration.
[0387] The composite material according to one embodiment of the present invention is also simply referred to as the present composite material.
[0388] This composite material can include reinforcing fibers. As the reinforcing fibers, there is no particular limitation, and glass fibers, long glass fibers, carbon fibers, natural fibers, metal fibers, thermoplastic resin fibers, boron fibers, aramid fibers, polyethylene fibers, and spunbond reinforcing fibers can be cited. Among these reinforcing fibers, glass fibers and carbon fibers are particularly preferred.
[0389] The manufacturing method (molding method) of the present composite material is not particularly limited, but examples include an autoclave molding method using prepreg, a filament winding molding method, a hand lay-up molding method, a vacuum bag molding method, a resin injection molding (RTM) method, a vacuum assisted resin injection molding (VARTM) method, a wire drawing method, an injection molding method, a sheet winding molding method, a spraying method, a BMC (Bulk Molding Compound) method, an SMC (Sheet Molding Compound) method, and the like.
[0390] Especially when carbon fiber is used as reinforcing fiber, the manufacturing method of the present composite material is preferably: high pressure autoclave molding method using prepreg, filament winding molding method, manual lay-up molding method, vacuum bag molding method, resin injection molding (RTM) method, vacuum assisted resin injection molding (VARTM) method, etc.
[0391] The use of the composite material is not particularly limited, and examples thereof include aircraft, spacecraft, automobiles, bicycles, ships, weapons, windmills, sporting goods, containers, building materials, waterproof materials, printed circuit boards, and electrical insulating materials.
[0392] The composite material can be manufactured using the first powder or the resin composition. For more details about the reinforcing fiber, manufacturing method (molding method), manufacturing conditions (molding conditions), compounding agent, and use related to the composite material, there can be cited U.S. Patent Application Publication No. 2006 / 0173128, U.S. Patent Application Publication No. 2012 / 0245286, Japanese Patent Publication No. 2002-530445 (International Publication No. WO2000 / 029459 of the same family), and Japanese Patent Publication No. 55-157620. The contents described in the Japanese Patent Application Publication No. 2003-220661 (U.S. Patent No. 4251428 of the same family), Japanese Patent Publication No. 2013-504007 (International Publication No. WO2011 / 028271 of the same family), Japanese Patent Application Publication No. 2007-125889 (U.S. Patent Application Publication No. 2007 / 0098997 of the same family), and Japanese Patent Application Publication No. 2003-220661 (U.S. Patent Application Publication No. 2003 / 0134085 of the same family).
[0393] (I-6-6.3D printing materials)
[0394] The 3D printing molding material according to one embodiment of the present invention includes the first powder or resin composition. The 3D printing molding material according to one embodiment of the present invention has the advantages of excellent toughness and impact resistance due to the above-mentioned solution.
[0395] The 3D printing modeling material involved in one embodiment of the present invention is also referred to as the modeling material for short.
[0396] The use of the modeling material is not particularly limited, but examples thereof include prototypes for the purpose of appearance verification and function verification before actual production of products, aircraft parts, building components, and medical equipment parts.
[0397] The present modeling material can be produced using the first powder or granular material or the resin composition. The method for producing the present modeling material is not particularly limited, and a known method can be used.
[0398] (I-6-7. Sealant)
[0399] The sealant according to one embodiment of the present invention uses the first powder or granular material or the resin composition. The sealant according to one embodiment of the present invention has the advantages of excellent toughness and impact resistance due to the above configuration.
[0400] The sealant according to one embodiment of the present invention is also simply referred to as the present sealant.
[0401] The use of the present sealing agent is not particularly limited, but examples thereof include sealing of various electrical devices such as semiconductors and power devices.
[0402] The present sealant can be produced using the first powder or granular material or the resin composition. The method for producing the present sealant is not particularly limited, and a known method can be used.
[0403] [II. Second embodiment]
[0404] Similar to the first embodiment of the present invention, the second embodiment is also studied in view of the problem of dispersibility of polymer particles in resin existing in the prior art such as the above-mentioned Patent Documents 1 to 3. That is, the purpose of the second embodiment of the present invention is similar to the first embodiment, and is to provide a new powder or granule having excellent dispersibility of polymer particles in a matrix resin and a method for producing the powder or granule.
[0405] The present inventors have repeatedly conducted in-depth studies from another perspective to solve the above-mentioned problems. As a result, the present inventors have found that by mixing an aqueous latex of polymer particles with an aqueous latex of a resin to form a mixed liquid containing a specific amount of droplets having a specific volume average particle size, a powder with excellent dispersibility of polymer particles in a matrix resin can be provided, thereby completing the invention related to another embodiment (second embodiment) of the present invention.
[0406] That is, a method for producing a powder or granule according to another embodiment of the present invention comprises: a mixing step of mixing an aqueous latex (A) containing polymer microparticles (A) and an aqueous latex (B) containing a resin (B); and a preparation step of preparing a powder or granule containing the polymer microparticles (A) and the resin (B) using the mixed solution obtained by the mixing step, wherein the polymer microparticles (A) comprise a rubber-containing graft copolymer, the rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastomer comprising one or more rubbers selected from a diene rubber, a (meth)acrylate rubber and an organosiloxane rubber, and the graft portion comprising a polymer having a specific structural unit derived from an aromatic vinyl monomer, a vinyl cyanide monomer and ( The invention relates to a method for preparing an aqueous latex (B) comprising: preparing an aqueous latex (B) and a mixture of at least one monomer selected from the group consisting of meth) acrylic acid ester monomers, wherein the resin (B) is a liquid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., or is a semisolid or solid. The powder or granule comprises: 50 to 99 wt % of the polymer particles (A) and 1 to 50 wt % of the resin (B) in a total of 100 wt % of the polymer particles (A) and the resin (B), and when the volume average particle size of droplets in the aqueous latex (B) is x (μm) and the standard deviation of the volume average particle size is σ, the mixed solution contains: 0.0 wt % to 14.0 wt % of droplets having a volume average particle size of not less than x-σ and not more than x+5σ relative to 100 wt % of the resin (B) in the mixed solution.
[0407] In addition, a powder or granule according to another embodiment of the present invention is a powder or granule containing polymer microparticles (A) and a resin (B), wherein the polymer microparticles (A) include a rubber-containing graft copolymer, the rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastomer including one or more rubbers selected from diene rubber, (meth)acrylate rubber, and organosiloxane rubber, and the graft portion includes a polymer having a specific structural unit derived from one or more monomers selected from an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer. , the resin (B) is a liquid having a viscosity of 100mPa·s to 1000000mPa·s at 25°C, or is a semisolid or solid, the powder and granules contain: 50 to 99 weight % of the polymer particles (A) and 1 to 50 weight % of the resin (B) in a total of 100 weight % of the polymer particles (A) and the resin (B), wherein when the resin composition obtained by mixing the powder and granules with the matrix resin (C) is stirred under the following stirring conditions, the stirring time from the start of stirring to the reaching of a good dispersibility state is 80 minutes or less. Here, the stirring conditions are: using a disperser with a blade diameter of 32mm as a stirring device, and the rotation speed is 3000rpm. The "good dispersibility" means that when the resin composition is placed on a particle size meter and the resin composition on the measuring disk is scraped flat with a metal scraper to visually confirm the dispersion state, the state of granular marks with an average particle size of more than 10 μm caused by the movement of the scraper is manifested as 5 to 10 points in a 3 mm wide measuring band corresponding to 0 μm.
[0408] According to another embodiment of the present invention, a powder or granule having excellent dispersibility of polymer microparticles in a matrix resin can be provided.
[0409] Another embodiment (second embodiment) of the present invention is described below, but the present invention is not limited to these examples. Regarding each scheme of another embodiment (second embodiment) of the present invention, in addition to the scheme described in detail below, the other can appropriately cite the description in the first embodiment.
[0410] [II-1. Method for producing powder or granule]
[0411] The method for producing a powder or granule according to another embodiment of the present invention comprises: a mixing step of mixing an aqueous latex (A) containing polymer microparticles (A) with an aqueous latex (B) containing a resin (B), and a preparation step of preparing a powder or granule containing the polymer microparticles (A) and the resin (B) using the mixed solution obtained by the mixing step. The polymer microparticles (A) include a rubber-containing graft copolymer, and the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer. The elastomer includes one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber. The graft portion includes a polymer having a specific structural unit, and the specific structural unit is derived from one or more monomers selected from aromatic vinyl monomers, vinyl cyanide monomers and (meth)acrylate monomers. The resin (B) is a liquid having a viscosity of 100 mPa·s to 1000000 mPa·s at 25°C, or is a semisolid or solid. The powder and granules include: 50 to 99 wt% of the polymer particles (A) and 1 to 50 wt% of the resin (B) in a total of 100 wt% of the polymer particles (A) and the resin (B). When the volume average particle size of the droplets in the aqueous latex (B) is x (μm) and the standard deviation of the volume average particle size is σ, the mixed liquid contains: 0.0 wt% to 14.0 wt% of droplets with a volume average particle size of not less than x-σ and not more than x+5σ relative to 100 wt% of the resin (B) in the mixed liquid.
[0412] Hereinafter, the “method for producing a powder or granule according to another embodiment (second embodiment) of the present invention” may be referred to as the “second production method.” The powder or granule obtained by the second production method is mixed with a matrix resin (C) described later to form a resin composition.
[0413] The second production method has the above-mentioned configuration and has the following advantages: it can be used to provide a powdery granule having excellent dispersibility of the polymer microparticles (A) in the matrix resin. The second production method has the above-mentioned configuration and has the following advantages: the powdery granule obtained by the second production method can be mixed with the matrix resin (C) described later to realize a resin composition in which the polymer microparticles (A) are uniformly dispersed in the matrix resin (C).
[0414] (II-1-1. Polymer microparticles (A))
[0415] The polymer particles (A) of the second embodiment may be the same as the polymer particles (A) of the first embodiment. For example, the polymer particles (A) of the second embodiment include a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer.
[0416] (II-1-1-1. Elastomer)
[0417] (Volume average particle size of elastomer)
[0418] In the second embodiment, the volume average particle size of the elastomer is preferably 0.03 μm to 50.00 μm, more preferably 0.05 μm to 10.00 μm, more preferably 0.08 μm to 2.00 μm, more preferably 0.09 μm to 1.00 μm, more preferably 0.09 μm to 0.80 μm, more preferably 0.09 μm to 0.50 μm, further preferably 0.09 μm to 0.23 μm, and particularly preferably 0.10 μm to 0.23 μm. If the volume average particle size of the elastomer (a) is 0.03 μm or more, an elastomer having a desired volume average particle size can be stably obtained, and if (b) is 50.00 μm or less, the heat resistance and impact resistance of the obtained cured product or molded product become good.
[0419] (Volume Average Particle Size (Mv) of Polymer Microparticles (A))
[0420] In the second embodiment, from the viewpoint of obtaining a resin composition having a desired viscosity and being highly stable, the volume average particle size (Mv) of the polymer microparticles (A) is preferably 0.03 μm to 50.00 μm, more preferably 0.05 μm to 10.00 μm, more preferably 0.08 μm to 2.00 μm, more preferably 0.09 μm to 1.00 μm, more preferably 0.09 μm to 0.80 μm, more preferably 0.09 μm to 0.50 μm, further preferably 0.09 μm to 0.23 μm, and particularly preferably 0.10 μm to 0.23 μm. In addition, when the volume average particle size (Mv) of the polymer microparticles (A) is within this range, there is also an advantage that the dispersibility of the polymer microparticles (A) in the matrix resin (C) is good. In addition, the larger the volume average particle size (Mv) of the polymer microparticles (A), the smaller the cohesive force of the polymer microparticles (A).
[0421] (II-1-2. Mixing step)
[0422] In the mixing step, the aqueous latex (A) containing the polymer microparticles (A) and the aqueous latex (B) containing the resin (B) are mixed. Thus, in the mixing step, a mixed solution containing the polymer microparticles (A) and the resin (B) can be obtained. The mixing step can also be referred to as a step of preparing a mixed solution containing the polymer microparticles (A) and the resin (B).
[0423] In the aqueous latex (A), the polymer particles (A) exist in the form of one or more droplets containing the polymer particles (A) (hereinafter also referred to as droplets (A)) due to the action of an emulsifier, etc. In the aqueous latex (B), the resin (B) exists in the form of one or more droplets containing the resin (B) (hereinafter also referred to as droplets (B)) due to the action of an emulsifier, etc. Therefore, the mixing step can also be referred to as a step of mixing one or more droplets containing the polymer particles (A) with one or more droplets containing the resin (B). The mixed liquid obtained by the mixing step contains: droplets of 0.0% by weight to 14.0% by weight relative to 100% by weight of the resin (B) in the mixed liquid, and a volume average particle size of greater than x-σ and less than x+5σ. This scheme is described in detail below.
[0424] The inventors of the present invention have reached the following unique insights during the process of conducting in-depth research on the above-mentioned subject: In order to obtain a powder with excellent dispersibility of polymer microparticles (A) in the matrix resin (C), it is important to achieve integration of droplets (A) and droplets (B) in the above-mentioned mixed liquid. By integrating droplets (A) and droplets (B), droplets (B) can disappear. Therefore, in the mixed liquid, the less the content of droplets having the same volume average particle size as droplets (B) relative to the amount of droplets (B) added, it is considered that the integration of droplets (A) and droplets (B) can be achieved in the mixed liquid. The amount of droplets (B) added can also be referred to as the content of droplets (B) in the aqueous latex (B) used during mixing. That is, in the mixed liquid, the smaller the content of droplets having a volume average particle size of greater than x-σ and less than x+5σ relative to 100 weight % of the resin (B) in the mixed liquid, the more integration of droplets (A) and droplets (B) in the mixed liquid is considered to be possible.
[0425] In the mixed liquid, the lower limit of the content of droplets having a volume average particle size of not less than x-σ and not more than x+5σ is preferably 0.0 wt % with respect to 100 wt % of the resin (B) in the mixed liquid. In the mixed liquid, the upper limit of the content of droplets having a volume average particle size of not less than x-σ and not more than x+5σ relative to 100% by weight of the resin (B) in the mixed liquid is preferably 13.5% by weight, and the content is more preferably 13.0% by weight or less, more preferably 12.5% by weight or less, more preferably 12.0% by weight or less, more preferably 11.5% by weight or less, more preferably 11.0% by weight or less, more preferably 10.5% by weight or less, more preferably 10.0% by weight or less, more preferably 9.5% by weight or less, more preferably 9.0% by weight or less, more preferably 8.5% by weight or less, more preferably 8.0% by weight or less, more preferably 7.5% by weight or less, more preferably 7.0% by weight or less, more preferably 6.5% by weight or less, more preferably 6.0% by weight or less, more preferably 5.5% by weight or less, and particularly preferably 5.0% by weight or less. In addition, in the mixed liquid, the content of droplets with a volume average particle size of at least x-σ and at most x+5σ relative to 100% by weight of the resin (B) in the mixed liquid is 0.0% by weight or more, which means that the mixed liquid does not contain the droplets or the mixed liquid contains more than 0.0% by weight of the droplets. Therefore, the mixed liquid obtained by the mixing step can also be said to contain no droplets with a volume average particle size of at least x-σ and at most x+5σ, or to contain more than 0.0% by weight and less than 14.0% by weight of the droplets relative to 100% by weight of the resin (B) in the mixed liquid.
[0426] The method of integrating droplets (A) and (B) is not particularly limited. As a method of integrating droplets (A) and (B), for example, there is the following method (hereinafter also referred to as method A): droplet (B) is dispersed into several droplets smaller than droplet (B). In other words, droplet (B) is micronized and dispersed into droplet (A) and captured by droplet (A). When method A is adopted, it is speculated that by adjusting the stability of droplet (B) to a degree that droplet (B) can be dispersed into several droplets smaller than droplet (B), (i) integration of droplet (A) and droplet (B), and (ii) dispersion and micronization of droplet (B) can be promoted. However, another embodiment of the present invention is not limited to this speculation and method A.
[0427] In the second manufacturing method, for example, the integration of (i) droplets (A) and droplets (B) and (ii) dispersion and miniaturization of droplets (B) in the mixed liquid can be promoted by adjusting the following matters (a) to (c): (a) the volume average particle size of polymer particles (A); (b) the stability of droplets (A) in aqueous latex (A) containing polymer particles (A); and (c) the stability of droplets (B) in aqueous latex (B) containing resin (B).
[0428] The embodiment of the volume average particle size of the polymer microparticles (A) includes a preferred embodiment, and the embodiment described in the above-mentioned "(Volume average particle size (Mv) of polymer microparticles (A))" can be cited. In addition, the smaller the volume average particle size (Mv) of the polymer microparticles (A), the larger the surface area of the polymer microparticles (A) relative to the volume, and thus the integration of the droplets (A) and the droplets (B), for example, the degree of transfer of the droplets (B) to the droplets (A) can be enhanced.
[0429] The mixing step may include an aqueous latex (A) preparation step for preparing an aqueous latex (A) containing polymer particles (A). The aqueous latex (A) preparation step may also be referred to as a step for preparing polymer particles (A). In addition, the aqueous latex (A) preparation step may also be referred to as a step for adjusting the stability of droplets (A) in the aqueous latex (A) containing polymer particles (A).
[0430] The specific operation of the aqueous latex (A) preparation process is not particularly limited. For example, as described in the aforementioned "(2-1-5. Method for producing polymer particles (A))", polymer particles (A) can be produced by emulsion polymerization, suspension polymerization, microsuspension polymerization, etc., thereby preparing an aqueous latex (A) containing polymer particles (A). In the production of polymer particles (A), for example, the volume average particle size of droplets (A) in the aqueous latex (A) containing polymer particles (A) can be adjusted by adjusting the type and amount (blending amount) of the emulsifier. Moreover, in the production of polymer particles (A), for example, the stability of droplets (A) in the aqueous latex (A) containing polymer particles (A) can be adjusted by adjusting (i) the type and amount (blending amount) of the emulsifier, and (ii) the volume average particle size of the droplets (A).
[0431] The mixing step may include a step of preparing an aqueous latex (B) containing the resin (B). The step of preparing the aqueous latex (B) may also be referred to as a step of adjusting the stability of the droplets (B) in the aqueous latex (B) containing the resin (B).
[0432] The specific operation of the aqueous latex (B) preparation process is not particularly limited, and for example, water, resin (B) and emulsifier are mixed and stirred. In the aqueous latex (B) preparation process, the volume average particle size of the droplets (B) in the obtained aqueous latex (B) can be adjusted by adjusting the type and amount of the emulsifier used (dosage), the stirring speed and stirring time of the stirring, etc. In addition, in the aqueous latex (B) preparation process, the stability of the droplets (B) in the obtained aqueous latex (B) can be adjusted by adjusting (i) the type and amount of the emulsifier used (dosage), (ii) the stirring speed and stirring time of the stirring, and (iii) the volume average particle size of the droplets (B).
[0433] The amount of the emulsifier used in the step of preparing the aqueous latex (B) is not particularly limited. The amount of the emulsifier used in the step of preparing the aqueous latex (B) is preferably 1.0 to 30.0 parts by weight, more preferably 1.0 to 30.0 parts by weight, more preferably 1.5 to 30.0 parts by weight, more preferably 2.0 to 29.0 parts by weight, more preferably 2.5 to 28.0 parts by weight, more preferably 3.0 to 27.5 parts by weight, more preferably 3.5 to 27.0 parts by weight, more preferably 4.0 to 26.5 parts by weight, more preferably 4.5 to 26.0 parts by weight, more preferably 5.0 to 25.5 parts by weight, more preferably 5.5 to 25.0 parts by weight, further preferably 6.0 to 24.5 parts by weight, and particularly preferably 6.5 to 24.0 parts by weight.
[0434] The emulsifier is not particularly limited, and examples thereof include: (a) anionic emulsifiers such as the acids exemplified below, alkali metal salts of the acids, or ammonium salts of the acids; (b) nonionic emulsifiers; (c) polyvinyl alcohol, alkyl-substituted cellulose, polyvinyl pyrrolidone, polyacrylic acid derivatives, and the like. Examples of the acids include: (a1) alkyl or aryl sulfonic acid, alkyl ether, or aryl ether sulfonic acid; (a2) alkyl or aryl sulfuric acid, alkyl ether, or aryl ether sulfuric acid; (a3) alkyl or aryl substituted phosphoric acid, alkyl ether, or aryl ether substituted phosphoric acid; (a4) N-alkyl or aryl sarcosine; (a5) alkyl or aryl carboxylic acid, alkyl ether, or aryl ether carboxylic acid, and the like. Specific examples of emulsifiers include sodium dodecylbenzene sulfonate and sodium polyoxyethylene lauryl ether phosphate. By using polyoxyethylene lauryl ether phosphoric acid and sodium hydroxide in combination, the resulting sodium polyoxyethylene lauryl ether phosphate can be used as an emulsifier.
[0435] The stirring speed in the aqueous latex (B) preparation step is not particularly limited. The stirring speed is preferably 1000 rpm to 50000 rpm, more preferably 2000 rpm to 45000 rpm, more preferably 3000 rpm to 40000 rpm, more preferably 4000 rpm to 35000 rpm, more preferably 5000 rpm to 30000 rpm, more preferably 6000 rpm to 25000 rpm, further preferably 7000 rpm to 20000 rpm, and particularly preferably 8000 rpm to 12000 rpm.
[0436] The stirring time in the step of preparing the aqueous latex (B) is not particularly limited, but is preferably 1 to 10 minutes, more preferably 2 to 9 minutes, further preferably 3 to 7 minutes, and particularly preferably 4 to 6 minutes.
[0437] (II-1-3. Preparation process)
[0438] The preparation step may also be referred to as a step of obtaining a powder containing polymer microparticles (A) and resin (B). In the preparation step, the specific step (operation) for obtaining the powder is not particularly limited. The preparation step may further include a coagulation step of preparing a coagulation containing polymer microparticles (A) and resin (B) using the mixed solution.
[0439] The coagulation step is not particularly limited as long as coagulations containing polymer particles (A) and resin (B) can be obtained. The method for coagulating the polymer particles (A) and the resin (B) in the mixed solution is not particularly limited. Examples of the method include known methods such as a method using a coagulant, a method using a solvent, and a method of spraying an aqueous latex. Here, the mixture containing coagulations containing polymer particles (A) and resin (B) and an aqueous solvent obtained by coagulating the polymer particles (A) and the resin (B) in the mixed solution is also referred to as a slurry.
[0440] The aggregation of the polymer fine particles (A) and the resin (B) in the mixed solution is preferably carried out in the presence of an anti-blocking agent, thereby improving the anti-blocking property and improving the dispersibility of the polymer fine particles (A) in the matrix resin (C).
[0441] The preparation step may include a recovery step of recovering agglomerates containing the polymer fine particles (A) and the resin (B) (for example, agglomerates obtained in the agglomeration step) from the slurry.
[0442] The recovery step is not particularly limited as long as the aqueous solvent in the slurry can be separated from the aggregates, and a known method can be used. Examples of the recovery step include a method of filtering the slurry and a method of centrifugally dehydrating the slurry.
[0443] The preparation process may also include a washing step of washing the agglomerates containing the polymer microparticles (A) and the resin (B) (for example, the agglomerates obtained in the agglomeration step or the recovery step). If the preparation process further includes a washing step, a powder with a small content of inclusions and the like can be obtained. In the washing step, it is more preferred to wash the agglomerates with water, and it is further preferred to wash with ion exchange water or pure water.
[0444] The washing process is not particularly limited to a specific method as long as it is a process for washing the agglomerates. As a specific method of the washing process, for example, a method of mixing the agglomerates with water and stirring them with a stirrer, a method of kneading the agglomerates with water using a kneader, a method of mixing the agglomerates with water using a planetary mixer, a method of spraying water onto the agglomerates, a method of washing the filter cake using a pressure filter, etc. As a kneading machine, various equipment such as a batch kneading machine, a continuous kneading machine, an extrusion kneading machine, and an extruder can be used.
[0445] The washing time is not particularly limited, and for example, 1 second to 60 minutes can be cited. The washing time is preferably 1 second to 45 minutes, more preferably 1 second to 30 minutes, more preferably 1 minute to 30 minutes, further preferably 3 minutes to 30 minutes, particularly preferably 5 minutes to 30 minutes, and particularly preferably 10 minutes to 30 minutes.
[0446] The number of washing is not particularly limited, and for example, 1 to 10 times (cycles) can be cited. The number of washing is preferably 1 to 6 times (cycles), more preferably 1 to 5 times (cycles), further preferably 1 to 4 times (cycles), and most preferably 1 to 3 times (cycles).
[0447] The amount of washing water is not particularly limited, and for example, it can be 0.1 to 1000 parts by weight relative to 1 part by weight of the agglomerate. The amount of washing water is preferably 1 to 1000 parts by weight, more preferably 1 to 500 parts by weight, more preferably 1 to 200 parts by weight, more preferably 10 to 200 parts by weight, further preferably 15 to 200 parts by weight, and particularly preferably 20 to 200 parts by weight. The amount of washing water is also preferably 1 to 10 parts by weight, preferably 2 to 10 parts by weight, and preferably 2 to 5 parts by weight relative to 1 part by weight of the agglomerate. In addition, if the agglomerate is kneaded with water for washing using a kneader, less washing water can be used, so it is more preferred.
[0448] The temperature of the washing water is also not limited. For example, normal temperature washing water or heated warm washing water can be appropriately used. Since warm washing water has a high washing effect, it is preferred to use heated washing water. The temperature of the washing water can be, for example, 10°C to 100°C, preferably 15°C to 100°C, more preferably 20°C to 100°C, more preferably 40°C to 100°C, more preferably 40°C to 90°C, further preferably 40°C to 85°C, further preferably 40°C to 80°C, and particularly preferably 40°C to 70°C.
[0449] There is no limitation on the method for removing the washing wastewater in the washing process, and examples thereof include drying of the washing water, vacuum filtration, oil-water separation, filter pressing, centrifugation, belt pressing, screw pressing, membrane separation, and squeeze dehydration.
[0450] The object to be washed is not particularly limited to various impurities contained in the aggregate, and includes, for example, not only impurities derived from emulsifiers (such as phosphorus emulsifiers and sulfonic acid emulsifiers), but also impurities derived from coagulants when coagulants are used.
[0451] The preparation process may also include a drying process of drying the agglomerates containing polymer particles (A) and resin (B) (for example, the agglomerates obtained in the agglomeration process, the recovery process or the washing process). The drying process is not particularly limited as long as the agglomerates containing polymer particles (A) and resin (B) can be dried. The method of drying the agglomerates is not particularly limited, and examples thereof include a method of drying the agglomerates using a dryer, a method of loading the agglomerates into a container and heating the inside of the container under reduced pressure, a method of loading the agglomerates into a container and bringing a dry gas into countercurrent contact with the agglomerates in the container, and the like.
[0452] The drying temperature in the drying process is not particularly limited, for example, the temperature in the dryer or the temperature of the drying gas. The drying temperature in the drying process is, for example, preferably lower than 90°C, more preferably lower than 80°C, more preferably lower than 70°C, more preferably lower than 60°C, more preferably lower than 50°C, and further preferably lower than 40°C.
[0453] The preparation process preferably includes a coagulation step, a recovery step, and a drying step, and more preferably includes a coagulation step, a recovery step, a washing step, and a drying step.
[0454] As another embodiment of the production process, there is also a method of spray-drying a mixed solution containing the polymer fine particles (A) and the resin (B).
[0455] (II-1-3. Temperature)
[0456] In the second manufacturing method, the exposure time (period) of the aggregate and granular body containing polymer microparticles (A) and resin (B) to a temperature environment above the glass transition temperature of the grafted part of the polymer microparticles (A) can be shortened by adjusting the following temperatures: the temperature of the aqueous latex (A) containing polymer microparticles (A); the temperature of the aqueous latex (B) containing resin (B); the temperature of the mixed solution (before solidification); the temperature of the aqueous solution of the coagulant; the temperature of the aqueous latex containing polymer microparticles (A), resin (B) and coagulant; the heating temperature in the heating process; the drying temperature in the drying process; the temperature of the washing water in the washing process, etc.
[0457] 〔II-2. Powder and granular body〕
[0458] The powder and granule involved in another embodiment of the present invention is a powder and granule containing polymer particles (A) and resin (B). The polymer particles (A) include a rubber-containing graft copolymer, which has an elastomer and a graft portion graft-bonded to the elastomer. The elastomer includes one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber. The graft portion includes a polymer having a specific structural unit, and the specific structural unit is derived from one or more monomers selected from aromatic vinyl monomers, vinyl cyanide monomers and (meth)acrylate monomers. The resin (B) is a liquid having a viscosity of 100mPa·s to 1000000mPa·s at 25°C, or is a semisolid or solid. The powder and granule includes: the polymer particles (A) accounting for 50 to 99 weight% and the resin (B) accounting for 1 to 50 weight% in the total of 100 weight% of the polymer particles (A) and the resin (B). When the resin composition obtained by mixing the powder and the matrix resin (C) is stirred under the following stirring conditions, the stirring time from the start of stirring to the reaching of a good dispersibility state is less than 80 minutes. Here, the stirring conditions are: using a disperser with a blade diameter of 32 mm as a stirring device, and the rotation speed is 3000 rpm. The "good dispersibility state" means that when the resin composition is placed on a particle size meter and the resin composition on the measuring disk is scraped flat with a metal scraper to visually confirm the dispersion state, the state of granular marks with an average particle size of more than 10 μm caused by the scraper movement is presented as 5 to 10 points corresponding to 0 μm in the 3 mm wide measuring band.
[0459] Hereinafter, “the powder or granule according to another embodiment (second embodiment) of the present invention” may also be referred to as “the second powder or granule.” The second powder or granule is mixed with a matrix resin (C) described later to form a resin composition.
[0460] The second powder or granule has the above-mentioned configuration and has the advantage that the polymer fine particles (A) are excellently dispersed in the matrix resin (C). In other words, the second powder or granule has the following advantage: the second powder or granule is mixed with the matrix resin (C) described later to realize a resin composition in which the polymer fine particles (A) are uniformly dispersed in the matrix resin (C).
[0461] The various forms of the second powder and particle are described in detail below, but matters other than those described below (for example, the physical properties of the polymer particles (A), the resin (B) and the powder and particle, etc.) are not particularly limited and the descriptions in the aforementioned "〔I-2. Powder and particle〕" and "〔II-1. Method for producing powder and particle〕" items may be appropriately cited.
[0462] (II-2-1. Dispersibility)
[0463] Regarding the resin composition obtained by mixing the powder and the matrix resin (C), when the resin composition is stirred under specific stirring conditions, the stirring time from the start of stirring until the second powder reaches a well-dispersible state is 80 minutes or less.
[0464] As a disperser with a blade diameter of 32 mm used as a stirring device under specific stirring conditions, for example, a disperser manufactured by PRIMIX Co., Ltd. can be cited. When the resin composition is stirred, as a container for containing the resin composition, a container with a volume 1.5 to 3 times the volume of the resin composition, and a container with a ratio of the bottom diameter of the container to the height of the container (diameter: height) of 1:1 to 1:5 can be preferably used. When the resin composition is stirred, regarding the position of the stirring device in the container for containing the resin composition, for example, the center position of the blade (stirring wing) is located at a height of 0.5 cm to 3 cm from the bottom of the container.
[0465] The second powder or granule can be said to be a powder or granule in which the polymer fine particles (A) have better dispersibility in the matrix resin (C) as the stirring time is shorter. The stirring time of the second powder or granule is preferably 75 minutes or less, more preferably 70 minutes or less, more preferably 65 minutes or less, more preferably 60 minutes or less, more preferably 55 minutes or less, more preferably 50 minutes or less, further preferably 45 minutes or less, and particularly preferably 40 minutes or less.
[0466] (II-2-2. Method for producing powder or granule)
[0467] The method for producing the second powder or granule is not particularly limited. Examples of the method for producing the powder or granule include the following methods (a) and (b): (a) preparing an aqueous latex containing polymer particles (A) and a resin (B), then salting out the polymer particles (A) and the resin (B) in the aqueous latex, and dehydrating and drying the obtained agglomerates containing the polymer particles (A) and the resin (B); and (b) spray drying the aqueous latex containing the polymer particles (A).
[0468] The method for producing the second powder or granule is preferably the method described in the above-mentioned item “[II-1. Method for producing a powder or granule]”. In other words, the method described in the item “[II-1. Method for producing a powder or granule]” can easily provide the second powder or granule.
[0469] [II-3. Resin composition]
[0470] A resin composition containing a second powder or particle and a matrix resin (C) is another embodiment of the present invention. With regard to each form of the resin composition containing the second powder or particle, "the first powder or particle" can be appropriately replaced with "the second powder or particle", and the description in the item "[I-4. Resin composition]" can be appropriately cited.
[0471] [II-4. Cured product]
[0472] Regarding the resin composition according to another embodiment of the present invention described in the item “〔II-3. Resin composition〕”, a cured product obtained by curing the resin composition when the matrix resin (C) is a thermosetting resin is also another embodiment of the present invention.
[0473] The cured product according to another embodiment of the present invention has the above configuration and has (a) a beautiful surface, (b) high rigidity and high elastic modulus, and (c) excellent toughness and adhesiveness.
[0474] 〔II-5. Other uses〕
[0475] The powder or granule (second powder or granule) or resin composition according to another embodiment of the present invention can be used for various purposes, and the purposes are not particularly limited. Regarding the various uses of the second powder or granule or the resin composition containing the second powder or granule, the "first powder or granule" can be appropriately replaced with the "second powder or granule", and the description in the "〔I-6. Other uses〕" item can be appropriately cited.
[0476] In one embodiment of the present invention, the first manufacturing method described in the item "〔I-3. Manufacturing method of powder and granule〕" and the second manufacturing method described in the item "〔II-1. Manufacturing method of powder and granule〕" can be combined for implementation. In other words, a manufacturing method obtained by combining the first manufacturing method and the second manufacturing method can also be used to manufacture powder and granule. A powder and granule manufactured by a manufacturing method obtained by combining the first manufacturing method and the second manufacturing method is also one embodiment of the present invention.
[0477] The method of combining the first manufacturing method and the second manufacturing method is not particularly limited. The "manufacturing method combining the first manufacturing method and the second manufacturing method" is sometimes also referred to as a "third manufacturing method". The third manufacturing method is not particularly limited, but is preferably the following manufacturing method.
[0478] A method for producing a powder or granule, comprising:
[0479] a mixing step of mixing an aqueous latex (A) containing polymer microparticles (A) and an aqueous latex (B) containing a resin (B),
[0480] a coagulation step of preparing a coagulation body containing polymer microparticles (A) and resin (B) using the mixed solution obtained in the mixing step; and
[0481] The agglomerate is subjected to a drying process of airflow drying or freeze drying,
[0482] in,
[0483] When the volume average particle size of the droplets in the aqueous latex (B) is x (μm) and the standard deviation of the volume average particle size is σ, the mixed liquid contains: 0.0 wt% to 14.0 wt% of droplets having a volume average particle size of not less than x-σ and not more than x+5σ relative to 100 wt% of the resin (B) in the mixed liquid,
[0484] The polymer microparticles (A) include a rubber-containing graft copolymer, wherein the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer.
[0485] The elastomer comprises one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber,
[0486] The graft portion includes a polymer having a specific structural unit, and the specific structural unit is derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer.
[0487] The resin (B) is a liquid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., or is a semisolid or solid.
[0488] When the total amount of the polymer fine particles (A) and the resin (B) is 100% by weight, the polymer fine particles (A) are 50 to 99% by weight, and the resin (B) is 1 to 50% by weight.
[0489] The mixing step in the third manufacturing method can also be referred to as the step of preparing a mixed solution containing polymer particles (A) and resin (B). The mixing step in the third manufacturing method can also be the mixing step in the second manufacturing method. Therefore, for each scheme of the mixing step in the third manufacturing method, the records in the item "(II-1-2. Mixing step)" in the item "〔II-1. Method for producing powders and granules〕" can be appropriately cited. The mixing step in the third manufacturing method can also be referred to as the preparation step (a1) in the first manufacturing method. Therefore, for each scheme of the mixing step in the third manufacturing method, the records in the item "〔I-3. Method for producing powders and granules〕" can be appropriately cited.
[0490] The agglomeration step in the third production method may also be the agglomeration step in the first production method, and more specifically, may also be the agglomeration step (a2). Therefore, with respect to each embodiment of the agglomeration step in the third production method, the description of the agglomeration step (a2) in the item "(I-3-1. Agglomeration step)" in the item "〔I-3. Production method of powder and granule〕" may be appropriately cited.
[0491] The drying process in the third manufacturing method can also be the drying process in the first manufacturing method. Therefore, for each scheme of the agglomeration process in the third manufacturing method, the records of the drying process in the item "(I-3-3. Drying process)" in the item "〔I-3. Manufacturing method of powder and granular body〕" can be appropriately cited.
[0492] The step of combining the agglomeration step and the drying step in the third production method can also be said to be the preparation step in the second production method.
[0493] Regarding aspects other than the above in the third production method, the above description, for example, the description in the items “[I-3. Production method of powder or granule]” and “[II-1. Production method of powder or granule]” can be appropriately cited.
[0494] “Powder or granule obtained by a production method in which the first production method and the second production method are combined” may also be referred to as “third powder or granule.” The third production method is not particularly limited, but is preferably the following.
[0495] A powder containing polymer particles (A) and a resin (B),
[0496] The polymer microparticles (A) include a rubber-containing graft copolymer, wherein the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer.
[0497] The elastomer comprises one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber,
[0498] The graft portion includes a polymer having a specific structural unit, and the specific structural unit is derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer.
[0499] The resin (B) is a liquid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., or is a semisolid or solid.
[0500] When the total amount of the polymer fine particles (A) and the resin (B) is 100 wt %, the polymer fine particles (A) are 50 to 99 wt %, and the resin (B) is 1 to 50 wt %.
[0501] The powder or granular material has pores with an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is 0.0600 mL / g or more.
[0502] When the resin composition obtained by mixing the powder or granules with the matrix resin (C) is stirred under the following stirring conditions, the stirring time from the start of stirring until the dispersion reaches a good state is 80 minutes or less.
[0503] Regarding each aspect of the third powder or granule, the above description, for example, the description in the items "[I-2. Powder or granule]" and "[II-2. Powder or granule]" can be appropriately cited.
[0504] One embodiment of the present invention may be the following.
[0505] [X1] A powder and granule comprising polymer microparticles (A) and a resin (B), wherein the polymer microparticles (A) comprise a rubber-containing graft copolymer, the rubber-containing graft copolymer comprising an elastomer and a graft portion graft-bonded to the elastomer, the elastomer comprising at least one rubber selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber, the graft portion comprising a polymer having a specific structural unit derived from at least one monomer selected from an aromatic vinyl monomer, a vinyl cyanide monomer and a (meth)acrylate monomer, and the resin (B) having a A liquid with a viscosity of 100 mPa·s to 1000000 mPa·s, or a semisolid or solid, wherein, when the total amount of the polymer particles (A) and the resin (B) is set to 100 weight %, the polymer particles (A) are 50 to 99 weight %, the resin (B) is 1 to 50 weight %, the powder and granule have pores with an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is not less than 0.0600 mL / g, and among 100 weight % of the powder and granule, particles with a volume average particle diameter of not less than 1000 μm account for not more than 3.00 weight %.
[0506] [X2] The powder or granule according to [X1], wherein particles having a volume average particle size of 600 μm or more account for 6.00% by weight or less of 100% by weight of the powder or granule.
[0507] [X3] The powder or granule according to [X1] or [X2], wherein the powder or granule has pores with an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is 0.0800 mL / g or more.
[0508] [X4] The powder or granule according to any one of [X1] to [X3], wherein the powder or granule has pores having an average pore diameter of 0.03 μm to 4.50 μm, and the total volume of the pores is 0.1100 mL / g or more.
[0509] [X5] The powder or granule according to any one of [X1] to [X4], wherein the proportion of particles having a volume average particle size of 600 μm or more in 100 wt % of the powder or granule is 1.90 wt % or less.
[0510] [X6] A powder or particle according to any one of [X1] to [X5], wherein the force required to disintegrate the agglomerate of the powder or particle is 30,000 Pa or less, and the agglomerate is obtained by applying a load of 6.3 kg to the powder or particle by placing a 6.3 kg weight on 30 g of the powder or particle contained in a cylindrical container with a diameter of 50 mm and leaving it to stand at 60°C for 2 hours, and the force is a value measured by a rheometer.
[0511] [X7] The powder or granule according to any one of [X1] to [X6], wherein the volume average particle size of the polymer fine particles (A) is 0.23 μm or less.
[0512] [X8] The powder or granule according to any one of [X1] to [X7], wherein the volume average particle size of the polymer fine particles (A) is 0.09 μm or more.
[0513] [X9] A resin composition comprising the powder or granule according to any one of [X1] to [X8] and a matrix resin (C).
[0514] [X10] A method for producing a powder, comprising: a coagulation step of preparing an agglomerate containing polymer particles (A) and a resin (B), and a drying step of airflow drying or freeze drying the agglomerate, wherein the polymer particles (A) contain a rubber-containing graft copolymer, the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer, the elastomer contains one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosilicone rubber, and the graft portion contains A polymer having a specific structural unit, wherein the specific structural unit is derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer, wherein the resin (B) is a liquid, a semisolid, or a solid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., and when the total amount of the polymer microparticles (A) and the resin (B) is 100% by weight, the polymer microparticles (A) are 50 to 99% by weight, and the resin (B) are 1 to 50% by weight.
[0515] [X11] The method for producing a powder or particle according to [X10], wherein the agglomeration step further comprises a polymer fine particle spraying step of spraying an aqueous latex containing polymer fine particles (A) and a resin (B) in the presence of a coagulant.
[0516] [X12] The method for producing a powder or granule according to [X11], wherein the agglomeration step further comprises a coagulant spraying step of spraying the coagulant or a solution containing the coagulant in the presence of polymer particles (A) and resin (B).
[0517] [X13] The method for producing a powder or granule according to any one of [X10] to [X12], wherein the drying step is performed at a temperature of 100° C. or less.
[0518] [X14] A method for producing a powder or particle, comprising: a mixing step of mixing an aqueous latex (A) containing polymer particles (A) and an aqueous latex (B) containing a resin (B); and a preparation step of preparing a powder or particle containing the polymer particles (A) and the resin (B) using the mixed solution obtained by the mixing step, wherein the polymer particles (A) contain a rubber-containing graft copolymer, the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer, the elastomer contains one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosilicone rubber, and the graft portion contains a polymer having a specific structural unit, the specific structural unit being derived from an aromatic vinyl monomer, a vinyl cyanide monomer and a (meth)acrylate monomer. The present invention relates to a method for preparing an aqueous latex composition comprising: a first monomer selected from the group consisting of an aqueous latex and ...
[0519] [X15] A method for manufacturing a powder or particle according to any one of [X10] to [X14], wherein the force required to disintegrate the agglomerate of the powder or particle is 30,000 Pa or less, and the agglomerate is obtained by applying a load of 6.3 kg to the powder or particle by placing a 6.3 kg weight on 30 g of the powder or particle contained in a cylindrical container with a diameter of 50 mm and leaving it to stand at 60°C for 2 hours, and the force is a value measured by a rheometer.
[0520] [X16] The method for producing a powder or granule according to any one of [X10] to [X15], wherein the volume average particle size of the polymer fine particles (A) is 0.23 μm or less.
[0521] [X17] The method for producing a powder or granule according to any one of [X10] to [X16], wherein the volume average particle size of the polymer fine particles (A) is 0.09 μm or more.
[0522] [Y1] A powder and granule comprising polymer microparticles (A) and a resin (B), wherein the polymer microparticles (A) comprise a rubber-containing graft copolymer, the rubber-containing graft copolymer comprising an elastomer and a graft portion graft-bonded to the elastomer, the elastomer comprising at least one rubber selected from the group consisting of a diene rubber, a (meth)acrylate rubber and an organosiloxane rubber, the graft portion comprising a polymer having a specific structural unit derived from at least one of an aromatic vinyl monomer, a vinyl cyanide monomer and a (meth)acrylate monomer. More than one monomer, the resin (B) is a liquid having a viscosity of 100 mPa·s to 1000000 mPa·s at 25°C, or is a semisolid or solid, and when the total amount of the polymer particles (A) and the resin (B) is set to 100 weight %, the polymer particles (A) are 50 to 99 weight %, the resin (B) is 1 to 50 weight %, and the powder has pores with an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is 0.0600 mL / g or more.
[0523] [Y2] The powder or granule according to [Y1], wherein the proportion of particles having a volume average particle size of 1000 μm or more is 3.00% by weight or less in 100% by weight of the powder or granule.
[0524] [Y3] The powder or granule according to [Y1] or [Y2], wherein particles having a volume average particle size of 600 μm or more account for 6.00% by weight or less of 100% by weight of the powder or granule.
[0525] [Y4] The powder or granule according to any one of [Y1] to [Y3], wherein the powder or granule has pores having an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is 0.0800 mL / g or more.
[0526] [Y5] The powder or granule according to any one of [Y1] to [Y4], wherein the powder or granule has pores having an average pore diameter of 0.03 μm to 4.50 μm, and the total volume of the pores is 0.1100 mL / g or more.
[0527] [Y6] The powder or granule according to any one of [Y1] to [Y5], wherein the proportion of particles having a volume average particle size of 600 μm or more is 1.90% by weight or less in 100% by weight of the powder or granule.
[0528] [Y7] A powder or granular material according to any one of [Y1] to [Y6], wherein the force required to disintegrate the agglomerate of the powder or granular material is 30,000 Pa or less, and the agglomerate is obtained by applying a load of 6.3 kg to the powder or granular material by placing a 6.3 kg weight on 30 g of the powder or granular material contained in a cylindrical container with a diameter of 50 mm and leaving the container at 60°C for 2 hours, and the force is a value measured by a rheometer.
[0529] [Y8] A resin composition comprising the powder or granule according to any one of [Y1] to [Y7] and a matrix resin (C).
[0530] [Y9] A method for producing a powder or granule, comprising: a coagulation step of preparing an agglomerate containing polymer particles (A) and a resin (B), and a drying step of airflow drying or freeze drying the agglomerate, wherein the polymer particles (A) contain a rubber-containing graft copolymer, the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer, the elastomer contains one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosilicone rubber, and the graft portion contains A polymer having a specific structural unit, wherein the specific structural unit is derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer, wherein the resin (B) is a liquid, a semisolid, or a solid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., and when the total amount of the polymer microparticles (A) and the resin (B) is 100% by weight, the polymer microparticles (A) are 50 to 99% by weight, and the resin (B) are 1 to 50% by weight.
[0531] [Y10] The method for producing a powder or particle according to [Y9], wherein the agglomeration step further comprises a polymer fine particle spraying step of spraying an aqueous latex containing polymer fine particles (A) and a resin (B) in the presence of a coagulant.
[0532] [Y11] The method for producing a powder or granule according to [Y10], wherein the agglomeration step further comprises a coagulant spraying step of spraying the coagulant or a solution containing the coagulant in the presence of polymer fine particles (A) and the resin (B).
[0533] [Y12] The method for producing a powder or granule according to any one of [Y9] to [Y11], wherein the drying step is performed at a temperature of 100° C. or less.
[0534] [Y13] A method for manufacturing a powder or particle according to any one of [Y9] to [Y12], wherein the force required to disintegrate the agglomerate of the powder or particle is 30,000 Pa or less, and the agglomerate is obtained by applying a load of 6.3 kg to the powder or particle by placing a 6.3 kg weight on 30 g of the powder or particle contained in a cylindrical container with a diameter of 50 mm and leaving it to stand at 60°C for 2 hours, and the force is a value measured by a rheometer.
[0535] An embodiment of the present invention may also be as follows.
[0536] [Z1] A method for producing a powder or granule, comprising: a mixing step of mixing an aqueous latex (A) containing polymer microparticles (A) and an aqueous latex (B) containing a resin (B); and a preparation step of preparing a powder or granule containing the polymer microparticles (A) and the resin (B) using the mixed solution obtained by the mixing step, wherein the polymer microparticles (A) comprise a rubber-containing graft copolymer, the rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastomer comprising one or more rubbers selected from diene rubbers, (meth)acrylate rubbers and organosiloxane rubbers, and the graft portion comprising a polymer having a specific structural unit derived from an aromatic vinyl monomer, a vinyl cyanide monomer and a (meth)acrylate monomer. At least one monomer of an acrylate monomer, the resin (B) is a liquid having a viscosity of 100 mPa·s to 1000000 mPa·s at 25°C, or is a semisolid or solid, the powder or granule contains 50 to 99 wt % of the polymer particles (A) and 1 to 50 wt % of the resin (B) in a total of 100 wt % of the polymer particles (A) and the resin (B), and when the volume average particle size of the droplets in the aqueous latex (B) is set to x (μm) and the standard deviation of the volume average particle size is set to σ, the mixed solution contains: 0.0 wt % to 14.0 wt % of droplets with a volume average particle size of not less than x-σ and not more than x+5σ relative to 100 wt % of the resin (B) in the mixed solution.
[0537] [Z2] The method for producing a powder or particle according to [Z1], wherein the volume average particle size of the polymer fine particles (A) is 0.23 μm or less.
[0538] [Z3] The method for producing a powder or particle according to [Z1] or [Z2], wherein the volume average particle size of the polymer fine particles (A) is 0.09 μm or more.
[0539] [Z4] A method for producing a powder or particle according to any one of [Z1] to [Z3], wherein the force required to disintegrate the agglomerate of the powder or particle is 30,000 Pa or less: wherein the agglomerate is obtained by applying a load of 6.3 kg to the powder or particle by placing a 6.3 kg weight on 30 g of the powder or particle contained in a cylindrical container having a diameter of 50 mm and leaving the container at 60°C for 2 hours, and the force is a value measured by a rheometer.
[0540] [Z5] A powder or granule comprising polymer microparticles (A) and a resin (B), wherein the polymer microparticles (A) comprise a rubber-containing graft copolymer, the rubber-containing graft copolymer comprising an elastomer and a graft portion graft-bonded to the elastomer, the elastomer comprising one or more rubbers selected from diene rubber, (meth)acrylate rubber and organosiloxane rubber, the graft portion comprising a polymer having a specific structural unit, the specific structural unit being derived from one or more monomers selected from aromatic vinyl monomers, vinyl cyanide monomers and (meth)acrylate monomers, the resin (B) being a liquid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25°C, or being a semisolid or solid, the powder or granule comprising: When a resin composition obtained by mixing the powder and granule with a matrix resin (C) is stirred under the following stirring conditions, the stirring time from the start of stirring to the reaching of a good dispersibility state is 80 minutes or less, the stirring conditions are: using a disperser with a blade diameter of 32 mm as a stirring device, and the rotation speed is 3000 rpm, and the "good dispersibility state" means that when the resin composition is placed on a particle size meter and the resin composition on the measuring disk is scraped flat with a metal scraper to visually confirm the dispersion state, the state of granular marks with an average particle size of 10 μm or more caused by the scraper movement is presented as 5 to 10 points corresponding to 0 μm in a 3 mm wide measuring band.
[0541] [Z6] The powder or granule according to [Z5], wherein the volume average particle size of the polymer fine particles (A) is 0.23 μm or less.
[0542] [Z7] The powder or granule according to [Z5] or [Z6], wherein the volume average particle size of the polymer fine particles (A) is 0.09 μm or more.
[0543] [Z8] A powder or granular material according to any one of [Z5] to [Z7], wherein the force required to disintegrate the agglomerate of the powder or granular material is 30,000 Pa or less, and the agglomerate is obtained by applying a load of 6.3 kg to the powder or granular material by placing a 6.3 kg weight on 30 g of the powder or granular material contained in a cylindrical container with a diameter of 50 mm and leaving the container at 60°C for 2 hours, and the force is a value measured by a rheometer.
[0544] [Example]
[0545] [Example A]
[0546] Hereinafter, one embodiment of the present invention (the first embodiment) will be described in more detail according to Example A and Comparative Example A, but the present invention is not limited to these examples. One embodiment of the present invention can be implemented by appropriately changing within the scope of the aforementioned or later technical gist, and these changed embodiments are also included in the technical scope of the present invention. In addition, in the following Example A and Comparative Example A, "parts" and "%" refer to parts by weight or weight %.
[0547] <Ingredients>
[0548] The components used in each of Production Example A, Example A and Comparative Example A are as follows.
[0549] Polymer microparticles (A)
[0550] The polymer microparticles (A) obtained in Production Example A shown below were used.
[0551] Resin (B)
[0552] A mixture of 67 parts by weight of epoxidized soybean oil (ADK CIZER O-130P manufactured by ADEKA CORPORATION) and 33 parts by weight of triethylene glycol bis[3-(tert-butyl-4-hydroxy-5-methylphenyl)propionate (antioxidant; Irganox 245 manufactured by BASF JAPAN CORPORATION) was used.
[0553] Matrix resin (C)
[0554] A bisphenol A type epoxy resin (JER828 manufactured by Mitsubishi Chemical Corporation) was used.
[0555] <Evaluation Method>
[0556] First, the evaluation method of the resin compositions produced according to Example A and Comparative Example A will be described below.
[0557] (Measurement of volume average particle size)
[0558] The volume average particle size (Mv) of the elastomer or polymer microparticles (A) dispersed in the aqueous latex was measured using Nanotrac WaveII-EX150 (manufactured by Micro Track Bell Co., Ltd.). The aqueous latex diluted with deionized water was used as the measurement material. In the measurement, water and the refractive index of the elastomer or polymer microparticles (A) obtained in each manufacturing example A were input, the measurement time was set to 120 seconds, and the material concentration was adjusted to meet the range of the loading index 1 to 10.
[0559] The volume average particle size (Mv) of the powder or granule is measured using a laser diffraction particle size distribution measuring apparatus MICROTRAC MT3000II (manufactured by MICROTRAC BEL CO., LTD.).
[0560] (Measurement of the volume average particle size and content of droplets in the aqueous latex (B) or the mixed liquid)
[0561] The volume average particle size and content of droplets in the aqueous latex (B) containing the resin (B) or in the mixed solution containing the polymer particles (A) and the resin (B) are measured by using the aqueous latex (B) or the mixed solution as the material and using a laser diffraction particle size distribution measuring device. As the laser diffraction particle size distribution measuring device, MICROTRAC MT3000II (manufactured by MICROTRACBEL Co., Ltd.) is used.
[0562] (Differential Scanning Calorimetry (DSC) of Resin (B))
[0563] The resin (B) used was measured using DSC7020 (manufactured by Hitachi High-Tech Science Co., Ltd.) at a temperature increase rate of 10°C / min. As a result, the DSC thermogram of the resin (B) showed an endothermic peak at -16.9°C.
[0564] (Measurement of Viscosity of Resin (B))
[0565] The viscosity of the resin (B) used was measured using a digital viscometer DV-II+Pro manufactured by Brookfield, using a spindle CPE-52 that matches the viscosity range, at a measurement temperature of 25°C and by changing the shear rate as needed. As a result, the viscosity of the resin (B) was 11,000 mPa·s.
[0566] (Dispersibility of Powder and Particle in Matrix Resin (C))
[0567] 15 parts by weight (15 g) of the powder obtained from Example A and Comparative Example A, and 85 parts by weight (85 g) of bisphenol A epoxy resin as the matrix resin (C) were prepared. The prepared powder and bisphenol A epoxy resin were added to a container with a volume of 200 mL. The volume of the container is about twice the volume of the prepared powder and bisphenol A epoxy resin. Using a disperser with a stirring blade having a blade diameter of Φ32 mm (manufactured by PRIMIX Co., Ltd.), the powder and bisphenol A epoxy resin were mixed at a rotation speed of 3000 rpm to obtain a resin composition. The resin composition was placed on a particle size meter (particle size measuring disk), and the resin composition on the measuring disk was scraped flat with a metal scraper to visually confirm the dispersion state. The corresponding scale of the position where 5 to 10 granular marks caused by the scraper movement occurred in the 3 mm wide measuring tape was read, and the time until the corresponding scale finally became 0 μm was measured. The results are shown in Table 1.
[0568] (Pore of powder)
[0569] The powders and granules obtained in Example A and Comparative Example A were measured using an automatic mercury intrusion porosimeter pore distribution measuring device (manufactured by Shimadzu Corporation) at a pressure range of 20 psia to 3000 psia. Based on the obtained results, the total volume value of pores with an average pore diameter of 0.03 μm to 1.0 μm and the total volume value of pores with an average pore diameter of 0.03 μm to 4.5 μm were calculated respectively. The results are shown in Table 1.
[0570] (Anti-adhesion properties of powders and particles)
[0571] Using the powders obtained in Example A and Comparative Example A, the following operations (1) to (3) were performed in sequence to prepare a powder agglomerate: (1) 30 g of the powder was placed in a cylindrical container with a diameter of 50 mm; (2) a 6.3 kg weight was placed on the powder in the container and the powder was left to stand at 60° C. for 2 hours to apply a 6.3 kg load to the powder; (3) the obtained agglomerate was taken out of the container. Then, the force required to disintegrate the obtained powder agglomerate was measured using a rheometer. Based on the obtained results, the anti-blocking property was evaluated according to the following criteria.
[0572] Acceptable: The force required to disintegrate the agglomerates of the powder or granules is 30,000 Pa or less.
[0573] Unqualified: The force required to disintegrate the agglomerate of powder and particles exceeds 30,000 Pa.
[0574] <1. Preparation of polymer microparticles (A)>
[0575] (Production Example A)
[0576] (Manufacturing Example A1-1; Preparation of Aqueous Latex (L-A1) Containing Polymer Microparticles (A))
[0577] In a pressure polymerizer, 160 parts by weight of deionized water, 0.002 parts by weight of disodium ethylenediaminetetraacetate (EDTA), 0.001 parts by weight of ferrous sulfate 7-hydrate, 0.029 parts by weight of polyoxyethylene lauryl ether phosphate, and 0.003 parts by weight of sodium hydroxide are added. Here, polyoxyethylene lauryl ether phosphate becomes sodium polyoxyethylene lauryl ether phosphate in the presence of sodium hydroxide and functions as an emulsifier. Next, while stirring the added raw materials, the gas inside the pressure polymerizer is replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 76.5 parts by weight of butadiene (Bd) and 23.5 parts by weight of styrene (St) are added to the pressure polymerizer, and the temperature inside the pressure polymerizer is raised to 45°C. Thereafter, 0.03 parts by weight of menthane hydrogen peroxide (PHP) was added to the pressure-resistant polymerizer, and then 0.05 parts by weight of sodium formaldehyde sulfoxylate (SFS) was added to the pressure-resistant polymerizer to start polymerization. At 20 hours after the start of the polymerization, devolatilization was carried out under reduced pressure to remove the monomers remaining in the polymerization that were not used, thereby terminating the polymerization. Here, during the polymerization, PHP, polyoxyethylene lauryl ether phosphate and sodium hydroxide were added to the pressure-resistant polymerizer in any amount and at any time. Through this polymerization, an aqueous latex (R-A1) containing an elastomer (core layer) with polystyrene-butadiene rubber as the main component was obtained. The volume average particle size of the elastomer (core layer) contained in the obtained aqueous latex was 192 nm.
[0578] 215 parts by weight of aqueous latex (R-A1) of polystyrene-butadiene rubber (including 70 parts by weight of an elastomer with polystyrene-butadiene rubber as the main component) and 82 parts by weight of deionized water were added to a glass reactor. Here, the glass reactor has a thermometer, a stirrer, a reflux cooler, a nitrogen inlet, and a monomer addition device. The raw materials added at 60°C were stirred while replacing the gas in the glass reactor with nitrogen. Next, 2.6 parts by weight of 1,3-butylene di(methacrylate) and 0.07 parts by weight of tert-butyl hydroperoxide (BHP) were added to the glass reactor and stirred for 10 minutes. Thereafter, 0.004 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate 7-hydrate, and 0.13 parts by weight of SFS were added to the glass reactor and stirred for 30 minutes. Thereafter, 0.013 parts by weight of BHP was added to the glass reactor and further stirred for 30 minutes. Thereafter, a mixture of 28.5 parts by weight of methyl methacrylate (MMA), 1.5 parts by weight of butyl acrylate (BA) and 0.085 parts by weight of BHP was continuously added to the glass reactor over 120 minutes. Thereafter, 0.013 parts by weight of BHP was added to the glass reactor, and the mixture in the glass reactor was continuously stirred for 1 hour to complete the polymerization. Through the above operation, an aqueous latex (L-A1) containing polymer particles (A) was obtained. The polymerization conversion rate of its monomer components was more than 99%. The volume average particle size of the polymer particles (A) contained in the obtained aqueous latex was 200 nm.
[0579] (Manufacturing Example A1-2; Preparation of Aqueous Latex (L-A3) Containing Polymer Microparticles (A))
[0580] In the pressure polymerizer, 200 parts by weight of deionized water, 0.03 parts by weight of tripotassium phosphate, 0.002 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate 7-hydrate, and 1.55 parts by weight of sodium dodecylbenzene sulfonate (SDBS) as an emulsifier are added. Next, while stirring the added raw materials, the gas inside the pressure polymerizer is replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 100 parts by weight of Bd are added to the pressure polymerizer, and the temperature inside the pressure polymerizer is raised to 45°C. Thereafter, 0.03 parts by weight of PHP are added to the pressure polymerizer, and then 0.10 parts by weight of SFS are added to the pressure polymerizer to start polymerization. At 15 hours after the start of polymerization, devolatilization is carried out under reduced pressure to devolatilize and remove the monomers that are not used in the polymerization and remain, thereby ending the polymerization. Here, during the polymerization process, PHP, EDTA and ferrous sulfate 7 hydrate salt were added to the pressure-resistant polymerization vessel in any amount and at any time. Through the polymerization, an aqueous latex (R-A2) containing an elastomer with polybutadiene rubber as the main component was obtained. The volume average particle size of the elastomer contained in the obtained aqueous latex was 90 nm.
[0581] In the pressure polymerizer, an amount of polybutadiene rubber aqueous latex (R-A2) equivalent to 7 parts by weight of an elastomer with polybutadiene rubber as the main component, 200 parts by weight of deionized water, 0.03 parts by weight of tripotassium phosphate, 0.002 parts by weight of EDTA, and 0.001 parts by weight of ferrous sulfate 7 hydrate salt were added. Next, while stirring the added raw materials, the gas inside the pressure polymerizer was replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 93 parts by weight of Bd were added to the pressure polymerizer, and the temperature inside the pressure polymerizer was raised to 45°C. Thereafter, 0.02 parts by weight of PHP were added to the pressure polymerizer, and then 0.10 parts by weight of SFS were added to the pressure polymerizer to start polymerization. At 30 hours after the start of polymerization, devolatilization was carried out under reduced pressure to devolatilize and remove the monomers that were not used in the polymerization and remained, thereby ending the polymerization. Here, during the polymerization process, PHP, EDTA, and ferrous sulfate 7-hydrate salt were added to the pressure-resistant polymerization vessel in any amount and at any time. Through the polymerization, an aqueous latex (R-A3) containing an elastomer (core layer) with polybutadiene rubber as the main component was obtained. The volume average particle size of the elastomer (core layer) contained in the obtained aqueous latex was 195 nm.
[0582] In a glass reactor, 215 parts by weight of an aqueous latex of polybutadiene rubber (R-A3) (including 71 parts by weight of an elastomer with polybutadiene rubber as the main component) and 82 parts by weight of deionized water were added. Here, the glass reactor has a thermometer, a stirrer, a reflux cooler, a nitrogen inlet, and a monomer addition device. While replacing the gas in the glass reactor with nitrogen, the raw materials added at 60°C were stirred. Next, 2.6 parts by weight of 1,3-butylene di(methacrylate) ester and 0.07 parts by weight of BHP were added to the glass reactor and stirred for 10 minutes. Thereafter, 0.004 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate 7-hydrate, and 0.13 parts by weight of SFS were added to the glass reactor and stirred for 30 minutes. Thereafter, 0.013 parts by weight of BHP was added to the glass reactor and further stirred for 30 minutes. Thereafter, a mixture of 22 parts by weight of MMA, 7 parts by weight of St, and 0.085 parts by weight of BHP was continuously added to a glass reactor over a period of 70 minutes. Thereafter, 0.013 parts by weight of BHP was added to the glass reactor, and the mixture in the glass reactor was continuously stirred for 1 hour to complete the polymerization. Through the above operation, an aqueous latex (L-A3) containing polymer particles (A) was obtained. The polymerization conversion rate of its monomer components was more than 99%. The volume average particle size of the polymer particles (A) contained in the obtained aqueous latex was 200 nm.
[0583] <2. Preparation of powder and granules>
[0584] (Example A1: Preparation of Powder and Granule)
[0585] Water, resin (B), and SDBS as an emulsifier are mixed together using a homogenizer to prepare an aqueous emulsion (S-A1) (resin (B) content is 50%) in which the resin (B) is emulsified. Next, 325 parts by weight of an aqueous latex (L-A1) equivalent to 100 parts by weight of polymer particles (A) are mixed with 22.2 parts by weight of the aqueous emulsion (S-A1) (equivalent to 11.1 parts by weight of resin (B)) to prepare an aqueous latex (L-A2) containing polymer particles (A) and resin (B). The aqueous latex (L-A2) is sprayed into a container having a coagulable atmosphere formed inside (i.e., also referred to as a coagulation chamber) to obtain a slurry having a coagulant containing polymer particles (A) and resin (B). The coagulation atmosphere in the container is formed by the following steps: (1) in a cylindrical container with a height of 9 m and a diameter of 1.5 m, 46°C warm water is allowed to flow down along the inner wall surface from a side nozzle installed at the upper part of the inner wall of the container; (2) in parallel with step (1), a coagulation atmosphere is formed by a pressure of 0.6 kg / cm 2G water vapor, 25% calcium acetate aqueous solution, is dispersed into the container from an internal mixing two-fluid nozzle with an aperture of 2.0mm to form fine droplets below 100 microns. The temperature of the coagulant atmosphere in the container is 60°C, and the pressure of the coagulant atmosphere (pressure inside the container) is set to atmospheric pressure. "The inside of the container where the coagulant atmosphere is formed" can also be referred to as "the coagulation chamber." Regarding the spraying of the aqueous latex (L-A2), 8 hollow cone nozzles (a type of pressurized nozzle) with an aperture of 2.0mm are used, with a spray pressure of 7.3Kg / cm 2 G was sprayed. That is, what was implemented in Example A1 was gas phase coagulation. Next, the slurry was centrifugally dehydrated to obtain a wet powder as the agglomerate. Furthermore, the wet powder obtained was subjected to an operation of putting the wet powder into 500 parts by weight of ion exchange water and an operation of centrifugally dehydrating the mixture obtained in this way, and these two operations were repeated for a total of two cycles (twice), thereby obtaining a wet powder. The moisture content of the wet powder was 57%. Finally, by blowing in dry air at 50°C, the wet powder was made to fly while being dried until the temperature of the wet powder reached 40°C. That is, what was implemented in Example A1 was airflow drying. The dried powder was sieved with a 32-mesh sieve to obtain a powder containing polymer particles (A) and resin (B). The anti-blocking properties of the obtained powder were evaluated, and the result was qualified. The volume average particle size of the obtained powder was measured, and the result was that the volume average particle size was less than 10 mm.
[0586] (Example A2: Preparation of Powder and Granule)
[0587] By the same method as in Example A1, a wet powder with a moisture content of 57% was obtained. Finally, the wet powder was dried while being made to flutter by blowing dry air at 110°C until the temperature of the wet powder reached 40°C. That is, airflow drying was implemented in Example A2. The dried powder was sieved with a 32-mesh sieve to obtain a powder containing polymer particles (A) and resin (B). The anti-blocking properties of the obtained powder were evaluated and the result was qualified. The volume average particle size of the obtained powder was measured and the result was that the volume average particle size was less than 10 mm.
[0588] (Comparative Example A1: Preparation of Powder and Granule)
[0589] By the same method as in Example A1, a wet powder with a moisture content of 57% was obtained. Finally, the wet powder was dried in a box-type dryer at 50°C for 48 hours. That is, the comparative example A1 was dried by standing. The dried powder was sieved with a 32-mesh sieve to obtain a powder containing polymer particles (A) and resin (B).
[0590] (Comparative Example A2: Preparation of Powder and Granule)
[0591] 600 parts by weight of ion exchange water in which 4 parts by weight of calcium acetate was dissolved and the temperature was adjusted at 70°C was prepared. Next, 325 parts by weight of an aqueous latex (L-A1) equivalent to 100 parts by weight of polymer particles (A) and 22.2 parts by weight of the aqueous emulsion (S-A1) (equivalent to 11.1 parts by weight of resin (B)) were added to the 600 parts by weight of ion exchange water to obtain a slurry having a coagulation body containing polymer particles (A) and resin (B). That is, liquid phase coagulation was implemented in Comparative Example A2. Next, the slurry was centrifugally dehydrated to obtain a wet powder as the coagulation body. Furthermore, the obtained wet powder was subjected to an operation of adding the wet powder to 500 parts by weight of ion exchange water and an operation of centrifugally dehydrating the mixture thus obtained, and these two operations were repeated for a total of two cycles (twice), thereby obtaining a wet powder. The moisture content of the wet powder was 60%. Finally, the wet powder was dried in a box-type dryer at 50°C for 48 hours. That is, in Comparative Example A2, static drying was performed. The dried granules were sieved with a 32-mesh sieve to obtain granules containing polymer microparticles (A) and resin (B).
[0592] (Comparative Example A3: Preparation of Powder and Granule)
[0593] 600 parts by weight of ion exchange water in which 4 parts by weight of calcium acetate was dissolved and the temperature was adjusted at 70°C was prepared. Next, 325 parts by weight of an aqueous latex (L-A1) equivalent to 100 parts by weight of polymer particles (A) was added to the 600 parts by weight of ion exchange water to obtain a slurry of a coagulation of polymer particles (A). That is, liquid phase coagulation was implemented in Comparative Example A3. Next, the slurry was centrifugally dehydrated to obtain a wet powder as the coagulation. Furthermore, the obtained wet powder was subjected to an operation of adding the wet powder to 500 parts by weight of ion exchange water and an operation of centrifugally dehydrating the mixture thus obtained, and these two operations were repeated for a total of two cycles (twice), thereby obtaining a wet powder. The moisture content of the wet powder was 58%. Finally, the wet powder was left to dry in a box-type dryer at 50°C for 48 hours. That is, static drying was implemented in Comparative Example A3. The dried powder was sieved with a 32-mesh sieve to obtain a powder containing polymer microparticles (A).
[0594] (Comparative Example A4; Preparation of Powder and Granule)
[0595] The aqueous latex (L-A3) was sprayed into a container (also referred to as a coagulation chamber) in which a coagulation atmosphere was formed, thereby obtaining a slurry having a coagulation body containing polymer particles (A) and resin (B). The coagulation atmosphere in the container was formed according to the following steps: (1) in a cylindrical container having a height of 9 m and a diameter of 1.5 m, 46°C warm water was allowed to flow down along the inner wall surface from a side nozzle installed at the upper part of the inner wall of the container; (2) in parallel with the step (1), a pressure of 0.6 kg / cm 2 G of water vapor, 25% calcium acetate aqueous solution, is dispersed into the container from an internal mixing two-fluid nozzle with an aperture of 2.0mm to form fine droplets of less than 100 microns, thereby forming a coagulable atmosphere. The temperature of the coagulable atmosphere in the container is 60°C, and the pressure of the coagulable atmosphere (pressure inside the container) is set to atmospheric pressure. "The inside of the container where the coagulable atmosphere is formed" can also be referred to as "the coagulation chamber." Regarding the spraying of the aqueous latex (L-A2), 8 hollow cone nozzles (a type of pressurized nozzle) with an aperture of 2.0mm are used, with a spray pressure of 7.3Kg / cm 2 G was sprayed. That is, what was implemented in Comparative Example A4 was gas phase coagulation. Next, the slurry was centrifugally dehydrated to obtain a wet powder as the agglomerate. Furthermore, the wet powder obtained was subjected to an operation of putting the wet powder into 500 parts by weight of ion exchange water and an operation of centrifugally dehydrating the mixture thus obtained, and these two operations were repeated for a total of two cycles (twice), thereby obtaining a wet powder. The moisture content of the wet powder was 56%. Finally, by blowing in dry air at 50°C, the wet powder was made to fly while being dried until the temperature of the wet powder reached 40°C. That is, what was implemented in Comparative Example A4 was airflow drying. The dried powder was sieved with a 32-mesh sieve to obtain a powder containing polymer particles (A). The anti-blocking properties of the obtained powder were evaluated, and the result was qualified. The volume average particle size of the obtained powder was measured, and the result was that the volume average particle size was less than 10 mm.
[0596] (Comparative Example A5; Preparation of Powder and Granule)
[0597] The powder obtained in Comparative Example A4 in an amount equivalent to 100 parts by weight of polymer microparticles (A) and 11.1 parts by weight of the resin (B) were mixed with a planetary agitator at 2000 rpm for 40 minutes. The obtained mixture was then sieved with a 32-mesh sieve to obtain granules. The volume average particle size of the obtained powder was measured, and the volume average particle size was less than 10 mm.
[0598] (Example A3: Preparation of Powder and Granule)
[0599] The following aqueous latex (B) preparation process was carried out. That is, water, resin (B), and SDBS as an emulsifier were mixed to obtain a mixture; then, the obtained mixture was stirred (mixed) using a homogenizer. Through this aqueous latex (B) preparation process, an aqueous latex (B) containing resin (B) as an aqueous latex (S-A2) was obtained, that is, an aqueous latex (B) having one or more droplets (B) containing resin (B) was obtained. The content of resin (B) in 100% by weight of the aqueous latex (S-A2) was 50% by weight. Using the aqueous latex (S-A2) as a material, the volume average particle size (particle size distribution) of the droplets in the aqueous latex (B), i.e., the aqueous latex (S-A2), was determined by the aforementioned method. As a result, the volume average particle size of the droplets in the aqueous latex (S-A2) was 5.60 μm, and the standard deviation was 5.21 μm. Therefore, x-σ is 0.39 and x+5σ is 31.65.
[0600] 325 parts by weight of an aqueous latex (L-A3) equivalent to 100 parts by weight of polymer particles (A) are mixed with 22.2 parts by weight of the aqueous emulsion (S-A2) (equivalent to 11.1 parts by weight of resin (B)). Through this mixing process, a mixed solution containing polymer particles (A) and resin (B), namely, aqueous latex (L-A4) is prepared. Using this mixed solution (aqueous latex (L-A4)) as a material, the volume average particle size and content (particle size distribution) of droplets in the mixed solution are measured by the aforementioned method. As a result, the content of droplets with a volume average particle size of 0.39 or more and 31.65 or less relative to 100% by weight of resin (B) in the mixed solution (aqueous latex (L-A4)) is below the detection limit. In this specification, results below the detection limit are recorded as ND (abbreviation for Not detection). The aqueous latex (L-A4) was sprayed into a container (also referred to as a coagulation chamber) in which a coagulation atmosphere was formed, thereby obtaining a slurry having a coagulation body containing polymer particles (A) and resin (B). The coagulation atmosphere in the container was formed according to the following steps: (1) in a cylindrical container having a height of 9 m and a diameter of 1.5 m, 46°C warm water was allowed to flow down along the inner wall surface from a side nozzle installed at the upper part of the inner wall of the container; (2) in parallel with the step (1), a pressure of 0.6 kg / cm 2 G water vapor, 25% calcium acetate aqueous solution, is dispersed into the container from an internal mixing two-fluid nozzle with an aperture of 2.0mm to form fine droplets of less than 100 microns, thereby forming a coagulable atmosphere. The temperature of the coagulable atmosphere in the container is 60°C, and the pressure of the coagulable atmosphere (pressure inside the container) is set to atmospheric pressure. "The inside of the container where the coagulable atmosphere is formed" can also be called "the coagulation chamber". Regarding the spraying of the aqueous latex (L-A2), 8 hollow cone nozzles (a type of pressurized nozzle) with an aperture of 2.0mm are used, with a spray pressure of 7.3Kg / cm2 G was sprayed. That is, gas phase coagulation was implemented in Example 3. Next, the slurry was centrifugally dehydrated to obtain a wet powder as the agglomerate. Furthermore, the wet powder obtained was subjected to an operation of putting the wet powder into 500 parts by weight of ion exchange water and an operation of centrifugally dehydrating the mixture obtained in this way, and these two operations were repeated for a total of two cycles (twice), thereby obtaining a wet powder. The moisture content of the wet powder was 55%. Finally, by blowing in dry air at 50°C, the wet powder was made to fly while being dried until the temperature of the wet powder reached 40°C. That is, air flow drying was implemented in Example 3. The dried powder was sieved with a 32-mesh sieve to obtain a powder containing polymer particles (A) and resin (B). The anti-blocking property of the obtained powder was evaluated, and the result was qualified. The volume average particle size of the obtained powder was measured, and the result was that the volume average particle size was less than 10 mm.
[0601] [Table 1]
[0602]
[0603] [Example B]
[0604] Hereinafter, an embodiment of the present invention (the second embodiment) will be described in more detail according to Example B and Comparative Example B, but the present invention is not limited to these examples. An embodiment of the present invention can be implemented by appropriately changing within the scope of the aforementioned or later technical gist, and these changed embodiments are also included in the technical scope of the present invention. In addition, in the following Example B and Comparative Example B, "parts" and "%" refer to parts by weight or weight %.
[0605] <Ingredients>
[0606] The components used in each of Production Example B, Example B and Comparative Example B are as follows.
[0607] Polymer microparticles (A)
[0608] The polymer microparticles (A) obtained in Production Example B shown below were used.
[0609] Resin (B)
[0610] The same mixture as used in Example A was used.
[0611] Matrix resin (C)
[0612] The same bisphenol A type epoxy resin as in Example A was used.
[0613] <Evaluation Method>
[0614] First, the evaluation method of the resin composition produced according to Example B and Comparative Example B will be described below.
[0615] (Measurement of volume average particle size)
[0616] The volume average particle size (Mv) of the elastomer or polymer microparticles (A) dispersed in the aqueous latex was measured using the same apparatus as in Example A and using the measurement material prepared by the same method. In the measurement, water and the refractive index of the elastomer or polymer microparticles (A) obtained in each Production Example B were input, the measurement time was set to 120 seconds, and the material concentration was adjusted to satisfy the range of the loading index 1 to 10. In addition, the volume average particle size (Mv) of the powder was measured using the same apparatus as in Example A.
[0617] (Measurement of the volume average particle size and content of droplets in the aqueous latex (B) or the mixed liquid)
[0618] The volume average particle size and content of droplets in the aqueous latex (B) containing the resin (B) or in the mixed solution containing the polymer particles (A) and the resin (B) are measured by using the aqueous latex (B) or the mixed solution as the material and using a laser diffraction particle size distribution measuring device. As the laser diffraction particle size distribution measuring device, MICROTRAC MT3000II (manufactured by MICROTRACBEL Co., Ltd.) is used.
[0619] (Differential Scanning Calorimetry (DSC) of Resin (B))
[0620] The resin (B) used was measured under the same conditions using the same apparatus as in Example A. As a result, similarly to Example A, the DSC thermogram of the resin (B) showed an endothermic peak at -16.9°C.
[0621] (Measurement of Viscosity of Resin (B))
[0622] The viscosity of the resin (B) used was measured using the same apparatus and conditions as in Example A. As a result, similarly to Example A, the viscosity of the resin (B) was 11000 mPa·s.
[0623] (Anti-adhesion properties of powders and particles)
[0624] Using the powders obtained in Example B and Comparative Example B, powder agglomerates were prepared in the same manner as in Example A. Next, the force required to disintegrate the obtained powder agglomerates was measured using a rheometer. Based on the obtained results, the anti-blocking property was evaluated according to the following criteria.
[0625] Acceptable: The force required to disintegrate the agglomerates of the powder or granules is 30,000 Pa or less.
[0626] Unqualified: The force required to disintegrate the agglomerate of powder and particles exceeds 30,000 Pa.
[0627] (Dispersibility of resin composition)
[0628] 15 parts by weight (15 g) of the powder obtained by Example B and Comparative Example B and 85 parts by weight (85 g) of bisphenol A epoxy resin as a matrix resin (C) were prepared. The prepared powder and bisphenol A epoxy resin were added to a container with a volume of 200 mL to mix and obtain a resin composition. The volume of the container is about twice the volume of the prepared powder and bisphenol A epoxy resin. A disperser with a stirring blade having a blade diameter of Φ32 mm (manufactured by PRIMIX Co., Ltd.) was used to mix the obtained resin composition at a rotation speed of 3000 rpm. The resin composition was placed on a particle size meter (particle size measuring disk), and the resin composition on the measuring disk was scraped flat with a metal scraper to visually confirm the dispersion state. The corresponding scale marks at the positions where 5 to 10 granular marks were left by the scraper movement in the 3 mm wide measuring band were read, and the stirring time from the start of stirring until the corresponding scale marks finally reached 0 μm was measured, that is, the stirring time until the dispersion reached a good state was measured. The results are shown in Table 2.
[0629] <1. Preparation of elastomer>
[0630] (Production Example B)
[0631] (Manufacturing Example B1-1: Preparation of Polystyrene-Butadiene Rubber Latex (R-B1))
[0632] In the pressure polymerizer, 160 parts by weight of deionized water, 0.002 parts by weight of disodium ethylenediaminetetraacetate (EDTA), 0.001 parts by weight of ferrous sulfate 7 hydrate, 0.02 parts by weight of polyoxyethylene lauryl ether phosphoric acid, and 0.003 parts by weight of sodium hydroxide were added. Here, polyoxyethylene lauryl ether phosphoric acid becomes sodium polyoxyethylene lauryl ether phosphate in the presence of sodium hydroxide and functions as an emulsifier. Next, while stirring the added raw materials, the gas inside the pressure polymerizer is replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 76.5 parts by weight of butadiene (Bd) and 23.5 parts by weight of styrene (St) are added to the pressure polymerizer, and the temperature inside the pressure polymerizer is raised to 45°C. Thereafter, 0.03 parts by weight of p-menthane hydrogen peroxide (PHP) is added to the pressure polymerizer, and then 0.05 parts by weight of sodium formaldehyde sulfoxylate (SFS) is added to the pressure polymerizer to start polymerization. At 20 hours after the start of polymerization, devolatilization was carried out under reduced pressure to remove the monomers that were not used in the polymerization and remained, thereby terminating the polymerization. Here, during the polymerization process, PHP, polyoxyethylene lauryl ether phosphate and sodium hydroxide were added to the pressure-resistant polymerizer in any amount and at any time. Through this polymerization, an aqueous latex (R-B1) containing an elastomer (core layer) with polystyrene-butadiene rubber as the main component was obtained. The volume average particle size of the elastomer (core layer) contained in the obtained aqueous latex was 240nm.
[0633] (Manufacturing Example B1-2: Preparation of Polystyrene-Butadiene Rubber Latex (R-B2))
[0634] In the pressure polymerizer, 160 parts by weight of deionized water, 0.002 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate 7-hydrate, 0.05 parts by weight of polyoxyethylene lauryl ether phosphoric acid, and 0.003 parts by weight of sodium hydroxide are added. Here, polyoxyethylene lauryl ether phosphoric acid becomes sodium polyoxyethylene lauryl ether phosphate in the presence of sodium hydroxide and functions as an emulsifier. Next, while stirring the added raw materials, the gas inside the pressure polymerizer is replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 76.5 parts by weight of Bd and 23.5 parts by weight of St are added to the pressure polymerizer, and the temperature inside the pressure polymerizer is raised to 45°C. Thereafter, 0.03 parts by weight of PHP is added to the pressure polymerizer, and then 0.05 parts by weight of SFS is added to the pressure polymerizer to start polymerization. At 25 hours after the start of polymerization, devolatilization was carried out under reduced pressure to remove the monomers that were not used in the polymerization and remained, thereby terminating the polymerization. Here, during the polymerization process, PHP, polyoxyethylene lauryl ether phosphate and sodium hydroxide were added to the pressure-resistant polymerizer in any amount and at any time. Through this polymerization, an aqueous latex (R-B2) containing an elastomer (core layer) with polystyrene-butadiene rubber as the main component was obtained. The volume average particle size of the elastomer (core layer) contained in the obtained aqueous latex was 170nm.
[0635] (Manufacturing Example B1-3: Preparation of Polystyrene-Butadiene Rubber Latex (R-B3))
[0636] In the pressure polymerizer, 160 parts by weight of deionized water, 0.002 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate 7-hydrate, 0.07 parts by weight of polyoxyethylene lauryl ether phosphoric acid, and 0.003 parts by weight of sodium hydroxide are added. Here, polyoxyethylene lauryl ether phosphoric acid becomes sodium polyoxyethylene lauryl ether phosphate in the presence of sodium hydroxide and functions as an emulsifier. Next, while stirring the added raw materials, the gas inside the pressure polymerizer is replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 76.5 parts by weight of Bd and 23.5 parts by weight of St are added to the pressure polymerizer, and the temperature inside the pressure polymerizer is raised to 45°C. Thereafter, 0.03 parts by weight of PHP is added to the pressure polymerizer, and then 0.05 parts by weight of SFS is added to the pressure polymerizer to start polymerization. At 25 hours after the start of polymerization, devolatilization was carried out under reduced pressure to remove the monomers that were not used in the polymerization and remained, thereby ending the polymerization. Here, during the polymerization process, PHP, polyoxyethylene lauryl ether phosphate and sodium hydroxide were added to the pressure-resistant polymerizer in any amount and at any time. Through this polymerization, an aqueous latex (R-B3) containing an elastomer (core layer) with polystyrene-butadiene rubber as the main component was obtained. The volume average particle size of the elastomer (core layer) contained in the obtained aqueous latex was 150nm.
[0637] (Manufacturing Example B1-4: Preparation of Polystyrene-Butadiene Rubber Latex (R-B4))
[0638] In the pressure polymerizer, 200 parts by weight of deionized water, 0.03 parts by weight of tripotassium phosphate, 0.002 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate 7-hydrate, and 1.5 parts by weight of sodium dodecylbenzene sulfonate (SDBS) as an emulsifier were added. Next, while stirring the added raw materials, the gas inside the pressure polymerizer was replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 76.5 parts by weight of Bd and 23.5 parts by weight of St were added to the pressure polymerizer, and the temperature inside the pressure polymerizer was raised to 45°C. Thereafter, 0.03 parts by weight of PHP was added to the pressure polymerizer, and then 0.10 parts by weight of SFS was added to the pressure polymerizer to start polymerization. At 13 hours after the start of polymerization, devolatilization was carried out under reduced pressure to devolatilize and remove the monomers that were not used in the polymerization and remained, thereby ending the polymerization. Here, during the polymerization process, PHP, EDTA and ferrous sulfate 7-hydrate salt were added to the pressure-resistant polymerization vessel in any amount and at any time. Through the polymerization, an aqueous latex (R-B4) containing an elastomer (core layer) mainly composed of polystyrene-butadiene rubber was obtained. The volume average particle size of the elastomer (core layer) contained in the obtained aqueous latex was 80nm.
[0639] (Manufacturing Example B1-5; Preparation of polybutadiene rubber latex (R-B5))
[0640] In the pressure polymerizer, 200 parts by weight of deionized water, 0.03 parts by weight of tripotassium phosphate, 0.002 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate 7-hydrate, and 1.55 parts by weight of sodium dodecylbenzene sulfonate (SDBS) as an emulsifier are added. Next, while stirring the added raw materials, the gas inside the pressure polymerizer is replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 100 parts by weight of Bd are added to the pressure polymerizer, and the temperature inside the pressure polymerizer is raised to 45°C. Thereafter, 0.03 parts by weight of PHP are added to the pressure polymerizer, and then 0.10 parts by weight of SFS are added to the pressure polymerizer to start polymerization. At 15 hours after the start of polymerization, devolatilization is carried out under reduced pressure to devolatilize and remove the monomers that are not used in the polymerization and remain, thereby ending the polymerization. Here, during the polymerization process, PHP, EDTA and ferrous sulfate 7 hydrate salt were added to the pressure-resistant polymerization vessel in any amount and at any time. Through the polymerization, an aqueous latex (R-B5) containing an elastomer with polybutadiene rubber as the main component was obtained. The volume average particle size of the elastomer contained in the obtained aqueous latex was 90nm.
[0641] (Manufacturing Example B1-6; Preparation of polybutadiene rubber latex (R-B6))
[0642] In the pressure polymerizer, 7 parts by weight of an elastomer containing polybutadiene rubber as the main component of polybutadiene rubber, an aqueous latex of polybutadiene rubber (R-B5), 200 parts by weight of deionized water, 0.03 parts by weight of tripotassium phosphate, 0.002 parts by weight of EDTA, and 0.001 parts by weight of ferrous sulfate 7 hydrate were added. Next, while stirring the added raw materials, the gas inside the pressure polymerizer was replaced with nitrogen, thereby fully removing oxygen from the inside of the pressure polymerizer. Thereafter, 93 parts by weight of Bd were added to the pressure polymerizer, and the temperature inside the pressure polymerizer was raised to 45°C. Thereafter, 0.02 parts by weight of PHP were added to the pressure polymerizer, and then 0.10 parts by weight of SFS were added to the pressure polymerizer to start polymerization. At 30 hours after the start of polymerization, devolatilization was carried out under reduced pressure to remove the monomers remaining in the polymerization without being used, thereby terminating the polymerization. Here, during the polymerization process, PHP, EDTA, and ferrous sulfate 7-hydrate salt were added to the pressure-resistant polymerization vessel in any amount and at any time. Through the polymerization, an aqueous latex (R-B6) containing an elastomer (core layer) with polybutadiene rubber as the main component was obtained. The volume average particle size of the elastomer (core layer) contained in the obtained aqueous latex was 195 nm.
[0643] <2. Preparation of polymer microparticles (A) (polymerization of grafted part)>
[0644] (Production Example B2-1; Preparation of latex of polymer microparticles (L-B1))
[0645] In a glass reactor, 201 parts by weight of an aqueous latex (latex of the polystyrene-butadiene rubber) (R-B1) containing an elastomer (core layer) (containing 70 parts by weight of an elastomer with polystyrene-butadiene rubber as the main component) and 73 parts by weight of deionized water are added. Here, the glass reactor has a thermometer, a stirrer, a reflux cooler, a nitrogen inlet, and a monomer addition device. The gas in the glass reactor was replaced with nitrogen, and the raw materials added were stirred at 60°C. Next, 0.003 parts by weight of EDTA, 0.0007 parts by weight of ferrous sulfate 7 hydrate, and 0.14 parts by weight of SFS were added to the glass reactor and stirred for 10 minutes. Thereafter, a mixture of 28.5 parts by weight of methyl methacrylate (MMA), 1.5 parts by weight of butyl acrylate, and 0.1 parts by weight of tert-butyl hydroperoxide (BHP) was continuously added to the glass reactor over a period of 80 minutes. Thereafter, 0.012 parts by weight of BHP was added to a glass reactor, and the mixture in the glass reactor was continuously stirred for 1 hour to complete the polymerization. Through the above operation, an aqueous latex (L-B1) containing polymer particles (A) was obtained. The polymerization conversion rate of its monomer components was more than 99%. The volume average particle size of the polymer particles (A) contained in the obtained aqueous latex was 240 nm. The solid content concentration (concentration of polymer particles (A)) in the obtained aqueous latex (L-B1) was 30%.
[0646] (Production Example B2-2: Preparation of latex of polymer microparticles (L-B2))
[0647] On the basis of Manufacturing Example B2-1, an aqueous latex (R-B2) containing an elastomer (core layer) was used to replace the aqueous latex (R-B1) containing an elastomer (core layer). Except for this, an aqueous latex (L-B2) containing polymer particles (A) was obtained by the same method as in Manufacturing Example B2-1. The polymerization conversion rate of its monomer components is more than 99%. The volume average particle size of the polymer particles (A) contained in the obtained aqueous latex is 170nm. The solid content concentration (concentration of polymer particles (A)) in the obtained aqueous latex (L-B2) is 30%.
[0648] (Manufacturing Example B2-3; Preparation of latex of polymer microparticles (L-B3))
[0649] On the basis of Manufacturing Example B2-1, an aqueous latex (R-B3) containing an elastomer (core layer) was used to replace the aqueous latex (R-B1) containing an elastomer (core layer). Except for this, an aqueous latex (L-B3) containing polymer particles (A) was obtained by the same method as Manufacturing Example B2-1. The polymerization conversion rate of its monomer components is more than 99%. The volume average particle size of the polymer particles (A) contained in the obtained aqueous latex is 150nm. The solid content concentration (concentration of polymer particles (A)) in the obtained aqueous latex (L-B3) is 30%.
[0650] (Manufacturing Example B2-4; Preparation of latex of polymer microparticles (L-B4))
[0651] On the basis of Manufacturing Example B2-1, an aqueous latex (R-B4) containing an elastomer (core layer) was used instead of an aqueous latex (R-B1) containing an elastomer (core layer). Except for this, an aqueous latex (L-B4) containing polymer particles (A) was obtained by the same method as Manufacturing Example B2-1. The polymerization conversion rate of its monomer components is more than 99%. The volume average particle size of the polymer particles (A) contained in the obtained aqueous latex is 80nm. The solid content concentration (concentration of polymer particles (A)) in the obtained aqueous latex (L-B4) is 30%.
[0652] (Manufacturing Example B2-5; Preparation of Aqueous Latex (L-B5) Containing Polymer Microparticles (A))
[0653] In a glass reactor, 215 parts by weight of an aqueous latex of polybutadiene rubber (R-B6) (including 71 parts by weight of an elastomer with polybutadiene rubber as the main component) and 82 parts by weight of deionized water were added. Here, the glass reactor has a thermometer, a stirrer, a reflux cooler, a nitrogen inlet, and a monomer addition device. While replacing the gas in the glass reactor with nitrogen, the raw materials added at 60°C were stirred. Next, 2.6 parts by weight of 1,3-butylene di(methacrylate) ester and 0.07 parts by weight of BHP were added to the glass reactor and stirred for 10 minutes. Thereafter, 0.004 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate 7 hydrate, and 0.13 parts by weight of SFS were added to the glass reactor and stirred for 30 minutes. Thereafter, 0.013 parts by weight of BHP was added to the glass reactor and further stirred for 30 minutes. Thereafter, a mixture of 22 parts by weight of MMA, 7 parts by weight of St and 0.085 parts by weight of BHP was continuously added to the glass reactor over 70 minutes. Thereafter, 0.013 parts by weight of BHP was added to the glass reactor, and the mixture in the glass reactor was continuously stirred for 1 hour to complete the polymerization. Through the above operation, an aqueous latex (L-B5) containing polymer particles (A) was obtained. The polymerization conversion rate of its monomer components was more than 99%. The volume average particle size of the polymer particles (A) contained in the obtained aqueous latex was 200nm.
[0654] <3. Preparation of powder and granules>
[0655] Example B1 (Production Example B3-1)
[0656] The following aqueous latex (B) preparation process was carried out. That is, water, 100 parts by weight of resin (B), and 6.5 parts by weight of sodium polyoxyethylene lauryl ether phosphate as an emulsifier were mixed to obtain a mixture; then, the obtained mixture was stirred at 10,000 rpm for 5 minutes using a homogenizer. Through this aqueous latex (B) preparation process, an aqueous latex (B) containing resin (B) as an aqueous latex (S-B1) was obtained, that is, an aqueous latex (B) having more than one droplet (B) containing resin (B) was obtained. The content of resin (B) in 100% by weight of the aqueous latex (S-B1) was 50% by weight. Using the aqueous latex (S-B1) as a material, the volume average particle size (particle size distribution) of the droplets in the aqueous latex (B), i.e., the aqueous latex (S-B1), was determined by the aforementioned method. As a result, the volume average particle size of the droplets in the aqueous latex (S-B1) was 11.17 μm, and the standard deviation was 8.18 μm. Therefore, x-σ was 2.99, and x+5σ was 52.07.
[0657] 325 parts by weight of an aqueous latex (L-B1) equivalent to 100 parts by weight of polymer particles (A) are mixed with 22.2 parts by weight of an aqueous latex (S-B1) equivalent to 11.1 parts by weight of a resin (B). Through this mixing process, a mixed solution containing polymer particles (A) and resin (B) is obtained. The obtained mixed solution is used as a material, and the volume average particle size and content (particle size distribution) of the droplets in the mixed solution are determined by the aforementioned method. As a result, the droplets with a volume average particle size of greater than 2.99 and less than 52.07 are below the detection limit relative to the content of 100% by weight of the resin (B) in the mixed solution. In this specification, the results below the detection limit are recorded as ND (abbreviation for Not detection).
[0658] Next, the following preparation process was performed. That is, first, 600 parts by weight of ion exchange water in which 4 parts by weight of calcium acetate was dissolved and the temperature was adjusted to 70°C was prepared; then, 347.2 parts by weight of the mixed solution obtained by the mixing process was added to the 600 parts by weight of the ion exchange water to obtain a slurry having an aggregate containing polymer microparticles (A) and resin (B); then, the slurry was centrifugally dehydrated to obtain a wet powder as the aggregate. Furthermore, the wet powder was subjected to an operation of adding the wet powder to 500 parts by weight of ion exchange water and an operation of centrifugally dehydrating the mixture thus obtained, and these two operations were repeated for a total of two cycles (twice) to obtain a wet powder; finally, the wet powder was dried in a dryer at 50°C for 48 hours to obtain a powder containing polymer microparticles (A) and resin (B). The anti-blocking property of the obtained powder was evaluated and the result was qualified. The volume average particle size of the obtained powder was measured and the volume average particle size was less than 10 mm.
[0659] Comparative Example B1 (Production Example B3-2)
[0660] The aqueous latex (B) preparation process was carried out in the following manner. That is, water, 100 parts by weight of resin (B), and 24.0 parts by weight of sodium polyoxyethylene lauryl ether phosphate as an emulsifier were mixed to obtain a mixture; then, the obtained mixture was stirred at 10,000 rpm for 5 minutes using a homogenizer. Through this aqueous latex (B) preparation process, an aqueous latex (B) containing resin (B) as an aqueous latex (S-B2) was obtained, that is, an aqueous latex (B) having more than one droplet (B) containing resin (B) was obtained. The content of resin (B) in 100% by weight of the aqueous latex (S-B2) was 50% by weight. Using the aqueous latex (S-B2) as a material, the volume average particle size (particle size distribution) of the droplets in the aqueous latex (B), i.e., the aqueous latex (S-B2), was determined by the aforementioned method. As a result, the volume average particle size of the droplets in the aqueous latex (S-B2) was 1.46 μm, and the standard deviation was 0.6 μm. Therefore, x-σ was 0.86, and x+5σ was 4.46.
[0661] 325 parts by weight of aqueous latex (L-B1) equivalent to 100 parts by weight of polymer particles (A) and 22.2 parts by weight of aqueous latex (S-B2) equivalent to 11.1 parts by weight of resin (B) were mixed. Through this mixing process, a mixed solution containing polymer particles (A) and resin (B) was obtained. The obtained mixed solution was used as a material, and the volume average particle size and content (particle size distribution) of the droplets in the mixed solution were determined by the aforementioned method. As a result, the content of droplets with a volume average particle size of more than 0.86 and less than 4.46 was 14.8% by weight relative to 100% by weight of resin (B) in the mixed solution. The results are shown in Table 2.
[0662] Next, using the mixed solution obtained in the mixing step, a preparation step was carried out by the same method as in Production Example B3-1 to obtain a powder or granular body.
[0663] Example B2 (Production Example B3-3)
[0664] The following aqueous latex (B) preparation process was carried out. That is, water, 100 parts by weight of resin (B), and 13.0 parts by weight of sodium polyoxyethylene lauryl ether phosphate as an emulsifier were mixed to obtain a mixture; then, the obtained mixture was stirred at 10,000 rpm for 5 minutes using a homogenizer. Through this aqueous latex (B) preparation process, an aqueous latex (B) containing resin (B) as an aqueous latex (S-B3) ...
Claims
1. A powder or granule comprising polymer particles (A) and a resin (B), The polymer microparticles (A) include a rubber-containing graft copolymer, wherein the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer. The elastomer comprises a diene rubber, The diene rubber contains, in 100 wt % of its structural units, 50 to 100 wt % of structural units derived from a diene monomer and 0 to 50 wt % of structural units derived from a vinyl monomer other than the diene monomer and copolymerizable with the diene monomer. The diene monomer is at least one selected from 1,3-butadiene, 2-methyl-1,3-butadiene, and 2-chloro-1,3-butadiene. The vinyl monomer copolymerizable with the diene monomer and other than the diene monomer is at least one selected from the following: (a) styrene, α-methylstyrene, monochlorostyrene, dichlorostyrene; (b) acrylic acid, methacrylic acid; (c) acrylonitrile, methacrylonitrile; (d) vinyl chloride, vinyl bromide, chloroprene; (e) vinyl acetate; (f) ethylene, propylene, butylene, isobutylene; (g) diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, divinylbenzene, The graft portion includes a polymer having a specific structural unit, and the specific structural unit is derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer. The resin (B) is a liquid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., or is a semisolid or solid. When the total amount of the polymer fine particles (A) and the resin (B) is 100 wt %, the polymer fine particles (A) are 50 to 99 wt %, and the resin (B) is 1 to 50 wt %. The powder or granular material has pores with an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is 0.0600 mL / g or more. Of 100 wt % of the powder or granule, 3.00 wt % or less of the powder or granule has a volume average particle size of 1000 μm or more.
2. The powder or granular material according to claim 1, wherein Of 100 wt % of the powder or granule, 6.00 wt % or less of the powder or granule has a volume average particle size of 600 μm or more.
3. The powder or granular material according to claim 1 or 2, wherein: The powder or granule has pores with an average pore diameter of 0.03 μm to 1.00 μm, and the total volume of the pores is 0.0800 mL / g or more.
4. The powder or granule according to claim 1 or 2, wherein The powder or granule has pores with an average pore diameter of 0.03 μm to 4.50 μm, and the total volume of the pores is 0.1100 mL / g or more.
5. The powder or granular material according to claim 1 or 2, wherein: Of 100 wt % of the powder or granule, 1.90 wt % or less of the powder or granule has a volume average particle size of 600 μm or more.
6. The powder or granular material according to claim 1 or 2, wherein: The force required to disintegrate the agglomerates of the powder and granules is 30000 Pa or less, The agglomerate is obtained by placing a 6.3 kg weight on 30 g of the powder or granule contained in a cylindrical container having a diameter of 50 mm and leaving the container at 60° C. for 2 hours to apply a 6.3 kg load to the powder or granule. The force is a value measured by a rheometer.
7. The powder or granular material according to claim 1 or 2, wherein: The volume average particle size of the polymer fine particles (A) is 0.23 μm or less.
8. A resin composition, The invention comprises the powder or granular material according to any one of claims 1 to 7 and a matrix resin (C).
9. A method for producing a powder or granule, comprising: A coagulation step for preparing a coagulation body containing polymer particles (A) and resin (B); A drying step is to air dry or freeze dry the agglomerate. in, The polymer microparticles (A) include a rubber-containing graft copolymer, wherein the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer. The elastomer comprises a diene rubber, The diene rubber contains, in 100 wt % of its structural units, 50 to 100 wt % of structural units derived from a diene monomer and 0 to 50 wt % of structural units derived from a vinyl monomer other than the diene monomer and copolymerizable with the diene monomer. The diene monomer is at least one selected from 1,3-butadiene, 2-methyl-1,3-butadiene, and 2-chloro-1,3-butadiene. The vinyl monomer copolymerizable with the diene monomer and other than the diene monomer is at least one selected from the following: (a) styrene, α-methylstyrene, monochlorostyrene, dichlorostyrene; (b) acrylic acid, methacrylic acid; (c) acrylonitrile, methacrylonitrile; (d) vinyl chloride, vinyl bromide, chloroprene; (e) vinyl acetate; (f) ethylene, propylene, butylene, isobutylene; (g) diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, divinylbenzene, The graft portion includes a polymer having a specific structural unit, and the specific structural unit is derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer. The resin (B) is a liquid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., or is a semisolid or solid. When the total amount of the polymer fine particles (A) and the resin (B) is 100% by weight, the polymer fine particles (A) are 50 to 99% by weight, and the resin (B) is 1 to 50% by weight.
10. The method for producing a powder or granule according to claim 9, wherein: The agglomeration step further includes a polymer fine particle spraying step of spraying an aqueous latex containing the polymer fine particles (A) and the resin (B) in the presence of a coagulant.
11. The method for producing a powder or granule according to claim 10, wherein: The aggregation step further includes a coagulant spraying step of spraying the coagulant or a solution containing the coagulant in the presence of the polymer fine particles (A) and the resin (B).
12. The method for producing a powder or granule according to any one of claims 9 to 11, wherein: The drying step is performed at a temperature of 100° C. or lower.
13. A method for producing a powder or granule, comprising: A mixing step of mixing an aqueous latex (A) containing polymer particles (A) and an aqueous latex (B) containing a resin (B); a preparation step of preparing a powder containing the polymer microparticles (A) and the resin (B) using the mixed solution obtained in the mixing step; in, The polymer microparticles (A) include a rubber-containing graft copolymer, wherein the rubber-containing graft copolymer has an elastomer and a graft portion graft-bonded to the elastomer. The elastomer comprises a diene rubber, The diene rubber contains, in 100 wt % of its structural units, 50 to 100 wt % of structural units derived from a diene monomer and 0 to 50 wt % of structural units derived from a vinyl monomer other than the diene monomer and copolymerizable with the diene monomer. The diene monomer is at least one selected from 1,3-butadiene, 2-methyl-1,3-butadiene, and 2-chloro-1,3-butadiene. The vinyl monomer copolymerizable with the diene monomer and other than the diene monomer is at least one selected from the following: (a) styrene, α-methylstyrene, monochlorostyrene, dichlorostyrene; (b) acrylic acid, methacrylic acid; (c) acrylonitrile, methacrylonitrile; (d) vinyl chloride, vinyl bromide, chloroprene; (e) vinyl acetate; (f) ethylene, propylene, butylene, isobutylene; (g) diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, divinylbenzene, The graft portion includes a polymer having a specific structural unit, and the specific structural unit is derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer. The resin (B) is a liquid having a viscosity of 100 mPa·s to 1,000,000 mPa·s at 25° C., or is a semisolid or solid. The powder or granule comprises: 50 to 99 wt % of the polymer fine particles (A) and 1 to 50 wt % of the resin (B) in a total of 100 wt % of the polymer fine particles (A) and the resin (B); When the volume average particle size of the droplets in the aqueous latex (B) is set to x (μm) and the standard deviation of the volume average particle size is set to σ, the mixed liquid contains: 0.0 weight% to 14.0 weight% of droplets with a volume average particle size greater than x-σ and less than x+5σ relative to 100 weight% of the resin (B) in the mixed liquid.
14. The method for producing a powder or granule according to any one of claims 9, 10, 11 or 13, wherein: The force required to disintegrate the agglomerates of the powder and granules is 30000 Pa or less, The agglomerate is obtained by placing a 6.3 kg weight on 30 g of the powder or granule contained in a cylindrical container having a diameter of 50 mm and leaving the container at 60° C. for 2 hours to apply a 6.3 kg load to the powder or granule. The force is a value measured by a rheometer.
15. The method for producing a powder or granule according to any one of claims 9, 10, 11 or 13, wherein: The volume average particle size of the polymer fine particles (A) is 0.23 μm or less.
Citation Information
Patent Citations
Thermosetting forming composition and manufacture of product
JP1980157620A
Melamine-formaldehyde polycondensate
JP1993202157A
New amino resin composition
JP1997143238A
Polyisocyanurate compositions and composite materials
JP2002530445A
Laminate and method of manufacturing the same
JP2003220661A